Selenomethionine attenuates deoxynivalenol-induced jejunal injury in rabbits by activating the mTOR pathway and inhibiting NF-κB activation - Lan Wei; Jianing Sun; Mengqi Miao; Mengyu Zhang; Min Cui; Yumei Liu; Xuemin Zhu; Ziqiang Zhang (Tissue and Cell, 2027)

A novel titanium-based metal–organic material with abundant oxygen vacancies and hierarchical porosity for room-temperature oxidative desulfurization - Gan Ye; Yue Zhang; Min Wan; Boyu Cui; Weixue Zhang; Jinghan Wang; Jintao Liu; Jun Zhou; Nijun Xu; Qiuli Zhang (Fuel, 2026)

Three-stage integrated co-digestion of pig manure and rice straw combined with biogas slurry reflux: Performance and application evaluation - Kaitao Peng; Min Sun; Wei Zeng; Qi Zhang; Yunpu Wang; Shuyu Xiang; Yuhuan Liu; Xian Cui (Bioresource Technology, 2026)

The progress of mitochondrial function and transfer in stem cell regulation and therapy - Yubing Zhang; Zhuojian Qu; Zhiliang Guo; Lijuan Zhang; Hong Li; Xiaoyun Zhang; Xiumei Guan; Xiaodong Cui; Wenxu Wang; Min Cheng (Journal of Physiology and Biochemistry, 2026)

The responses of microbial extracellular enzyme activities to soil sample storage conditions across different soil types - Panpan Liu; Jiacong Zhou; Chris Freeman; Mallavarapu Megharaj; Kyungjin Min; Linchuan Fang; Gangsheng Wang; Lars Elsgaard; Nicolas Fanin; Hojeong Kang; Taiki Mori; Jianwei Li; et al. (Soil Ecology Letters, 2026)

Global prevalence of tigecycline-resistant foodborne Enterobacterales along the food chain: A meta-analysis - Mei Li; Siyue Wang; Kaiyi Zhao; Yinuo Yang; Min Li; Jingsen Zhang; Shenghui Cui; Jia Chen; Jiaoyi Luo; Baowei Yang (Food Research International, 2026)

Enhancing resistance against white spot syndrome virus in Litopenaeus vannamei via recombinant Lactobacillus acidophilus through modulation of gut microbiota function - Hang Zhang; Wei Liu; Yi-Ning Cui; Pei-Min He; Ji-shun Yang; Rui Jia (Aquaculture, 2026)

Phytoplankton biomass evolution and its drivers in the deep water entrance south of the Taiwan strait since 14 cal ka BP: insights from biomarker reconstructions - Junwen Wu; Zitong Liu; Xiuli Yan; Yuzheng Liao; Cui Wang; Min Chen; Aijun Wang; Shuqin Tao (Quaternary Science Reviews, 2026)

Discovery of garnet-bearing peraluminous ferroan granites in the Trans-North China Orogen: Evidence for anatexis of residual metasedimentary crust in a hot collisional orogen - Jing-Jing Fan; Caiyun Lan; Yong-Min Li; Jun Rao; Zi-Long Wang; Ze-Xian Cui; Meng-Jing Li; Xiaoping Long (Precambrian Research, 2026)

Genomic characterization of the convergence of multidrug resistance and virulence in Salmonella Enteritidis from a broiler slaughterhouse in China - Xinfeng Han; Junfeng Peng; Junlin Li; Ruyi Kuang; Haotian Liu; Jing Xia; Min Cui; Yong Huang; Likou Zou (International Journal of Food Microbiology, 2026)

Machine-learning-assisted multistage resonant gradient-impedance metastructure for broadband, wide-angle microwave absorption and multifunctional integration - Zihao Kang; Min Xi; Shudong Zhang; Cui Liu; Yaodong Wang; Dawei Zhu; Zhimei Xu; Usman Ali; Mohamed M. Salem; Nian Li; Zhenyang Wang (Chemical Engineering Journal, 2026)

Biomimetic damping eutectic gels enabled by comonomer-regulated phase separation for motion-artifact-resistant bioelectrodes - Menghan Pi; Yichun Zhang; Zihe Liu; Wenhao Li; Min Li; Honglin Wu; Wei Cui; Rong Ran (Chemical Engineering Journal, 2026)

Spatially distinct biomineralization patterns across granules and biofilms enhance phosphorus recovery in hybrid anammox reactor with simultaneous nitrogen removal - Weiyi Wang; Min Ye; Shen Cui; Junho Cha; Kengo Kubota; Yu-You Li (Chemical Engineering Journal, 2026)

Resolving the nitrogen retention-maturity dilemma in sulfur-amended composting via compost tea post-treatment - Weiwei Wang; Peng Zhang; Haoxing He; Min Chen; Huiban He; Hongliang Wang; Zongjun Cui; Boting Wen; Xufeng Yuan (Chemical Engineering Journal, 2026)

The upgrading and transformation of rice straw biogas engineering: efficient lactic acid production strategy in the lactic acid-biogas-fertilizer model - Xuan Luo; Min Sun; Wei Zeng; Qi Zhang; Yunpu Wang; Yuhuan Liu; Xian Cui (Bioresource Technology, 2026)

Chemical constituents from the aerial parts of Rauvolfia yunnanensis Tsiang and their chemotaxonomic significance - Wanqi Yang; Xiaoyan Cui; Renfeng Ye; Min Jiang; Shijing Tang; Wenjing Dong; Guiguang Cheng; Yaping Liu (Biochemical Systematics and Ecology, 2026)

Triply activated localized DNA circuit based on dual enzyme-guaranteed and analyte-stimulated strategy for robust tumor-cell-specific microRNA imaging - Yuanyuan Peng; Xiaoyu Wang; Wanling Cui; Rui Wang; Haiyan Zhao; Ning Zhang; Min Liu; Yushu Wu (Analytica Chimica Acta, 2026)

Novel analytical approach for the longitudinal vibration of floating pile groups in layered soils considering partial embedment - Kun Meng; Mingchen Zhong; Bo Min; Chunyi Cui; Mirlan Muktarovich Dyldaev; Zhenguo Lu; Bo Zhu; Chunshuo Jiao; Jun Zhao (Soil Dynamics and Earthquake Engineering, 2026)

Trade-offs between photosynthetic capacity and structural economy underlie the rapid proliferation of floating Ulva prolifera - Ruili Niu; Cancan Xia; Min Cha; Cui Han; Bojian Zhong; Xiaojie Liu (Harmful Algae, 2026)

Constraining marine silicate alteration in volcanic material-rich continental margin sediments since the last Glacier Maximum evidenced by stable Si isotopes - Quanchao Cui; Min Luo; Wei-Li Hong; Tzu-Hao Huang; Weidong Sun; Xiaole Sun (Geochimica et Cosmochimica Acta, 2026)

Global prevalence and distribution of bla-harboring Salmonella: A genome-wide association study of cephalosporin resistance mechanisms - Qiuping Yang; Jingsen Zhang; Tianxi Chen; Min Li; Mei Li; Huanjing Sheng; Shenghui Cui; Baowei Yang (Food Microbiology, 2026)

High-fidelity phase-change transfer platform for laser-induced graphene toward multifunctional flexible electronics - Zhao Li; Yanping Song; Wenjie Shao; Jun Kang; Na Hong; Shuai Han; Shihao Wang; Zhiyuan Yang; Zhuang Miao; Shudong Zhang; Cui Liu; Min Xi; et al. (Chemical Engineering Journal, 2026)

Bio-instructive polyetheretherketone implants combat implant-associated bone infections through inducing bacterial cuproptosis-like death and promoting peri-implant immune remodeling - Weinan Yang; Tao Zhang; Yongwei Zhou; Zizhan Su; Zihao An; Congsun Li; Jiaxuan Zou; Wushi Cui; Wentao Chen; Jian Xiao; Tao Sun; Shicheng Wang; et al. (Chemical Engineering Journal, 2026)

Identification of Novel Polysaccharide from Myxococcus xanthus and its Function in Developmental Sporulation - Lin Liu; Songchen Jiang; Guirong Yang; Wenming Chang; Jin Lin; Lujun Zhang; Yijia Xu; Xinyu Li; Jie Bai; Lei Zhang; Xianfeng Ye; Yan Huang; et al. (Current Microbiology, 2026)

LSTM-Driven Digital Groundwater Monitoring and Environmental Risk Assessment for Coal Mining Areas - Feng-zuo Guo; Guo-hui Wang; Zhen-yang Liu; Yu-min Jiang; Hai-cui Wang (Applied Geophysics, 2026)

Unraveling non-linear environmental controls on soil organic carbon in arid China: An interpretable machine learning approach - Zhun Zhao; Peng Shi; Jun Xiao; Zhiqiang Min; Zhanbin Li; Peng Li; Lulu Bai; Linzhou Cui (Journal of Mountain Science, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Foliar coronatine synergizes with rhizosphere-inoculated Trichoderma viride to suppress root rot by reshaping rhizosphere microbiome - Lifen Luo; Yuqi He; Gaihui Li; Kedan Wang; Xiubei Yan; Chaocang Chen; Shusheng Zhu; Guangfen Cui; Min Yang (Pesticide Biochemistry and Physiology, 2026)

Chronic intermittent hypobaric hypoxia ameliorates iron metabolism disorder through ferritinophagy in collagen-induced arthritis mice - XueRui Fu; Fang Cui; RuoTong Wang; Shuang Liu; YunLu Zhao; AiJing Liu; BingYan Guo; Chen Jia; ManNa Zhang; Di Hao; Min Shi (Journal of Trace Elements in Medicine and Biology, 2026)

Layer-by-layer assembly of polycationic electrolytes onto cation exchange membranes for enhanced Li+/Mg2+ selectivity: A comparative study of polyethyleneimine and chitosan - Jiadi Ying; Zhen Cui; Xiaoxiang Xi; Junwei Zhu; Tiancun Liu; Song Lu; Qi Shen; Min Guo; Yeqing Wang; Zhen Yang; Yaochun Chen; Minfeng Zeng; et al. (Desalination, 2026)

Transforming waste derived phosphate sources into resources for fluoride immobilization by microbially induced phosphate precipitation - Linlin Cui; Jianxing Sun; Min Huang; Guanzhou Qiu; Zhu Chen; Hongbo Zhao; Li Shen (Bioresource Technology, 2026)

Fracture behavior and constitutive modeling of rock-concrete contact surfaces with different roughness under freeze–thaw cycles - Mengyuan Cui; Taoying Liu; Yeshan Sheng; Min Tang; Wenbin Cai; Longjun Dong (Bulletin of Engineering Geology and the Environment, 2026)

Investigation on the density homogenization and swelling pressure evolution of compacted bentonite with technological voids based on friction analysis - Jing Ma; Yong-gui Chen; Yu-jun Cui; Zhao Sun; Wei-min Ye; Qiong Wang (Bulletin of Engineering Geology and the Environment, 2026)

An improved Hoerl-Kennard-based ridge estimation method for SBAS-InSAR deformation model resolution - Zhiwei Wang; Xiang Wang; Wenzhuang Ding; Fangfang Li; Ying Cui; Tengfei Gao; Wanqiu Li; Min Zhai (International Journal of Remote Sensing, 2026)

Dietary lipid sources modulate low-salinity adaptation in Scylla paramamosain via integrated multi-omics and AQP1/AQP7 regulation - Tiantian Xu; Xiaoyue Li; Yao Deng; Shichao Xie; Wenhao Zhan; Xishuai Cui; Binjie Zhou; Wenli Zhao; Tingting Zhu; Peng Sun; Min Jin; Qicun Zhou (Marine Life Science & Technology, 2026)

Ultra-robust ionic biogel with multiscale structure and multifunctionality for wearable self-powered human-interactive sensing - Yan Liu; Yuxiang Shi; Min Wu; Junlei Wang; Zhenli Cui; Xilong Wang; Chunming Xu; Guozhen Shen; Chunya Wang (Science Bulletin, 2026)

Waste cooking oil biodiesel alters combustion pathways to enhance volatile organic compound emissions and reduce intermediate/semi -volatile organic compounds in agricultural machinery - Fan Zhang; Bo Huang; Junfeng Cui; Yi Wang; Xinyi Wan; Lele Han; Gehui Wang; Yong Han; Yu Wang; Hai Guo; Min Cui (Journal of Hazardous Materials, 2026)

Deconstructing thermal processing of cooperage oak: How oak species, toasting levels and charring levels collectively modulate phenolic profiles - Yongce Huang; Jiamin Gou; Dongsheng Cui; Min Luo; Mengyao Qi; Jin Li; Jisheng Fang; Kunqi Gao; Keji Yu; Changqing Duan; Ying Shi; Yibin Lan (Food Research International, 2026)

Saltiness enhancement of microwave-heated gel matrix focused on Na+ “burst” release behavior and matrix fragmentation during oral processing - Min Zhang; Yaqi Hou; Shuqin Xia; Song Miao; Khizar Hayat; Heping Cui; Jingyang Yu; Shahzad Hussain; Long Zhang (Food Research International, 2026)

Co-exposure to polystyrene microplastics and Di-(2-ethylhexyl) phthalate exacerbates food allergy in mice associated with gut barrier dysfunction - Xuanpei Wang; Wenfeng Liang; Shiyun Chen; Ying Liu; Jiaxin Yu; Jianing Cui; Lin Xu; Min Fang; Zhiyong Gong; Xin Liu; Qing Yang (Food Bioscience, 2026)

A tribo-photonic system based on Ti3C2Tx / hydrogenated amorphous carbon heterostructures for fast and on-demand friction modulation - Ziyi Jiang; Jielin Cui; Min Zhang; Zilin Zhang; Ruiyao Huo; Dandan Wang; Zhe Liu; Jianxi Liu; Peiwei Gong; Weimin Liu (Chemical Engineering Journal, 2026)

Effect of Medicinal Plant Extracts on Water Quality and Microbial Communities in Pond-based Aquaculture Systems - Min Cai; Li Zhou; Xu Zhang; Si Pang; Naxin Cui; Guoyan Zou (Water, Air, & Soil Pollution, 2026)

Correction to: A global synthesis of plant-plant interaction investigations: current knowledge and future directions - Shu Guo; Lizhen Cui; Jiayang Xu; Min Liu; Weining Wang; Anquan Xia; Zhijia Zhang; Youqing Yang; Xingliang Xu; Xiaoyong Cui (Plant and Soil, 2026)

Ankyrin-repeat transmembrane protein WAI-1 confers multiple disease resistance in wheat by activating autoimmunity - Qiuhong Wu; Wenling Li; Yongxing Chen; Huaizhi Zhang; Delin Li; Zhan Li; Fei Xiong; Guanghao Guo; Lei Dong; Xuejia Cui; Jingzhong Xie; Ping Lu; et al. (Science China Life Sciences, 2026)

Divergent assembly mechanisms and network stability of microeukaryotes between water column and sediment in a marginal sea - Feilong Liu; Xiaoli Zhang; Kaiyue Lian; Yi Li; Can Wang; Chuyu Zhang; Honglei Zhang; Bo Wang; Qian Liu; Hui He; Cui Guo; Andrew McMinn; et al. (Marine Pollution Bulletin, 2026)

Light-driven community assembly and functional performance of aeration-free filamentous algae–partial nitrification/anammox granule - Cui-Zhong Chen; Hui-Min Fu; Tong-Xu Li; Xiao-Yu Gao; Qing Hu; Peng Yan; Jin-Song Guo; Xiao-Wei Xu; You-Peng Chen (Water Research, 2026)

Endothelial FAM171A2 is required for maintaining autophagy flux and blood–brain barrier integrity - Si-Da Han; Ning Ding; Jia-hui Huang; Yi-Wei Feng; Kai-Min Wu; Shi-Dong Chen; Qiang Dong; Mei Cui; Ting-ting Wang; Peng Yuan; Jin-Tai Yu (Science Bulletin, 2026)

Epimedium polysaccharide alleviates adenine-induced oligoasthenozoospermia in mice by inhibiting ferroptosis and inflammation through TLR4/NF-κB and SLC7A11/GPX4 axis - Kun-Yang Tang; Wang Ai; Xiao-Cui Jiang; Min Xiao; Yan-Yan Zhou; Xiao-Ming Yu; Shu-Hui Chen; Jing-Ling Zhao (Reproductive Biology, 2026)

One-step Fe-doped cyanobacterial biochar: 4-nitrophenol reduction boosted by synergistic adsorption and redox cycling - Jin-Xing Zheng; Min-Hua Cui; Yan Zhang; Jing Wu; He Liu; Zhi-Yong Zheng (Journal of Environmental Chemical Engineering, 2026)

Zein-based films with γ-cyclodextrin metal organic framework/oregano essential oil for fruit preservation - Zhenbin Liu; Fengbing Yang; Liangbin Hu; Dan Xu; Guoqiang Zhang; Yumei Liao; Min Cui; Hongbo Li; Haizhen Mo (Food Packaging and Shelf Life, 2026)

Hydrothermal-assisted enzymatic pretreatment enhances the cassava residue-based integrated biorefinery: “L-lactic acid – Biogas” production technology - Zixuan Zhou; Jiali Shen; Min Sun; Wei Zeng; Qi Zhang; Yunpu Wang; Yuhuan Liu; Xian Cui; Roger Ruan (Chemical Engineering Journal, 2026)

Enhanced nutrient removal coupled with nitrous oxide mitigation in agricultural eco-ditches: Mechanistic insights into synergistic effects of macrophytes and rice straw - Naxin Cui; Min Cai; Xu Zhang; Si Pang; Guoyan Zou; Yi Zhu; Guifa Chen (Bioresource Technology, 2026)

Early Paleozoic Affiliation between South China Block and Gondwana Revealed by Early Silurian Remagnetization - Min Zhang; Yan Liu; Huafeng Qin; Jinhua Li; Yifei Hou; Bitian Wei; Wei Liu; Linhao Cui; Xingliang Zhang; Chenglong Deng; Yongxin Pan (Journal of Earth Science, 2026)

Construction of a predictive model for postoperative subsyndromal delirium in patients undergoing brain tumor surgery - Min Liu; Dan Duan; Wenjing Sun; Qiang Sun; Wenyao Cui (Acta Neurologica Belgica, 2026)

Brain Serotonin Deficiency Impairs Ovarian Reserve Function via the Hypothalamic-Pituitary-Ovarian Axis - Shuang-Shuang Cui; Zhuo-Nan Yang; Jin Xiao; Jin-Ping Qiao; Yue-Ming Zhang; Ling-Ge Shi; Hui-Ru Cheng; Si-Min Ding; Meng-Yao Wang; Dong-Mei Ji; Tao Zhang; Dan Liang; et al. (Neuroscience Bulletin, 2026)

Modelling and assessing eutrophication and antibiotic risks in a lake system under large‑scale water diversion - Yihan Chen; Shuanggang Hu; Yongjie Yang; Kangping Cui; Chao Zhu; Min Zhang; Youde Zhang; Chen-Xuan Li; Sanjeeb Mohapatra; Peng Jiang; Xuneng Tong (Journal of Hydrology, 2026)

Synergistic hydroxyl and chlorine radicals in contact-electro-catalysis for sustainable PFAS remediation - Jin Zhang; Wei Li; Jinxing Ma; Jianghu Cui; Kuanchang He; Kui Yang; Qian Liu; Min Zhang; Sihao Lv; Faliang Cheng; Defeng Xing (Journal of Hazardous Materials, 2026)

Speciated full-volatility organic compound emissions from typical agriculture machinery in China - Yi Wang; Lele Han; Bo Huang; Xia Xu; Xinyi Wan; Yubao Chen; Yong Han; Min Cui; Yu Wang; Hai Guo; Fan Zhang; Gehui Wang (Journal of Environmental Sciences, 2026)

Meta-analysis of the prevalence, serotype distribution, and antimicrobial susceptibility of Salmonella spp. from eggs in China - Shenfei Zhang; Jiaqi Ma; Tianxi Chen; Mengting Han; Xiaoqi Wang; Min Li; Mei Li; Chenyang Cao; Shenghui Cui; Baowei Yang (International Journal of Food Microbiology, 2026)

Quercetin ameliorates intestinal barrier dysfunction by suppressing the PKCα/MLCK signaling pathway in piglets - Qiuyu Chen; Huadi Mei; Mengyao Fang; Yiyan Cui; Ting Rong; Dun Deng; Zhimei Tian; Min Song; Zhenming Li; Zhichang Liu; Xianyong Ma; Miao Yu (Food Research International, 2026)

Modelling swelling pressure evolution of compacted bentonite considering wetting-induced collapse in a dual-porosity framework - Jing Ma; Yong-gui Chen; Yu-jun Cui; Wei-min Ye; Qiong Wang (Engineering Geology, 2026)

Smart persulfide nanogenerator for acute ischemic stroke treatment by suppressing oxidative stress and inflammation - Zhiyi Min; Wei Lv; Xiang Cao; Hongli Liu; Tianyi Zhuang; Shengnan Li; Zhenwei Ding; Wei Zhao; Yingying Xu; Sijia He; Junli Cui; Xiuzhen Wang; et al. (Chemical Engineering Journal, 2026)

Long-term succession and driving mechanisms of soil microbial communities in reclaimed farmland - Shuangjiao Liu; Xiangyu Min; Junying Li; Wen Song; Zhaoxinyu Liu; Xinju Li; Zhaozhen Cui; Jiale Zhang (CATENA, 2026)

A thermal history-incorporated RWI model for dynamic thermal comfort in transportation-commercial integrated continuous underground spaces - Fangning Shi; Nianping Li; Wenrui Zheng; Mengyu Song; Min Wang; Xinyue Cui (Building and Environment, 2026)

Protopanaxatriol ameliorates diabetic retinopathy by regulating mTOR/G6PD mediated pentose phosphate pathway - Min Guan; Zhenshuang Yuan; Jiaqi Xie; Junbo Cui; Shidan Zang; Jianmei Huang; Can Wang (Journal of Natural Medicines, 2026)

Quantitative assessment of neutrophil chemotactic migration under coexisting intermediate and terminal chemokine gradients in a microfluidic environment: Applications for immune dysfunction and prognostic evaluation in sepsis - Zhuoyi Zhu; Xiao Yang; Yuhang Yao; Ming Fang; Min Shao; Yutao Zha; Jun Zhao; Junsheng Cui; Xiaoou Ren; Ling Zhu; Xuexue Pu; Qiuling Li; et al. (Analytica Chimica Acta, 2026)

Study on the pro-inflammatory mechanism mediated by the RANK-SPP1 axis in macrophage immunomodulation during atherosclerosis - Qiyu Sun; Yanbo Hu; Zeming Sun; Mingyan Shang; Zhengyi Li; Juan Shen; Zhenzhen Cui; Jiaxin Yang; Xiaowen Ma; Min Li (Molecular and Cellular Biochemistry, 2026)

Protective effect of Florfenicol against DSS-induced ulcerative colitis by inhibiting cellular senescence and reducing inflammation via the AMPK signaling pathway - Wei Lian; Qinran Hou; Jinchan Liu; Cui Chen; Zhiwei Wang; Shujia Song; Min Zhou; Fei He; Xiaobo Wang (Toxicology and Applied Pharmacology, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Oral processing and saltiness enhancement mechanism of NaCl-loaded high internal phase emulsions stabilized by OSA-GA complexes - Yaqi Hou; Min Zhang; Shuqin Xia; Khizar Hayat; Heping Cui; Jingyang Yu; Shahzad Hussain (Food Hydrocolloids, 2026)

Experimental investigation of plasma activation on RP-3 cracking and atomization within a circumferential flameholder - Hao Wang; Xinyao Cheng; Di Jin; Huimin Song; Min Jia; Zhibo Zhang; Wei Cui; Jiulun Sun (Chemical Engineering Journal, 2026)

Unique characteristics of Candidatus Nitrosoglobus-driven acidic partial nitritation: critical review and potential applications - Tianyi Zhang; Yanyan Li; Shen Cui; Feng Tian; Min Ye; Yu-You Li (Bioresource Technology, 2026)

Spatiotemporal Variability of China's 800 mm Precipitation Isohyet (1961–2022): Multi-scale Analysis of its Migration and Impact on Hydroclimatic Extremes - Shaowei Ning; Le Chen; Rujian Long; Yuliang Zhou; Yi Cui; Min Zhang; Lichang Xu; Juliang Jin; Thapa bthapa (Atmospheric Research, 2026)

The effect of ammonia stress and the role of c-di-GMP on microalgal bacterial biofilm formation - Min Wang; Zhe Zhang; Hengyuan Chen; Jiayang Cui; Longzao Luo; Shuangshuang Zhu; Huabao Zheng (Algal Research, 2026)

Summer patterns of global lake total suspended solids under climate-hydrology-topography forcing - Min Cui; Mengyuan Zhu; Shun Bi; Boqiang Qin; Qi Guan; Kun Shi (Water Research, 2026)

Diversity loss of soil microbiome stimulates soil carbon emissions - Haibo Pan; Yingyi Fu; Hairong Tu; Yongxing Cui; Beibei Chen; Jiejun Qi; Ziheng Peng; Shi Chen; Chunling Liang; Jiai Liu; Xiaomeng Li; Min Gao; et al. (Soil Biology and Biochemistry, 2026)

Novel metabolic pathway of skatole degradation by Enterococcus hirae IDO5 and its application in swine manure wastewater treatment - Yanzhi Lin; Yanchen Liu; Xianyong Ma; Miao Yu; Yiyan Cui; Guangying Weng; Jing Yu; Ting Rong; Zhichang Liu; Dun Deng; Min Song (Journal of Hazardous Materials, 2026)

County-level emission inventory reveals substantial contributions of small and medium-sized cities to air pollutants and CO2 emissions in China - Zhezhe Shi; Shengyue Li; Qingru Wu; Kaiyun Liu; Yuying Cui; Daiwei Ouyang; Xiaoming Gu; Jia Liu; Xionghui Qiu; Zeqi Li; Hao Wang; Yanning Zhang; et al. (Journal of Environmental Management, 2026)

Development of portable and highly sensitive electrochemical sensor for rapid on-site analysis of levofloxacin residue in pork samples - Xia Cui; Xueqiang Chen; Tianxin Xiao; Xinran Wei; Min Gong; Guanjun Nan; Yunzhe Li; Zhimin Luo; Aiguo Zeng (Food Chemistry, 2026)

Effect of roasting on the chemical profiles of white and black sesame seeds during accelerated storage - Hao Liu; Shu-Guang Gao; Ming-Zhe Sun; Mei-Qi Yang; Huai-Yang Cao; Ke-Xin Zhang; Min-Shu Hong; Rui-Fu Cui; Zhao Qin; Hua-Min Liu; Xue-Ya Wang; Zhi-Jie Li (Food Chemistry, 2026)

Influence of protease type and concentration on protein digestibility, physicochemical and textural properties of extruded high-moisture meat analogues - Grace Cui Fang Ng; Caleb Ong; Alicia Hui Ping Theng; Dayna Shu Min Ong; Chaoyu Dong; Hui Yu Sim; Xin Yi Hua; Felicia Siew Kay Ng; Jie Hong Chiang (Food Hydrocolloids, 2026)

Corrigendum to “Construction of ultrathin PANI nanostructure on cation-exchange membranes for selective lithium extraction” [Desalination, 619 (2026) 119555] - Jiadi Ying; Zhen Cui; Tiancun Liu; Song Lu; Qi Shen; Min Guo; Yeqing Wang; Zhen Yang; Minfeng Zeng; Zhixin Yu; Yuqing Lin (Desalination, 2026)

Pressure- and temperature-dependent real gas transport behavior in nanopores of coal matrix considering gas adsorption - Min Chen; Lin-Yong Cui (Computers and Geotechnics, 2026)

Silicon isotope-based assessments of biogenic and dissolved silica content determination in marine sediments - Die Li; Quanchao Cui; Haiyang Liu; Tzu-Hao Huang; Wei-li Hong; Bangqi Hu; Jing Huang; Min Luo; Weidong Sun; Xiaole Sun (Chemical Geology, 2026)

Evaluating surface fluxes in WRF using eddy-covariance flux measurements in the Western and Eastern U.S. - Fan Wu; Kenneth J. Davis; Li Zhang; Ray G. Anderson; Jason P. Horne; Sarah Goslee; William Munger; Chenxia Cai; Yu Yan Cui; Zhan Zhao; Min Zhong (Agricultural and Forest Meteorology, 2026)

Electrical Structure of the Narusongduo Cryptoexplosive Breccia Deposit, Gangdese Belt, Tibet: Insights from Integrated MT/AMT Data Inversion and Implications for Mineral Exploration - Hui-cui Xin; Zhi-min Xu; Guang Li; Cong Zhou; Zhi-ning Jia (Applied Geophysics, 2026)

Research on the therapeutic effects of recombinant protein PON1Q/R192 intervention on mice poisoned by different categories of organophosphorus compounds - Shuang Zhou; Yue Cui; Lu Li; Pengsi Zhang; Zhe Zhu; Li Yuan; Min Zhao (Toxicology Letters, 2026)

An mRNA microsphere vaccine inhibiting overactivation of DNA sensing mechanisms - Fangke Zhang; Jiancheng Zheng; Fei Wang; Yaping Zhuang; Yunkai Tang; Juan Wang; Yawei Du; Wei-Li Zhao; Min Lu; Weiguo Hu; Wenguo Cui (Science Bulletin, 2026)

Holocene fire dynamics and environmental drivers in Northeastern China: Insights from Lake Woniupaozi Sediments - Weihe Ren; Xia Wang; Min Liu; Qiaoyu Cui; Jing Wu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Artificial sweeteners and antibiotics enhance the dissemination and diversity of antibiotic resistance genes in a soil-water continuum - Chen-Xi Fu; Qian Xiang; Ran Li; Na-Qi Cui; Bin Guo; Dong Zhu; Min Qiao (Journal of Environmental Chemical Engineering, 2026)

Experimental analysis and numerical identification of flame transfer functions at high Reynolds numbers in a premixed swirl combustor - Zhijian Yu; Enguang Liang; Huiying Sang; Yongqing Xu; Guangzhi Cui; Min Zhu (Fuel, 2026)

Sulfur-doped carbon for enhanced flue gas desulfurization: Synergistic experimental and DFT insights - Jun Li; Xiang Wang; Xiao Zhu; Yuke Li; Min Yan; Yang Ma; Ping Cui; Jingcai Chang; Liqiang Zhang; Tao Wang; Chunyuan Ma; Zhanlong Song (Fuel, 2026)

Structural characterization and prebiotic activity of oligosaccharides derived from sesame meal produced by different oil extraction methods - Hui-Fang Duan; Xiao-Rong Chen; Ran Zhang; Yuan-Qing Luo; Chang-Yong Lu; Ke-Qing Liu; Rui-Fu Cui; Run-Yang Zhang; Hua-Min Liu (Food Research International, 2026)

Enhancing pepper peeling efficiency and product quality based on steam explosion-induced cell wall disruption and enzymatic browning inhibition - Jingyi Jiang; Min Zhang; Shuqin Xia; Wenjian Yang; Khizar Hayat; Shahzad Hussain; Heping Cui; Jingyang Yu (Food Bioscience, 2026)

Construction of ultrathin PANI nanostructure on cation-exchange membranes for selective lithium extraction - Jiadi Ying; Zhen Cui; Tiancun Liu; Song Lu; Qi Shen; Min Guo; Yeqing Wang; Zhen Yang; Minfeng Zeng; Zhixin Yu; Yuqing Lin (Desalination, 2026)

Natural protein-based robust and multifunctional biogels engineered via silk nanofibril reinforcement and swelling-assisted solvent enhancement - Min Wu; Yan Liu; Xinyuan Song; Zhenli Cui; Junlei Wang; Zhengxuan Li; Xilong Wang; Chunming Xu; Chunya Wang (Chemical Engineering Journal, 2026)

Transforming Camellia oleifera meal into feedstuff: Enhancing value through detoxification and fermentation - Yiyan Cui; Yuheng Lei; Zhenming Li; Zhichang Liu; Min Song; Dun Deng; Zhimei Tian; Ting Rong; Pan Yang; Xianyong Ma; Miao Yu (Bioresource Technology, 2026)

Vitamin D3 enhances physiological performance in Portunus trituberculatus: Growth, lipid / cholesterol metabolism, and immunity - Tingting Zhu; Yuhui Cui; Haiqing Cao; Yao Deng; Shichao Xie; Wenli Zhao; Peng Sun; Min Jin; Qicun Zhou (Aquaculture, 2026)

ASFV activates STAT3 to induce proviral M2 macrophage polarization - Yanru Chen; Haowei Chen; Weijia Zhang; Penghao Lv; Zhichao Wang; Hanlin Liao; Kaiyue Wei; Qigai He; Min Cui (Veterinary Microbiology, 2026)

Corrigendum to “ASFV activates STAT3 to induce proviral M2 macrophage polarization” [Vet. Microbiol. 311 (2025) 110733] - Yanru Chen; Haowei Chen; Weijia Zhang; Penghao Lv; Zhichao Wang; Hanlin Liao; Kaiyue Wei; Qigai He; Min Cui (Veterinary Microbiology, 2026)

Nobiletin alleviates heat stress-induced meiotic arrest via restoring CDK1 and MAPK activity in porcine oocytes - Jae-Min Sim; Song-Hee Lee; Cheng-Lin Zhan; Qin-Yue Lu; Gyu-Hyun Lee; Hyeon-Ji Song; Yu-Jin Jo; Ji-Su Kim; Eui-Bae Jeung; Xiang-Shun Cui (Theriogenology, 2026)

Novel analytical approach of vertical vibration of closely spaced pipe pile groups considering soil plug and scattering effects - Kun Meng; Mingchen Zhong; Chunyi Cui; Xiubing Li; Zhenguo Lu; Bo Min (Soil Dynamics and Earthquake Engineering, 2026)

Curcumin-mediated photodynamic action disturbs TOM70-depedent MIC60 import to damage mitonchondria against breast cancer - Xiang-Yi Zhao; Min Yan; Liang Zheng; Chang-Long Gou; Qi Huang; Liu-Gen Li; Xin-Ran Yu; Jing-Yu Lu; Cui Hu; Si-Han Zhang; Cunqing Kong; Fan Leng; et al. (Journal of Photochemistry and Photobiology B: Biology, 2026)

Characteristics and genomics study of Salmonella isolates in retail chicken in Shaanxi, China: Focus on comparative genomics analysis of S. Kentucky and S. enteritidis isolates from Shaanxi with those from elsewhere in China - Jiaqi Ma; Xiaobao Bai; Siyue Wang; Yinuo Yang; Mei Li; Min Li; Wei Zhou; Shenghui Cui; Baowei Yang (International Journal of Food Microbiology, 2026)

A new model for relative gas permeability considering the dynamics of pore-scale water distribution - Lin-Yong Cui; Min Chen; Shakil A. Masum; Yuan-Hao Wei (Gas Science and Engineering, 2026)

Spatiotemporal characteristics and source apportionment of intermediate volatility organic compounds in the riverside industrial parks - Xiaoxiao Hou; Yingjun Chen; Wanting Zhuang; Fuqiang Shi; Yishun Zhang; Caiqing Yan; Min Cui (Environmental Pollution, 2026)

Effective conversion of lignocellulose to fermentable sugars using engineered Clostridium thermocellum with co-enhanced cellulolytic and xylanolytic activities - Xiaoqing Wang; Min Xiao; Chao Chen; Kuan Qi; Chaoyang Chen; Qiu Cui; Akihiko Kosugi; Ya-Jun Liu; Yingang Feng (Bioresource Technology, 2026)

Salidroside-Pretreated Small Extracellular Vesicles Derived from Human Umbilical Cord Mesenchymal Stem Cells Promote Blood-Spinal Cord Barrier Repair After Spinal Cord Injury in Mice - Juan Wang; Qian Zhu; Peiran Chan; Ziyan Zhu; Mingming Zheng; Zhiyuan Mao; Mufeng Gu; Zijian Ren; Min Cui; Jie Liu; Yongjie Zhang (Molecular Neurobiology, 2026)

Plant patch size, not number, determines vegetation recovery in mildly degraded Bangor alpine steppes under grazing exclusion - Haishan Niu; Min Liu; Jing Zhang; Qian Kong; Runfu Li; Chuanlu Zhu; Xiaoyong Cui; Shiping Wang; Yanfen Wang (Journal of Mountain Science, 2026)

ASFV activates STAT3 to induce proviral M2 macrophage polarization - Yanru Chen; Haowei Chen; Weijia Zhang; Penghao Lv; Zhichao Wang; Hanlin Liao; Kaiyue Wei; Qigai He; Min Cui (Veterinary Microbiology, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Rapid change in structural stability of tidal flats in response to large-scale eradication of Spartina alterniflora: evidence from dense time-series PlanetScope satellite imagery - Jiaru Yang; Liyue Cui; Zhaojun Zhuo; Jinyan Tian; Peng Li; Yukui Min; Yinghai Ke (Journal of Environmental Management, 2025)

Comparative genomic analysis of ciprofloxacin-resistant Escherichia coli from retail chicken in Shaanxi, China and global sources - Jiali Sun; Mengting Han; Qiuping Yang; Mei Li; Siyue Wang; Min Li; Wei Zhou; Shenghui Cui; Baowei Yang (Food Research International, 2025)

Food defect detection technologies based on deep learning and prospects in detection of unsound wheat kernels - Rong Wang; Zhiyao Zhao; Ying Sun; Yongbiao Ni; Jin Ye; Min Zhang; Liwen Cui (Food Chemistry, 2025)

Dual-signal ratiometric electrochemical aptasensor based on COFs-derived Fe/N-doped porous carbon and methylene blue-enriched COFs for sensitive and accurate detection of kanamycin - Haiyan Zhao; Yunzhi Zhao; Shanshan Li; Meiya Zhang; Na Li; Min Cui; Cong Zhang (Food Chemistry, 2025)

Characterization of inhomogeneous Na+ distribution in myofibrillar protein-based emulsion gels during microwave heating and mechanistic insights into migration attenuation - Min Zhang; Yaqi Hou; Shuqin Xia; Khizar Hayat; Heping Cui; Jingyang Yu; Shahzad Hussain (Food Chemistry, 2025)

An innovative intimately coupled photocatalysis and biodegradation system for simultaneous removal of emerging contaminants and nitrate - Shi-Ming Niu; Thangavel Sangeetha; Xue-Dong Zhang; Wei-Mon Yan; Peng-Fei Li; Jiří Ryšavý; Jakub Čespiva; Min-Hua Cui (Chemical Engineering Journal, 2025)

Electronic behavior and state changes drive tungsten oxide for ultra-low energy consumption dual-band electrochromic smart windows - Junkai Wang; Lixuan Cui; Mei Zhang; Min Guo (Chemical Engineering Journal, 2025)

Multiomics integration unveils rapeseed adaptative responses to potassium deprivation: a synergy of morpho-physiological, transcriptomic, and metabolic reprogramming - Rui Cui; Si-si Sun; Min-nan Pei; Ying Liu; Yu-shan Xiao; Ying-na Feng; Ting Zhou; Ying-peng Hua (Plant and Soil, 2025)

The NLRP3 inflammasome: a pivotal orchestrator of multisystem diseases—from molecular mechanisms to therapeutic innovation - Shu-yan Xiao; Ya-hui Lv; Yin-min Ji; Yi Dong; Mei-cen Liu; Tao Li; Xiao-ran Cui; Yi Hu (Molecular Biology Reports, 2025)

Peripheral inflammation in spinocerebellar ataxia type 3: associations with genetic and clinical manifestations - Jia-Yi Zhang; Qiu-Ni Su; Han Lin; Wei Lin; Mao-Lin Cui; Zhuo-Ying Huang; Bei-Ning Ye; Ying-Xin Ye; Yi-Lin Jia; Qing-Ying Zhu; Zhi-Han Li; Min-Ting Lin; et al. (Inflammation Research, 2025)

Unravel the impact of land use type on taxonomic and functional structure of microbial communities in coastal urban and rural areas, China - Min Yang; Wenbo Cui; Yu Tao; Ying Chen; Zhen Liu; Taotao Zeng; Ai-jie Wang (Science of The Total Environment, 2025)

Nonlinear trajectory tracking control of UVMS with compositing fuzzy disturbance observer and robust state-dependent Riccati equation - Qirong Tang; Yuanjie Di; Tong Li; Yuanzhe Cui; Zongwu Xie; Linlin Feng; Min Yu (Ocean Engineering, 2025)

Dynamic model for charging tight gas reservoirs: A case study from the Xujiahe Formation in the Sichuan Basin, China - Haoming Shao; Min Wang; Junfeng Cui; Hui Jin; Dianshi Xiao; Yidong Jia; Wei Li; Xiaodie Guan; Chen Zhao; Tao Zhang (Marine and Petroleum Geology, 2025)

Development of MgFe layered double hydroxide-modified biochar for efficient nitrate adsorption and potential slow-release fertilizer: Mechanism and artificial neural network modeling - Xing Gao; Menglu Xu; Ya'nan Shi; Qiuxia Meng; Jiaxing Zhang; Shihao Cui; Zhiping Yang; Min Yan (Journal of Environmental Management, 2025)

Rapid formation of acetaldehyde and its influence on ozone formation in a petrochemical industrialized region - Can Cui; Yujiao Zhu; Xiaoyu Yan; Xin Zhang; Min Zhao; Jiangshan Mu; Xuelian Zhong; Jinghao Tang; Yanqiu Nie; Cong An; Wanghui Chu; Yue Sun; et al. (Journal of Environmental Sciences, 2025)

Corrigendum to “Analysis of the effects of hydroxyl radicals on the volatile flavor composition and lipid profile of sheep meat based on HS-SPME–GC–MS and UPLC–MS/MS studies” [Food Chem. 484 (2025) 144161] - Zhihao Yang; Zihao Cui; Min Zhang; Lina Sun; Lihua Zhao; Lin Su; Ye Jin (Food Chemistry, 2025)

Discovery of two IgM subclasses in Nile tilapia (Oreochromis niloticus) provides insights into IgM evolution in teleost fish - Yuan-Yuan Yao; Chen-Xi Pan; Yu-Dong Hao; Xun Liu; Dan-Dan Chen; Zheng-Wei Cui; Xiang-Yang Zhang; Jian-Min Ye; Yong-An Zhang; Xu-Jie Zhang (Fish & Shellfish Immunology, 2025)

Study on the residual dynamics of diazepam in freshwater fish of Zhejiang, China and its implications for human health - Jing Cui; Jing Wang; Shihuan Zhong; Min Hong; Chenze Lu; Jiehong Fang; Han Jiang (Environmental Pollution, 2025)

A hydrogen-based indigenous bacterial and algal biofilm system for enhanced nutrient removal in oxidation ponds - Si Pang; Lin Yang; Min Cai; Xu Zhang; Naxin Cui; Li Zhou; Guoyan Zou (Chemical Engineering Journal, 2025)

Size-segregated emission characteristics and associated toxicity of polycyclic aromatic compounds from agricultural machinery - Yishun Zhang; Zeyu Liu; Yingjun Chen; Yanli Feng; Min Cui; Xinxin Feng; Yu Peng; Junjie Cai; Tian Chen (Journal of Hazardous Materials, 2025)

Core–shell structured Co3O4@CoMnFe layered composite metal oxides derived from ZIF-67 for C3H6-SCR of NOx: Trimetallic synergy and reaction mechanism - Min Cui; Jacob Senior Atta Owusu; Mingyu Su; Yuhao Wang; Huqin Zheng; Sameer Shahid; Wenyi Deng; Nini Wen; Bingtao Zhao; Yaxin Su (Journal of Environmental Chemical Engineering, 2025)

Modulating the aggregation pattern of interface myofibrillar protein in emulsion gel to enhance Na+ inhomogeneous distribution during microwave heating: The effects of hydrophobic interactions and disulfide bonding - Min Zhang; Yaqi Hou; Shuqin Xia; Khizar Hayat; Di Hua; Heping Cui; Jingyang Yu; Shahzad Hussain (Food Research International, 2025)

Rapid and sensitive in-situ detection of malachite green and crystal violet in aquaculture using flexible SERS substrates via instant self-assembly - Yupeng Sun; Kaihui Zhou; Yuxin Wang; Ye Lin; Weiran Wang; Xue Xiong; Xiangru Zhao; Huinan Cui; Min Liang; Qiao Wang; Shengnan Yang; Li Li (Food Chemistry, 2025)

Extraction of 4’-hydroxyacetophenone and caudatin from Cynanchum auriculatum flowers using enzymolysis-green surfactant assisted homogenate ultrasound method - Guoqiang Cui; Yue Wen; Leyi Yang; Xinyu Liu; Xiaodong Wu; Min Shen; Yijun Kang; Li Yao (Food Chemistry, 2025)

Impact of natural rainfall and solidifying agents on solidified river sludge: Environmental characteristics - Mengyi Wei; Junjie Shen; Suqing Wu; Xiangyong Zheng; Min Zhao; Sihong Liu; Liujiang Wang; Chunzhen Fan; Noriyuki Yoshida; Hongbin Cui (Environmental Pollution, 2025)

A hydraulic conductivity model for unsaturated bentonite-based materials incorporating surface enhanced vapour diffusion - Zhang Rong LIU; Yu Jun CUI; Wei Min YE; Yong Gui CHEN; Qiong WANG (Computers and Geotechnics, 2025)

Laser-engineered carbon hierarchies with multiscale attenuation mechanisms for ultrabroadband microwave absorption - Zhao Li; Nian Li; Yanping Song; Jun Kang; Na Hong; Shuai Han; Shihao Wang; Zhiyuan Yang; Shudong Zhang; Cui Liu; Min Xi; Congfa Song; et al. (Chemical Engineering Journal, 2025)

Electricity-driven microbial production of medium-chain fatty acids from biowaste: From mechanisms to applications - Jiayu Gu; Zihan Cui; Yang Wu; Jing Sun; Xiong Zheng; Min Long; Yinguang Chen (Chemical Engineering Journal, 2025)

In situ tracking of MOF structural reconstruction toward a Cu/Bi/MOF composite electrocatalyst for efficient CO2-to-formate conversion - Yutao Cao; Yongjian Zhao; Tingting Tang; Shuo Cui; Min Li; Xianhu Sun; Wei Cui; Hong Zhao (Chemical Engineering Journal, 2025)

Low temperature efficient adsorption of toxic gas phosphine over CuCe co-doped nitrogen-rich biochar in an anaerobic environment - Ruoxu Liu; Min Shao; Junjie Ma; Fang Wang; Rui Cao; Zibin Pan; Ping Ning; Jiayu Feng; Shuo Cui; Lijuan Jia (Chemical Engineering Journal, 2025)

Dynamically cross-linked polyethylene vitrimers: An alternative approach to high-performance high-voltage cable insulation - Zhuolin Zhang; Kangning Wu; Haoran Sui; Ge Zhao; Youshen Wu; Chenhui Cui; Peng Zhao; Kai Yang; Lisheng Zhong; Baoquan Wan; Shengtao Li; Zhi-Min Dang; et al. (Chemical Engineering Journal, 2025)

circRNA_Atp8a1 Promotes Glycolytic Reprogramming in Damage of Intestinal Mucosal Barrier by Upregulating IGF2 through miR-200b-3p - Wen Qiang Yuan; Yun Han Yang; Peng Shuang Shi; Shi Min Wu; Fang Yan; De Jun Cui (Tissue Engineering and Regenerative Medicine, 2025)

Investigation of an Accelerated Deterioration Method for Subsea Tunnel RC Linings via Electromigration and Its Associated Test Parameters - Jiguo Liu; Qinglong Cui; Shengbin Zhang; Xin Li; Longhai Wei; Huimin Gong; Yiguo Xue; Min Han (Journal of Marine Science and Engineering, 2025)
Appropriate accelerated deterioration methods are crucial for studying the deterioration behavior of reinforced concrete linings in subsea tunnels. To investigate the deterioration mechanisms of reinforced concrete (RC) structures in marine environments, this study employed the electromigration method to simulate accelerated chloride-induced corrosion of steel reinforcement. The results demonstrate that under a direct current (DC) electric field, chloride ions migrate directionally and accumulate on the side of the steel facing the chloride source, successfully inducing non-uniform corrosion features that closely resemble those in natural environments. The side facing chloride ingress exhibited severe corrosion and significant cross-sectional loss, while the shielded side remained largely intact. The experimental process clearly reveals that the applied electric field does not directly initiate corrosion of the steel reinforcement before chloride ions migrate to its surface. Furthermore, analysis of experimental parameters showed that symmetrical perforations on electrode plates are crucial for a uniform electric field, while perforation ratio and electrode–specimen distance have a minor influence. The average chloride penetration depths corresponding to electrode plate perforation areas of 5.5%, 15%, 25.5%, and 38.1% were measured as 1.63 cm, 1.67 cm, 1.57 cm, and 1.57 cm, respectively. This research confirms electromigration as an efficient and reliable technique for accelerated corrosion testing, providing a significant theoretical basis for assessing and predicting the long-term durability of marine engineering structures.

Preparation and characterization of PA6/PANI/α-Fe2O3-x composite nanofiber membranes for the removal of tetracycline from wastewater - Wenlong Wang; Min Li; Junhui Si; Qianting Wang; Sijie Qiu; Yiwen Xu; Xiaolong Liu; Zhixiang Cui (Journal of Water Process Engineering, 2025)

Investigation of high-gain mechanisms for nonlinear flame responses in a swirled premixed combustor - Zhijian Yu; Meng Ji; Yongqing Xu; Guangzhi Cui; Min Zhu (Fuel, 2025)

Antibacterial mechanism and computer simulation analysis of a novel antimicrobial peptide inducing membrane disintegration in Gram-positive bacteria - Meili Cui; Haoyan Sun; Xia Liu; Zirong Huang; Zhenhua Su; Yu Zheng; Yanbing Shen; Min Wang (Food Bioscience, 2025)

Enhancing ion dynamics and ion-enrichment through electronegative azolate framework for zinc anode stabilization - Wenbo Li; Shun Wang; Xuehan Hou; Peiyu Cui; Wentao Li; Wenhuan Huang; Xiaoyu Zhang; Min Jia; Yuee Xie; Yuanping Chen (Chemical Engineering Journal, 2025)

Alleviating moxifloxacin-induced biological inhibition in ethanol and Cl− coexisted wastewater: Why UV/H2O2 is better than Fenton - Yingying Zhang; Min Yang; Wenbo Cui; Lin-Ji Xu; Depeng Zhang; Yu Tao; Jing-Long Han; Aijie Wang (Chemical Engineering Journal, 2025)

VrMYB90 negatively regulates proanthocyanidin biosynthesis by repressing VrANR in mung bean (Vigna radiata L.) - Changjian Bao; Mengyang Niu; Ze Liu; Yukun Wu; Beier Cao; Min Zhou; Xingxing Yuan; Li Jia; Jin Cui; Zhenguo Shen; Nana Su (Planta, 2025)

A highly stable and recyclable palladium nanocatalyst supported on a core-shell structure for Suzuki cross-coupling - Min Li; Xueyan Hu; Jiang Gao; Yongxue Guo; Cui Wang (Sustainable Chemistry and Pharmacy, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Analysis of the effects of hydroxyl radicals on the volatile flavor composition and lipid profile of sheep meat based on HS-SPME–GC–MS and UPLC–MS/MS studies - Zhihao Yang; Zihao Cui; Min Zhang; Lina Sun; Lihua Zhao; Lin Su; Ye Jin (Food Chemistry, 2025)

Characterization and enhanced saltiness retention time of sodium chloride-containing high internal phase Pickering emulsions stabilized by OSA starch and gum Arabic - Yaqi Hou; Min Zhang; Shuqin Xia; Khizar Hayat; Heping Cui; Jingyang Yu (Food Hydrocolloids, 2025)

Disentangling and hedging global warming risk: A machine learning approach - Shusheng Ding; Tianxiang Cui; Anna Min Du; John W. Goodell; Nanjiang Du (Environmental Impact Assessment Review, 2025)

A global synthesis of plant-plant interaction investigations: current knowledge and future directions - Shu Guo; Lizhen Cui; Jiayang Xu; Min Liu; Weining Wang; Anquan Xia; Zhijia Zhang; Youqing Yang; Xingliang Xu; Xiaoyong Cui (Plant and Soil, 2025)

Correction: IL-32/NFκB/miR-205 loop sustains the high expression of IL-32 and enhances the motility of cervical cancer cells - Jianbing Liu; Kai Yang; Xiaoyu Lin; Jing Xu; Xiaohua Cui; Jianqing Hao; Wei Wang; Wenhao Wang; Li Li; Min Hao (Human Cell, 2025)

Source of dietary iron and zinc affects meat quality by altering muscular fatty acid profile, flavor substances, and metabolomics in finishing pigs - Zhimei Tian; Miao Yu; Yiyan Cui; Dun Deng; Min Song; Zhichang Liu; Ting Rong; Zhenming Li; Xianyong Ma (Meat Science, 2025)

Glass transition features of frozen dough regulated by lentinan molecular weight and their correlation with dough structural and rheological properties - Shunqin Li; Wenjie Sui; Jiayi Cui; Ziyi Wan; Jingxin Zhang; Tao Wu; Dan Liu; Min Zhang (Food Hydrocolloids, 2025)

Hydro-mechanical behavior of compacted GMZ bentonite blocks with a vertical technological void - Jing Ma; Yong-gui Chen; Yu-jun Cui; Wei-min Ye; Qiong Wang (Engineering Geology, 2025)

A soil–water retention model with differentiated adsorptive and capillary regimes - Zhang-Rong Liu; Wei-Min Ye; Yu-Jun Cui; He-Hua Zhu; Yong-Gui Chen; Qiong Wang (Computers and Geotechnics, 2025)

Pressure-tailored phase engineering for giant enhancement of photoelectric effect in the 2D-layered semiconductor CrPS4 - Junming Feng; Mengyao Qi; Hao Song; Meiyan Ye; Marcin Runowski; Ziyang Hu; Like Huang; Min Lian; Xingbin Zhao; Yaqian Dan; Shuailing Ma; Tian Cui (Chemical Engineering Journal, 2025)

Collagen targeting BMSCs-derived extracellular vesicles coupled with decellularized tendon scaffold for anterior cruciate ligament reconstruction - Jie Wang; Jing Cui; Liang-Ju Ning; Yan-Jing Zhang; Fei Xing; Lei-Lei Zhao; Hui-Min Liu; Xuan Li; Min Zhu; Jing-Cong Luo; Zhou Xiang; Ting-Wu Qin (Chemical Engineering Journal, 2025)

Ecological Impacts of Sunflowers on Soil Microbial Communities: Insights from Full-Length 16S rRNA Sequencing - Seong-Jun Chun; Yingshun Cui; Jihoon Kim; Jun-Woo Lee; Sung Min Han; Kyong-Hee Nam (Current Microbiology, 2025)

Effects of Exposure to Chromium During Pregnancy on Fetal Growth and a Possible Sex-Dependent Response: Results of Cross-sectional Study - Yuanyuan Fang; Qingmei Shen; Kuanying Yang; Meng Wang; Wenxin Wang; Jia Lv; Mingliang Fang; Min Nian; Yichao Huang; Zhaohui Huang; Liping Cui; Dexiang Xu; et al. (Biological Trace Element Research, 2025)

Analysis of the potential resource, environmental and economic impacts of EU battery and waste battery regulations on China's lithium-ion battery industry - Min Liu; Wei Liu; Mingyue Zhang; Xin Pan; Qian Zhang; Mingxue Zhang; Tengyun Ma; Zhaojie Cui (Resources, Conservation and Recycling, 2025)

A possible northward subduction in the southwestern Yangtze block during the Rodinia assembly: New constraints from three-dimensional magnetotelluric imaging - Shibin Xia; Qiao Wang; Jian Yang; Xiaozhuang Cui; Gang Min; Gang Zhang; Guozhong Liao; Dewei Li; Guangming Ren (Precambrian Research, 2025)

Effect of the construction of α-Al2O3 interface layer on the interfacial properties of Alumina fiber/Alumina-silica composites - Fengyong Guo; Yining Zhang; Fengdan Cui; Shaokai Wang; Qidan Wang; Zilan He; Jian Zhang; Yizhuo Gu; Min Li (Next Research, 2025)

Analysis of seepage and hysteresis effect mechanism of unsaturated loess based on resistivity test - Bo Cui; Tianfeng Gu; Jiading Wang; Jiacheng Li; Nannan Fan; Xin Li; Zhijie Song; Min Hao (Journal of Hydrology, 2025)

Research on dust suppression technology and structural optimization of cylindrical vortex air curtains based on artificial tornado mechanism - Yanbin Yu; Lianxin Fang; Min Xiang; Wenting Cui; Sai Li; Kezhi Song (Journal of Environmental Chemical Engineering, 2025)

Modelling and prediction of toluene adsorption saturation basing on characteristic values of activated carbons - Quanli Ke; Yedong Xiong; Mei Lu; Kangkang Huang; Yiting Guo; Jiong Min; Chuanmin Jin; Zhenyu Gu; Guokai Cui; Xiaole Weng; Bingzhi Yi; Hanfeng Lu (Journal of Environmental Sciences, 2025)

Tenecteplase Plus Butyphthalide for Stroke Within 4.5–6 Hours of Onset (EXIT-BT): a Phase 2 Study - Hui-Sheng Chen; Ming-Rui Chen; Yu Cui; Xin-Yu Shen; Hong Zhang; Jiang Lu; Li-Wei Zhao; Ying-Jie Duan; Jing Li; Ya-Mei Wang; Lian-Qiu Min; Li-Hong Zhao; et al. (Translational Stroke Research, 2025)

The molecular mechanism by which CTSB degrades FPN to disrupt macrophage iron homeostasis and promote the progression of atherosclerosis - Quanli Qiu; Qiyu Sun; Jiaxin Yang; Qingxin Yuan; Ping Wang; Qingwei Liu; Zhenzhen Cui; Xiaowen Ma; Min Li (Molecular and Cellular Biochemistry, 2025)

Roseateles cavernae sp. nov., a Bacterium Isolated from Freshwater of the Old Huanglong Cave in Yunnan Province, South-West China - Yu-Man Zhang; Qian Jiang; Mu-Yao Li; Qing-Yu Miao; Yi-Qing Li; Min Yin; Cui-Ping Miao; Shu-Kun Tang (Current Microbiology, 2025)

PSG-Crossformer: a hybrid model for long-term dissolved oxygen prediction in aquaculture - Min He; Meng Cui; Qinyue Zheng; Longqin Xu; Shuangyin Liu (Aquaculture International, 2025)

Anthracnose caused by Colletotrichum siamense on rambutan in China - Gengxin Chen; Jinhua Sun; Jiaming Cui; Yu Wang; Yajun Ran; Deqiang Gong; Yi Yang; Meijiao Hu; Min Li (Crop Protection, 2025)

Ca2 + substitution synergises zeolite physisorption accelerated Na+ substitution to improve saline soils - Haitao Liu; Min Jin; Chunhui Li; Jiayu Wang; Haiyan Wang; Weidong Xie; Haixing Cui; Yong Li; Zhenlin Wang (Soil and Tillage Research, 2025)

Iron-based nanomaterials enhanced immobilization of Cd2+ and Pb2+ in mine wastewater and soil by Clostridium sulfidigenes HY-1 - Li Zhang; Qi Min; Zheng Wu; Chenhui Cui; Youbin Si (Science of The Total Environment, 2025)

Phosphate-coupled high-carbon ferromanganese particles synergistically regulate co-composting of seaweed and corn starch residue: Improving nitrogen cycling and accelerating humification - Yinjie Cui; Dawei Feng; Min Xie; Yuxue Zhang; Derui Wang (Journal of Environmental Management, 2025)

Emergence of multidrug resistant Escherichia coli coharboring fosA3 and ESBL genes from retail ducks along slaughter line - Jialan Chen; Ruyi Kuang; Haotian Liu; Lei Yang; Jiarui Li; Junlin Li; Jing Xia; Yong Huang; Min Cui; Likou Zou; Xinfeng Han (International Journal of Food Microbiology, 2025)

Human Umbilical Cord Mesenchymal Stem Cells for the Treatment of Systemic Lupus Erythematosus via Glucose Metabolism of CD4+T Cells - Meng Ding; Lu Jin; Shaoxin Cui; Lin Yang; Jingjing He; Xiaoping Wang; Fei Chang; Qun Wang; Xue Liu; Hongtao Jin; Shuran Song; Min Shi; et al. (Stem Cell Reviews and Reports, 2025)

Advances in pharmacological activity and drug delivery systems of vinca alkaloids - Quanying Zhou; Min Jin; Yulong Cui; Siqi Jiang; Peizhao Shang; Lingjun Li (Natural Product Research, 2025)

Comparative study of the characteristics of the energy flow and food web structure in the Laizhou Bay ecosystem based on the Ecopath and LIM-MCMC models - Cui Wenhui; Xu Bingqing; Dong Xiuqiang; Yang Jisong; Li Min; Zhang Depu; Li Shengfu; Lv Zhenbo; Li Fan; Ren Zhonghua (Frontiers in Marine Science, 2025)
This study compared the characteristics of energy flow and food web structure in the Laizhou Bay ecosystem using the Ecopath model and linear inverse models enhanced by Monte Carlo methods coupled with a Markov Chain (LIM-MCMC), respectively, based on survey data collected in May, August, and November 2022. The ecosystem was divided into 22 functional groups with trophic levels ranging from 1.00 to 3.48 and a large proportion of predator groups. The Ecopath model estimated an overall energy transfer efficiency of 5.34%, with the detrital food chain exhibiting significantly higher energy transfer efficiency (6.73%) than the grazing food chain (5.31%). Energy flow paths in the LIM-MCMC model were classified into four primary routes, predominantly driven by respiration and the inflow of detritus at lower trophic levels, which accounted for 79.9% of the total energy flow in group a. The Ecopath model provided a connectance index of 0.30, a system omnivory index of 0.33, Finn’s mean path length of 2.46, and Finn’s cycle index of 8.18%, whereas the LIM-MCMC model produced an average path length of 2.78. Both models indicated a shorter food chain and low complexity of the food web. Total system throughput (TST) was estimated at 10,086.1 (Ecopath) and 10,968.0 t·km -2 a -1 (LIM-MCMC), with total respiration and total flows into detritus accounting for 41.2% and 51.1% of TST, respectively. The total primary production to total respiration ratios were 1.40 (Ecopath) and 0.86 (LIM-MCMC). Despite consistent ecosystem parameters across both models—total consumption (4,407.7 t·km -2 a -1 ), total primary production (3,606.4 t·km -2 a -1 ), and total biomas (151.0 t·km -2 a -1 )—the Ecopath model suggested a relatively mature ecosystem, whereas the LIM-MCMC model indicated that this ecosystem was in an unstable developmental stage with low energy utilisation efficiency of primary productivity

Metabolic Reprogramming in Spinal Cord Injury and Analysis of Potential Therapeutic Targets - Xiangjun Chen; Juan Wang; Peiran Chan; Qian Zhu; Ziyan Zhu; Mingming Zheng; Xinyi Chen; Haozhen Wu; Min Cui; Yongjie Zhang (Journal of Molecular Neuroscience, 2025)

Research Progress of Fuel Cell Technology in Marine Applications: A Review - Zheng Zhang; Xiangxiang Zheng; Daan Cui; Min Yang; Mojie Cheng; Yulong Ji (Journal of Marine Science and Engineering, 2025)
With the increasing severity of global environmental issues and the pressure from the strict pollutant emission regulations proposed by the International Maritime Organization (IMO), the shipping industry is seeking new types of marine power systems that can replace traditional propulsion systems. Marine fuel cells, as an emerging energy technology, only emit water vapor or a small amount of carbon dioxide during operation, and have received widespread attention in recent years. However, research on their application in the shipping industry is relatively limited. Therefore, this paper collects relevant reports and literature on the use of fuel cells on ships over the past few decades, and conducts a thorough study of typical fuel cell-powered vessels. It summarizes and proposes current design schemes and optimization measures for marine fuel cell power systems, providing directions for further improving battery performance, reducing carbon emissions, and minimizing environmental pollution. Additionally, this paper compares and analyzes marine fuel cells with those used in automotive, aviation, and locomotive applications, offering insights and guidance for the development of marine fuel cells. Although hydrogen fuel cell technology has made significant progress in recent years, issues still exist regarding hydrogen production, storage, and related safety and standardization concerns. In terms of comprehensive performance and economics, it still cannot effectively compete with traditional internal combustion engines. However, with the continued rapid development of fuel cell technology, marine fuel cells are expected to become a key driver for promoting green shipping and achieving carbon neutrality goals.

The recyclable non-metal acid-catalyzed ammination of benzyl alcohol - Mengyan Zhong; Min Li; Guoliang Chen; Cui Wang; Xuefei Bao (Sustainable Chemistry and Pharmacy, 2025)

Seasonal and spatial distribution of AmphiOctopus fangsiao and Octopus variabilis in the southern Yellow and East China Seas: Fisheries management implications based on climate scenario predictions - Linlin Yang; Min Xu; Zunlei Liu; Yi Zhang; Yan Cui; Shengfa Li (Regional Studies in Marine Science, 2025)

Preparation of a La(OH)CO3/NiAl-LDHs interface junction photoinitiated activator: Excellent photoinitiated activity and the photoactive pathway for destruction of phenol in wastewater - Hui-Min Zhao; Wei-Peng Jia; Rui Dang; Xiang-Rong Ma; Yang Ma; Shuang-Yu Li; Xin Han; Nai-Cai Xu; Yu-Hong Kang; Yong Gao; Hua-Rui Hao; Rui Bai; et al. (Journal of Environmental Chemical Engineering, 2025)

A review on the genus Melodinus: traditional uses, phytochemical diversity and pharmacological activities of indole alkaloids - Si-Fan Teng; Fang-Ru Li; Qi-Min Cui; Afsar Khan; Ting He; Xiao-Dong Luo; Ya-Ping Liu; Gui-Guang Cheng (Phytochemistry Reviews, 2025)

Analysis of Codon Usage Patterns in a Rare Palmitoleic Acid Production Oleaginous Yeast, Scheffersomyces segobiensis - Lili Zhang; Wenxing Cui; Dandan Tang; Haohong Lin; Weiliang Dong; Xiujuan Qian; Min Jiang (Current Microbiology, 2025)

Seasonal spatial distribution patterns of AmphiOctopus ovulum in the East China Sea: current status future projections under various climate change scenarios - Linlin Yang; Min Xu; Yan Cui; Shuhao Liu (Frontiers in Marine Science, 2025)
Currently, there is also little up to date information on the the current population status and life history traits of AmphiOctopus ovulum , a very often seen cephalopod species in the East China Sea. It is therefore important to figure out the seasonal spatial distribution of this species, both in terms of number and biomass, and the environmental variables which determine them. Additionally, climate change plays an important role in determining the characteristics of individual species and thus on the ecosystems they inhabit. We set out to understand the responses of A. ovulum to habitat variables and to make projections based on the climate change scenarios described in the IPCC’s SSP1-2.6 and SSP5-8.5 criteria. We carried out seasonal bottom trawling surveys in the East China Sea region during 2018 and 2019 to fill this knowledge gap. Our results showed that the average individual size values ranged from 17.80−43.00 g·ind -1 in spring and 23.49−33.00 g·ind -1 in summer; the measured sea bottom temperature, sea bottom salinity, and depth value ranges were 10.81−27.06°C, 31.73–35.25‰, and 91–103 m independently in spring to winter. Our study showed that A. ovulum was distributed in the area between 27°–29°N, 122.5°–125°E during spring to autumn, and expanded into the area between 26.5°–32.5°N, 121°–124.5°E in winter. The core habitat of A. ovulum was centered on the area between 27.5°–28°N, 122.5°–123.5°E, and can be expected to expand to the northeast and southwest independently under the most likely global warming scenarios. Our results will benefit the development of suitable conservation measures for cephalopod habitats, and incorporate the impacts of climate change into fisheries management programs.

Dietary retinoic acid improved the growth, lipid metabolism and immune status in Macrobrachium rosenbergii - Qin-Cheng Huang; Li Wang; Zhi-Min Gu; Cui Liu; Tian-Tian Ye; Jun-Jun Yan; Ji-Lun Meng; Yu-Tong Zheng; Xian-Ping Ge; Zhi-Deng Lin; Guo-Yuan Zou (Frontiers in Marine Science, 2025)
The effect of dietary retinoic acid (RA) on the growth, lipid deposition, oxidation resistance, immunity, hepatopancreatic and intestinal health of Macrobrachium rosenbergii was evaluated. A total of 1200 prawns (0.22 ± 0.00 g) were divided into six groups and fed their corresponding feed containing 4, 132, 296, 562, 1206 or 2562 mg/kg dietary RA. The weight gain rate, specific growth rate and final body weight of the prawns changed linearly and quadratically, with the maximum observed in those fed 296 mg/kg dietary RA. Increasing dietary RA linearly and quadratically raised the RA content in the whole body. Compared to the prawns fed 4 mg/kg dietary RA, there was significantly lower lipid deposition in the muscle, hepatopancreas and whole body of prawns fed 296 mg/kg dietary RA. Prawns fed 296 mg/kg dietary RA had lower triglyceride (TG) content in the hepatopancreas with upregulated gene expression of retinoid X receptor ( RXR ), diacylglycerol acyltransferase 1 ( dgat1 ) and carnitine palmitoyltransferase 1 ( cpt1 ). Additionally, 296 mg/kg dietary RA increased the protein expression of RXR, CAMKKβ and phospho-AMPK. A dietary RA level of 296 mg/kg could decrease oxidative stress by upregulating the expression of peroxiredoxin 5 ( prx5 ) and improve immunity by upregulating expression of toll - like receptor 2 ( toll2 ), myeloid differentiation factor 88 (myd88 ) and dosal in the hepatopancreas. The intestinal health related genes ( crustin 2 / 3 / 4 , anti-lipopolysaccharide factor 1 / 7 , prx5 , peritrophin-1 , myosin light chain kinase , claudin , myd88 and dosal ) and morphological structure were also positively affected by dietary RA. Furthermore, dietary RA could relieve the immune responses induced by lipopolysaccharide, thus leading to lower transcription of antimicrobial peptides. In summary, dietary RA could improve the growth, lipid utilisation, antioxidant capacity and immunity of M . rosenbergii . To avoid the negative effects of excessive addition and obtain optimal growth, a diet containing 296 mg/kg dietary RA was suggested by the present study.

Degradation Characteristics and Mechanisms of Steel Fiber-Reinforced Concrete Linings in Subsea Tunnels: Insights from Accelerated Erosion Tests with Applied Electric Fields - Longhai Wei; Jiguo Liu; Heng Shu; Qinglong Cui; Wenbo Peng; Huimin Gong; Yiguo Xue; Min Han (Journal of Marine Science and Engineering, 2025)
Understanding the long-term durability and degradation mechanisms of steel fiber-reinforced concrete (SFRC) linings in subsea tunnels is critical for ensuring structural safety, cost effectiveness, and sustainability. This study investigated the degradation characteristics of SFRC with varying fiber contents (0%, 0.35%, 0.55%, and 0.75%) and different acceleration durations, using the applied electric field acceleration method and X-ray CT tests. The experimental results revealed the characteristics of the surface crack distribution and evolution patterns in the SFRC specimens. Furthermore, the similarity between the non-uniform corrosion patterns observed in regard to accelerated corrosion under the applied electric fields and those occurring due to natural degradation was verified. The pore structure characteristics and internal crack development of the SFRC specimens were compared. The study found that the degradation process of the specimens was closely related to the fiber content. The incorporation of steel fibers altered the crack initiation and propagation modes, leading to a more scattered crack distribution. The accelerated corrosion method, employing an applied electric field, successfully simulated the non-uniform corrosion process of reinforcement in SFRC linings in subsea tunnels under natural conditions. Under the influence of a unidirectional chloride ingress source, the pronounced accumulation of corrosion products was observed only on the side of the reinforcement exposed to chloride penetration. This method effectively visualized the chloride penetration path and its impact on reinforcement corrosion, providing valuable insights for the anti-corrosion design of SFRC linings in subsea tunnels.

Experimental investigation of the undrained dynamic behavior of soft clay under equivalent earthquake loadings - Zhong-Liang Zhang; Zhen-Dong Cui; Min-Zhe Xu (Soil Dynamics and Earthquake Engineering, 2025)

cTAGE5 is involved in the assembly of Golgi ring in mouse primordial follicle - Haowei Wu; Yaqing Wang; Jiayi Li; Yan Qin; Min Chen; Zhiming Shen; Fangfang Dong; Xiuhong Cui; Liang Liu; Zhiheng Xu; Fei Gao (Science Bulletin, 2025)

A sliding window-based coastal bathymetric method for ICESat-2 photon-counting LiDAR data with variable photon density - Jinchen He; Shuhang Zhang; Wei Feng; Xiaodong Cui; Min Zhong (Remote Sensing of Environment, 2025)

Transcriptional and molecular simulation analysis of the response mechanism of anammox bacteria to 3,4-dimethylpyrazole phosphate stress - Cui-Zhong Chen; Jin Wang; Yi-Cheng Wang; Hui-Min Fu; Xiao-Wei Xu; Peng Yan; You-Peng Chen (Journal of Hazardous Materials, 2025)

Identifying spatial drivers of soil heavy metal pollution risk integrating positive matrix factorization, machine learning, and multi-scale geographically weighted regression - Yujie Pan; Anmeng Sha; Wenjing Han; Chang Liu; Guowangchen Liu; Emily Welsch; Min Zeng; Shasha Xu; Yi Zhao; Shang Tian; Yiyi Li; Rui Deng; et al. (Journal of Hazardous Materials, 2025)

Co-occurrence of qacEΔ1 disinfectant resistance gene and ARGs among Salmonella Indiana and its correlation with resistance to sodium hypochlorite - Xinfeng Han; Shujuan Chen; Qiuyan Zeng; Jiarui Li; Haotian Liu; Ruyi Kuang; Jing Xia; Min Cui; Yong Huang; Li Bai; Likou Zou (International Journal of Food Microbiology, 2025)

Removal of mixed antibiotics from saline wastewater under intermittent electrical stimulation and alterations of microbial communities and resistance genes - Yixian Wu; Nuerla Ailijiang; Yincang Cui; Zaimire Abdusalam; Yiping Wu; Junxuan Ma; Xiaoxiao Luo; Min Li (Environmental Research, 2025)

Experimental investigation on swelling and gas breakthrough properties of GMZ bentonite considering alkaline solution effects - Lin-Yong Cui; Wei-Min Ye; Qiong Wang; Yong-Gui Chen; Bao Chen; Yu-Jun Cui (Engineering Geology, 2025)

CAS-ESM2.0 Dataset for the G1ext Experiment of the Geoengineering Model Intercomparison Project (GeoMIP) - Min Cui; Duoying Ji; John C. Moore; He Zhang; Jiangbo Jin; Kece Fei; Chenglai Wu; Jiawen Zhu; Juanxiong He; Zhaoyang Chai; Dongling Zhang (Advances in Atmospheric Sciences, 2025)
Solar radiation modification, a scheme aimed at mitigating rapid global warming triggered by anthropogenic greenhouse gas emissions, has been explored through the G1ext experiment under the Geoengineering Model Intercomparison Project (GeoMIP) framework, utilizing the Chinese Academy of Sciences Earth System Model version 2 (CAS-ESM2.0). This paper briefly describes the basic configuration and experimental design of the CAS-ESM2.0 for G1ext, which involves a sudden reduction in solar irradiance to counterbalance the radiative forcing of an abrupt quadrupling of atmospheric CO 2 concentration, running for 100 years. Preliminary results show that this model can reproduce well the compensatory effect of a uniform decrease in global solar radiation on the radiative forcing resulting from an abrupt quadrupling of CO 2 concentration. Like other Earth system models, CAS-ESM2.0 reasonably captures variations in radiative adjustments, surface air temperature, and precipitation patterns, both globally and locally, under the G1ext scenario. The generated datasets have been released on the Earth System Grid Federation data server, providing insight into the potential efficacy and impact of solar geoengineering strategies.

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

In-situ nitrogen-doped porous carbon derived from penicillin mycelial residue for CO2 adsorption and adsorption mechanism investigation - Zan Liao; Rongjiang Hao; Min Meng; Lijie Cui (Fuel, 2025)

How does global agricultural research and innovation cooperation influence agricultural R&I system transformation in the South? Evidence from UK-China cooperation - Bin Wu; Cong Cao; Simon Mosey; Tim Daniell; Peter Noy; Yizhe Cui; Min Rose; Jonathan Snape (Food Policy, 2025)

The cytotoxicity of photoexcited CdS in an E. coli-CdS hybrid system and the roles of the sacrificial agent to reduce this toxic effect - Yue Yang; Daizong Cui; He Wang; Xinyu Di; Mingyu Jia; Jinming Yang; Min Zhao (Environmental Research, 2025)

Accelerating direct formation of α-FAPbl3 by dual-additives synergism for inverted perovskite solar cells with efficiency exceeding 26 % - Min Wang; Liang Li; Jinhui Wang; Hao Huang; Peng Cui; Zhineng Lan; Shujie Qu; Yi Suo; Meicheng Li (Chemical Engineering Journal, 2025)

The relationship between serum coagulation parameters and the recurrence of chronic subdural hematoma - Zhen Bao; Sen Xu; Gang Cui; Jian-Min Qu; Tian-Yu Liang (Molecular and Cellular Biochemistry, 2025)

First report of Colletotrichum siamense and C. tropicale causing anthracnose of Syngonium podophyllum in China - Jiaming Cui; Jinhua Sun; Min Li; Gengxin Chen; Jinyu Yang; Yu Wang; Tianyu Huang; Deqiang Gong; Meijiao Hu (Crop Protection, 2025)

Development and validation of a 40 K liquid SNP array for the mud crab (Scylla paramamosain) - Shaopan Ye; Xiyi Zhou; Min Ouyang; Wenxiao Cui; Zifei Xiang; Yin Zhang; Ye Yuan; Mhd Ikhwanuddin; Shengkang Li; Huaiping Zheng; Yueling Zhang; Hongyu Ma (Aquaculture, 2025)

Dietary butyrate promoted nutrient deposition by increasing carbohydrate utilization and energy supply in Scylla paramamosain - Hongyu Peng; Min Jin; Xishuai Cui; Haiqing Cao; Wenhao Zhan; Yao Deng; Shichao Xie; Qicun Zhou (Aquaculture, 2025)

Novel peptide inhibitor of matrix Metalloproteinases-1 from pufferfish skin collagen hydrolysates and its potential Photoprotective activity via the MAPK/AP-1 signaling pathway - Bei Chen; Shuilin Cai; Lulu Cui; Ting Yu; Kun Qiao; Yongchang Su; Min Xu; Haiyan Tang; Shuji Liu; Ming Yang; Zhiyu Liu (Journal of Photochemistry and Photobiology B: Biology, 2025)

Enzymatic oxidation increases the antibacterial activity of myricetin against Staphylococcus aureus - Jiao Li; Min Sun; Yu Pan; Xiaodong Cui; Chen Li (Food Chemistry, 2025)

Investigation of elastoplastic constitutive model of rubber-sand mixture - Zhen-Dong Cui; Min-Zhe Xu; Xiao-Dong Wang (Computers and Geotechnics, 2025)

A tetrahedral DNA nanoplatform with ultrasound-triggered biomimetic nanocarriers for targeted siMCM2 delivery and reversal of imatinib resistance in gastrointestinal stromal tumors - Li Han; Quan Dai; Chuanshi He; Jinshun Xu; Likun Cui; Xiaoxiao Xie; Zijian Zhang; Min Zhuang; Xiangyu Li; Man Lu (Chemical Engineering Journal, 2025)

Flower-structured CoP@MoS2-x S-scheme heterojunction photocatalysts for enhanced hydrogen evolution and selective biomass oxidation - Jia Zhang; Jiliang Ma; Rui Cui; Weikang Ling; Min Hong; Runcang Sun (Chemical Engineering Journal, 2025)

Corrigendum to “Chitosan/rutin multifunctional hydrogel with tunable adhesion, anti-inflammatory and antibacterial properties for skin wound healing” [Carbohydr. Polym. 343 (2024) 122492 - Ran An; Chenyu Shi; Yan Tang; Zan Cui; Yinping Li; Zhiyong Chen; Min Xiao; Li Xu (Carbohydrate Polymers, 2025)

Synergistic action of novel maltohexaose-forming amylase and branching enzyme improves the enzymatic conversion of starch to specific maltooligosaccharide - Lingli Zhong; Peiwen Wang; Min Jiang; Yitong Zheng; Xiaofan Xu; Xianfeng Ye; Yan Huang; Yanling Ji; Zhongli Cui; Zhoukun Li (Carbohydrate Polymers, 2025)

Selective Activation of G Protein–Coupled Estrogen Receptor 1 (GPER1) Reduces ER Stress and Pyroptosis via AMPK Signaling Pathway in Experimental Subarachnoid Hemorrhage - Yidan Liang; Wenqiao Fu; Yin Tang; Hongjiang Ye; Yanglingxi Wang; Chao Sun; Yi Xiang; Weiming Xiong; Min Cui; Yuanlin Chen; Ting Wang; Yongbing Deng (Molecular Neurobiology, 2025)

Inhibition of ATP1V6G3 prompts hepatic stellate cell senescence with reducing ECM by activating Notch1 pathway to alleviate hepatic fibrosis - Xiao-Pei Xue; Yu Sheng; Qi-Qi Ren; Shi-Meng Xu; Min Li; Zhao-Xiu Liu; Cui-Hua Lu (Tissue and Cell, 2024)

MAT2A is essential for zygotic genome activation by maintaining of histone methylation in porcine embryos - Xiao-Han Li; Song-Hee Lee; Qin-Yue Lu; Cheng-Lin Zhan; Gyu-Hyun Lee; Ji-Dam Kim; Jae-Min Sim; Hyeon-Ji Song; Xiang-Shun Cui (Theriogenology, 2024)

Association of ambient ozone exposure with early cardiovascular damage among general urban adults: A repeated-measures cohort study in China - Qiyou Tan; Min Zhou; Xiaojie You; Jixuan Ma; Zi Ye; Wendi Shi; Xiuqing Cui; Ge Mu; Linling Yu; Weihong Chen (Science of The Total Environment, 2024)

Emission inventory of IVOCs from diesel engine emissions in China based on real-world measured data - Han Yuanxin; Hou Xiaoxiao; Zhang Fan; Yan Caiqing; Li Jia; Cui Min (Science of The Total Environment, 2024)

Assessing the discrepant role of anions in the transformation of reactive oxygen species in H2O2 and PDS system: A comparative kinetic analysis - Ling Li; Min Cheng; Hao Sun; Huan Yi; Shiyu Liu; Mingming Zhang; Yukui Fu; Xuerong Zhou; Fuhang Xu; Dengsheng Ma; Guangming Zeng; Zhengjian Yang; et al. (Journal of Hazardous Materials, 2024)

Antibiotic resistance at environmental multi-media interfaces through integrated genotype and phenotype analysis - Chen-Xi Fu; Chen Chen; Qian Xiang; Yi-Fei Wang; Lu Wang; Feng-Yuan Qi; Dong Zhu; Hong-Zhe Li; Li Cui; Wei-Li Hong; Matthias C. Rillig; Yong-Guan Zhu; et al. (Journal of Hazardous Materials, 2024)

Mining and characterization of novel antimicrobial peptides from the large-scale microbiome of Shanxi aged vinegar based on metagenomics, molecular dynamics simulations and mechanism validation - Meili Cui; Mengyue Wang; Xia Liu; Haoyan Sun; Zhenghua Su; Yu Zheng; Yanbing Shen; Min Wang (Food Chemistry, 2024)

Microwave-induced heterogeneity in protein conformation and water mobility interferes with the distribution pattern and migration pathway of sodium ion in myofibrillar protein gel - Min Zhang; Tianyi Wei; Qianting Mai; Khizar Hayat; Yaqi Hou; Shuqin Xia; Heping Cui; Jingyang Yu (Food Chemistry, 2024)

Impact of mutations in carbohydrate binding sites of tandem-repeat type galectin from Takifugu obscurus on its antimicrobial activity - Ying Huang; Li-Fan Cui; Rui Shen; Ding-Yi Chen; Min Jin; Xue Jiao; Yu-Guang Chen; Ming-Xuan Pan; Ya-Dong Hu; Zhe Zhao (Fish & Shellfish Immunology, 2024)

Feasibility assessment of biochar amendment for mitigating phytotoxicity of polyvinyl chloride micro/nano-plastics: A study based on lettuce pot experiments - Yufei Yu; Zehua Xu; Min Cui; Jia Li (Environmental Pollution, 2024)

Vitrification cryo-foil method for shoot tip cryopreservation and virus eradication in apple - Min-Rui Wang; Jun-Hua Bao; Xiao-Yan Ma; Zi-Han Yan; Zhen-Hua Cui; Li-Ying Zhu; Dong Zhang; Qiao-Chun Wang (Cryobiology, 2024)

Photothermal enhanced antibacterial chitosan-based polydopamine composite hydrogel for hemostasis and burn wound repairing - Liming Chang; Yanai Chen; Min Zhou; Yuanwei Gao; Yong Wang; Wenjuan Li; Zhe Cui; Chengyan Zhou; Yingna He; Jianglei Qin (Carbohydrate Polymers, 2024)

Light-driven biodegradation of chloramphenicol by photosensitized Shewanella oneidensis MR-1 - Yongqi Wang; Haibing Dai; Meitong Jin; Jueyu Wang; Ziheng Song; Yingjie Liu; Wenqi Chai; Lu Cheng; Na Zhao; Daizong Cui; Min Zhao (Bioresource Technology, 2024)

Comparative analysis of sulfur-driven autotrophic denitrification for pilot-scale application: Pollutant removal performance and metagenomic function - Peng Cui; Nianhong Wan; Chaoyu Li; Lei Zou; Min Ma; Jing Du; Yu Jiang (Bioresource Technology, 2024)

Circular RNA and its potential diagnostic and therapeutic values in breast cancer - Di Gao; Can Cui; Yaoxuan Jiao; Han Zhang; Min Li; Junjie Wang; Xiumei Sheng (Molecular Biology Reports, 2024)

Muscone inhibits angiotensin II–induced cardiac hypertrophy through the STAT3, MAPK and TGF-β/SMAD signaling pathways - Yi-jiang Liu; Jia-jia Xu; Cui Yang; Yan-lin Li; Min-wei Chen; Shi-xiao Liu; Xiang-hui Zheng; Ping Luo; Rui Li; Di Xiao; Zhong-gui Shan (Molecular Biology Reports, 2024)
Background Muscone is a chemical monomer derived from musk. Although many studies have confirmed the cardioprotective effects of muscone, the effects of muscone on cardiac hypertrophy and its potential mechanisms are unclear.The aim of the present study was to investigate the effect of muscone on angiotensin (Ang) II-induced cardiac hypertrophy. Methods and results In the present study, we found for the first time that muscone exerted inhibitory effects on Ang II-induced cardiac hypertrophy and cardiac injury in mice. Cardiac function was analyzed by echocardiography measurement, and the degree of cardiac fibrosis was determined by the quantitative real-time polymerase chain reaction (qRT-PCR), Masson trichrome staining and western blot assay. Secondly, qRT-PCR experiment showed that muscone attenuated cardiac injury by reducing the secretion of pro-inflammatory cytokines and promoting the secretion of anti-inflammatory cytokines. Moreover, western blot analysis found that muscone exerted cardio-protective effects by inhibiting phosphorylation of key proteins in the STAT3, MAPK and TGF-β/SMAD pathways. In addition, CCK-8 and determination of serum biochemical indexes showed that no significant toxicity or side effects of muscone on normal cells and organs. Conclusions Muscone could attenuate Ang II-induced cardiac hypertrophy, in part, by inhibiting the STAT3, MAPK, and TGF-β/SMAD signaling pathways.

Identification of key genes of diabetic cardiomyopathy in hiPSCs-CMs based on bioinformatics analysis - Shuo An; Hongchen Bi; Xiaoli Luo; Caiying Zhu; Min Wang; Aiming Pang; Yujie Cui (Molecular and Cellular Biochemistry, 2024)

Description and genomic characterization of Cohnella caldifontis sp. nov., isolated from hot springs in Yunnan province, south-west China - Ming-Xian Xiang; Cui-Ping Miao; Dian-Yan Zhang; Juan Wang; Yi-Qing Li; Min Yin; ShuKun Tang (Antonie van Leeuwenhoek, 2024)

Bacterial consortium amendment effectively reduces Pb/Cd bioavailability in soil and their accumulation in wheat - Xiaozhen Zhu; Wenliang Ju; Jingzi Beiyuan; Herong Chao; Zhiqin Zhang; Li Chen; Qingliang Cui; Tianyi Qiu; Wenju Zhang; Min Huang; Yufang Shen; Linchuan Fang (Journal of Environmental Management, 2024)

Biodegradable MAM-based amphiphilic block copolymers: Toward efficient and eco-friendly kinetic inhibitors for methane hydrate formation - Li Wan; Xiang-Long Ding; Ai-Xiang Liu; Hao Cui; Jin-Rong Zhong; Yi-Min Dai (Chemical Engineering Journal, 2024)

Advanced design of metal single-atom (Pt, Mn, Fe or Cu) loaded S-Ni(OH)2 nanosheets array catalysts to achieve high-performance overall water splitting - Wenhui Fang; Tingting Tang; Min Li; Shixian Xin; Ying Wu; Yutao Cao; Zhize Yu; Wei Cui; Zengxi Li; Hong Zhao (Chemical Engineering Journal, 2024)

Chitosan/rutin multifunctional hydrogel with tunable adhesion, anti-inflammatory and antibacterial properties for skin wound healing - Ran An; Chenyu Shi; Yan Tang; Zan Cui; Yinping Li; Zhiyong Chen; Min Xiao; Li Xu (Carbohydrate Polymers, 2024)

Reconciled estimation of Antarctic ice sheet mass balance and contribution to global sea level change from 1996 to 2021 - Rongxing Li; Guojun Li; Gang Hai; Huan Xie; Yuan Cheng; Wei Chen; Xiangbin Cui; Minghu Ding; Chunchun Gao; Tong Hao; Changqing Ke; Chuanjin Li; et al. (Science China Earth Sciences, 2024)
The Antarctic Ice Sheet (AIS) has been losing ice mass and contributing to global sea level rise (GSLR). Given its mass that is enough to cause ∼58 m of GSLR, accurate estimation of mass balance trend is critical for AIS mass loss monitoring and sea level rise forecasting. Here, we present an improved approach to reconciled solutions of mass balance in AIS and its regions from multiple contributing solutions using the input-out, altimetric, and gravimetric methods. In comparison to previous methods, such as IMBIE 2018, this approach utilizes an adaptive data aggregation window to handle the heterogeneity of the contributing solutions, including the number of solutions, temporal distributions, uncertainties, and estimation techniques. We improved the regression-based method by using a two-step procedure that establishes ensembled solutions within each method (input-output, altimetry, or gravimetry) and then estimates the method-independent reconciled solutions. For the first time, 16 contributing solutions from 8 Chinese institutions are used to estimate the reconciled mass balance of AIS and its regions from 1996 to 2021. Our results show that AIS has lost a total ice mass of ∼3213±253 Gt during the period, an equivalent of ∼8.9±0.7 mm of GSLR. There is a sustained mass loss acceleration since 2006, from 88.1±3.6 Gt yr −1 during 1996–2005 to 130.7±8.4 Gt yr −1 during 2006–2013 and further to 157.0±9.0 Gt yr −1 during 2014–2021. The mass loss signal in the West Antarctica and Antarctic Peninsula is dominant and clearly presented in the reconciled estimation and contributing solutions, regardless of estimation methods used and fluctuation of surface mass balance. Uncertainty and challenges remain in mass balance estimation in East Antarctica. This reconciled estimation approach can be extended and applied for improved mass balance estimation in the Greenland Ice Sheet and mountain glacier regions.

Comparative efficacy of alkaline slag, biomass ash, and biochar application for the amelioration of different acidic soils - Ernest Uwiringiyimana; Hong-wei Lai; Ni Ni; Ren-yong Shi; Xiao-ying Pan; Jia-ning Gao; Md Romel Biswash; Jiu-yu Li; Xiu-min Cui; Ren-kou Xu (Plant and Soil, 2024)

Research progress on pharmacological effects and bioavailability of berberine - Yulong Cui; Quanying Zhou; Min Jin; Siqi Jiang; Peizhao Shang; Xiaofan Dong; Lingjun Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

NUS1 Variants Cause Lennox-Gastaut Syndrome Related to Unfolded Protein Reaction Activation - Nan-Xiang Shen; Xiao-Chong Qu; Jing Yu; Cui-Xia Fan; Fu-Li Min; Ling-Ying Li; Ming-Rui Zhang; Bing-Mei Li; Jie Wang; Na He; Wei-Ping Liao; Yi-Wu Shi; et al. (Molecular Neurobiology, 2024)

Mechanical properties of teguline clay pellet mixtures during continuous oedometric compression - Peng-Ju Qin; Marsheal Fisonga; Yong-Feng Deng; Yu-Jun Cui; Wei-Min Ye (Applied Clay Science, 2024)

Dietary supplementation with sodium propionate and tributyrin alleviated hepatic lipid deposition and improved the antioxidant capacity and hypoxic stress resistance of spotted seabass (Lateolabrax maculatus) - Kun Cui; Hanle Zhang; Biao Yun; Jianxue Wang; Xueqiao Qian; Min Xue (Frontiers in Marine Science, 2024)
We investigated the effects of dietary supplementation with sodium propionate (SP) and tributyrin (TB) on hepatic lipid deposition and antioxidant capacity of spotted seabass ( Lateolabrax maculatus ) via an 8-week feeding experiment and a hypoxia stress experiment. The fish were fed five experimental diets: a control diet (CON), a diet supplemented with 2 g/kg SP (SP-0.2%), 4 g/kg SP (SP-0.4%), 2 g/kg TB (TB-0.2%), or 4 g/kg TB (TB-0.4%). No significant difference in growth performance was presented among the groups ( P > 0.05). The SP-0.4% and TB-0.2% groups presented significantly lower hepatosomatic and viscerasomatic indexes compared with the CON group. Then, the SP-0.4% and TB-0.2% groups presented stronger resistance to hypoxic stress than the other groups and were analyzed further. The hepatic histology and triglyceride levels revealed that SP-0.4% and TB-0.2% reduced hepatic lipid deposition. Similarly, the downregulation of malondialdehyde and the upregulation of total antioxidant capacity, superoxide dismutase, and catalase activities and the related gene expression levels revealed that SP-0.4% and TB-0.2% improved the antioxidant capacity. Additionally, the RNA sequencing demonstrated that SP-0.4% and TB-0.2% regulated gene expression to a similar extent. Among the 117 differentially expressed genes, 67 genes were enriched in the same pattern, and involved the FoxO signaling, PI3K-Akt signaling, and insulin-related pathways. In conclusion, supplementing SP-0.4% and TB-0.2% as feed additives effectively improved hepatic lipid metabolism, antioxidant capacity, and hypoxic stress resistance of spotted seabass.

Roof greening in major Chinese cities possibly afford a large potential carbon sink - Chao Yang; Yinghui Zhang; Min Chen; Song Zhu; Yuzhi Tang; Zhixin Zhang; Wei Ma; Huizeng Liu; Junyi Chen; Bohui Tang; Dejin Zhang; Zhengdong Huang; et al. (Science Bulletin, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Microbiomic and metabolomic dynamics in chrysanthemum waste at different fermentation stages - Yiyan Cui; Xinyan Ma; Miao Yu; Su Peng; Zhimei Tian; Min Song; Dun Deng; Zhichang Liu; Ting Rong; Zhenming Li; Xianyong Ma (Food Bioscience, 2024)

Vitamin C as a functional enhancer in the non-specific immune defense, antioxidant capacity and resistance to low-temperature stress of juvenile mud crab, Scylla paramamosain - Zheng Tang; Shichao Xie; Yuhui Cui; Wenhao Zhan; Yao Deng; Hongyu Peng; Haiqing Cao; Yinqiu Tian; Min Jin; Peng Sun; Yingzhao Zhang; Feng Tang; et al. (Fish & Shellfish Immunology, 2024)

Synthesis and antiproliferative activity of 7-substituted amide estradiol derivatives - Chun-Fang Gan; Ying Li; Hua-Long Chen; Jia-Wei Yao; Yun-Qiong Gu; Bin Su; Zhi-Wei Zhong; Jian-Guo Cui; Yan-Min Huang; Zhi-Ping Liu (Medicinal Chemistry Research, 2024)

Impact of corticosteroid doses on prognosis of severe and critical COVID-19 patients with Omicron variant infection: a propensity score matching study - Shiyao Wang; Ziying Chen; Xinran Zhang; Xiaojing Wu; Yuqiong Wang; Qi Zhang; Linna Huang; Xiaoyang Cui; Ying Cai; Xu Huang; Jingen Xia; Sichao Gu; et al. (Inflammopharmacology, 2024)
Background There is lack of research on corticosteroid use for severe and critical COVID-19 patients with Omicron variant infection. Methods This multi-center retrospective cohort study involved 1167 patients from 59 ICUs across the mainland of China diagnosed with severe or critical SARS-CoV-2 Omicron variant infection between November 1, 2022, and February 11, 2023. Patients were segregated into two groups based on their corticosteroid treatment—usual dose (equivalent prednisone dose 30–50 mg/day) and higher dose (equivalent prednisone dose > 50 mg/day). The primary outcome was 28-day ICU mortality. Propensity score matching was used to compare outcomes between cohorts. Results After propensity score matching, 520 patients in the usual dose corticosteroid group and 260 patients in the higher dose corticosteroid group were included in the analysis, respectively. The mortality was significantly higher in the higher dose corticosteroid group (67.3%, 175/260) compared to the usual dose group (56.0%, 291/520). Logistic regression showed that higher doses of corticosteroids were significantly associated with increased mortality at 28-day (OR = 1.62,95% CI 1.19–2.21, p = 0.002) and mortality in ICU stay (OR = 1.66,95% CI 1.21–2.28, p = 0.002). Different types of corticosteroids did not affect the effect. Conclusions The study suggests that higher-dose corticosteroids may lead to a poorer prognosis for severe and critical COVID-19 patients with Omicron variant infection in the ICU. Further research is needed to determine the appropriate corticosteroid dosage for these patients.

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Epinephelus coioides Sec3 promotes Singapore grouper iridovirus infection by negatively regulates immune response - Yu-Rong Lei; Jia-Yang He; Xue-Mei Fu; Cui-Fen Huang; Yun-Xiang Lin; Li-Ling Dai; Zi-An Chen; Ze-Peng Zhang; Fu-Min Liu; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2024)

Nitrogen removal performance and mechanism in constructed wetlands under saline conditions: Role of Canna indica inoculated with Piriformospora indica - Naxin Cui; Min Cai; Xu Zhang; Rong Zeng; Li Zhou; Guifa Chen; Guoyan Zou (Bioresource Technology, 2024)

Impact and migration behavior of triclosan on waste-activated sludge anaerobic digestion - Min-Hua Cui; Lei Chen; Thangavel Sangeetha; Wei-Mon Yan; Chao Zhang; Xue-Dong Zhang; Shi-Ming Niu; He Liu; Wen-Zong Liu (Bioresource Technology, 2024)

Meta-Analysis Study on the Role of Biochar on Soil Nitrogen Cycling - Binbin Yu; Keming Yang; Min Cui; Zilong Chen; Yuanyuan Dai; Xiaoqing Qian; Zhongzhi Chen (Journal of Soil Science and Plant Nutrition, 2024)

Polyvinyl chloride nanoplastics transport inhibited in natural sandy soil by iron-modified biochar - Zifan Ni; Xuehai Chen; Min Cui; Jia Li (Environmental Monitoring and Assessment, 2024)

Emission and optical characteristics of brown carbon in size-segregated particles from three types of Chinese ships - Fengqin Yang; Fan Zhang; Zeyu Liu; Yingjun Chen; Yan Zhang; Can Wu; Yali Lei; Shijie Liu; Binyu Xiao; Xinyi Wan; Yubao Chen; Yong Han; et al. (Journal of Environmental Sciences, 2024)

Numerical and physical implementation of controlled stress wave excitation and waveform effect in SHPB system - Chun-yang Cui; Xiang-shang Li; Jia-min Wang; Mei-mei Wang; Wei-yu Zheng; Wei-sheng Du (International Journal of Rock Mechanics and Mining Sciences, 2024)

Dietary lauric acid promoted antioxidant and immune capacity by improving intestinal structure and microbial population of swimming crab (Portunus trituberculatus) - Wenhao Zhan; Hongyu Peng; Shichao Xie; Yao Deng; Tingting Zhu; Yuhui Cui; Haiqing Cao; Zheng Tang; Min Jin; Qicun Zhou (Fish & Shellfish Immunology, 2024)

Metal-organic frameworks derived low-cost Cu-doped Co3O4 for efficient reduction of ultra-low nitrate concentrations to ammonia - Xiaorui Hu; Mingming Zhang; Cui Lai; Min Cheng; Fuhang Xu; Dengsheng Ma; Ling Li; Huchuan Yan; Hao Sun; Xing Fan; Biting Wang (Chemical Engineering Journal, 2024)

Correction to: The relationship between serum coagulation parameters and the recurrence of chronic subdural hematoma - Zhen Bao; Sen Xu; Gang Cui; Jian-Min Qu; Tian-Yu Liang (Molecular and Cellular Biochemistry, 2024)

New insights into the influences of firework combustion on molecular composition and formation of sulfur- and halogen-containing organic compounds - Caiqing Yan; Haibiao Chen; Fei Xu; Qinglong Fu; Ying Zhou; Ruizhi Zhou; Ruiyu Li; Mei Zheng; Mingjie Xie; Bin Jiang; Zhisheng Zhang; He Meng; et al. (Science of The Total Environment, 2024)

Biochar reduces antibiotic transport by altering soil hydrology and enhancing antibiotic sorption - Xiang-Yu Tang; Wen-Min Yin; Guang Yang; Jun-Fang Cui; Jian-Hua Cheng; Fei Yang; Xiao-Yu Li; Chun-Yan Wu; Sen-Gen Zhu (Journal of Hazardous Materials, 2024)

The involvement of SigmaR1K142 degradation mediated by ERAD in neural senescence linked with CdCl2 exposure - Bo Qian; Ting-Yu Li; Zhao-Xuan Zheng; Han-Yu Zhang; Wen-Qi Xu; Su-Min Mo; Jia-Jia Cui; Wei-Jie Chen; Yu-Chun Lin; Zhong-Ning Lin (Journal of Hazardous Materials, 2024)

H*ads dynamics engineering via bimetallic Pd–Cu@MXene catalyst for enhanced electrocatalytic hydrodechlorination - Lan-Ying Liu; Min-Hua Cui; John Justo Ambuchi; Shi-Ming Niu; Xin-Hui Li; Wo-Long Wang; He Liu; Guo-Shuai Liu; Ai-Jie Wang (Environmental Research, 2024)

Multi-omics association study of hexadecane degradation in haloarchaeal strain Halogranum rubrum RO2-11 - HeLang Huang; CaiYun Xie; ZiYuan Xia; ZhaoYong Sun; YaTing Chen; Min Gou; YueQin Tang; HengLin Cui; XiaoLei Wu (Environmental Research, 2024)

Engineering multifunctional phase change composites enabled by dual-interpenetrating hybrid scaffold for excellent thermal conductivity and electromagnetic absorption - Boyang Hu; Hong Guo; Ying Cui; Jiaye Li; Min Cao; Weiyan Qi; Xiwei Cao; Baoan Li (Chemical Engineering Journal, 2024)

IL-32/NFκB/miR-205 loop sustains the high expression of IL-32 and enhances the motility of cervical cancer cells - Jianbing Liu; Kai Yang; Xiaoyu Lin; Jing Xu; Xiaohua Cui; Jianqing Hao; Wei Wang; Wenhao Wang; Li Li; Min Hao (Human Cell, 2024)

Enhancing precision of root-zone soil moisture content prediction in a kiwifruit orchard using UAV multi-spectral image features and ensemble learning - Shidan Zhu; Ningbo Cui; Li Guo; Huaan Jin; Xiuliang Jin; Shouzheng Jiang; Zongjun Wu; Min Lv; Fei Chen; Quanshan Liu; Mingjun Wang (Computers and Electronics in Agriculture, 2024)

First report of Colletotrichum siamense causing leaf spot on silver date palm in China - Jinyu Yang; Min Li; Gengxin Chen; Jinhua Sun; Wu Zhang; Jiaming Cui; Yu Wang; Deqiang Gong; Meijiao Hu (Crop Protection, 2024)

Urinary haloacetic acid concentrations and thyroid function among women: Results from the TREE study - Yang Wu; Yan-Ling Deng; Min Zhang; Yu Miao; Fei-Peng Cui; Jia-Yue Zeng; Xiao-Ying Liu; Cheng-Ru Li; A-Xue Liu; Jin-Qin Zhu; Yang-Juan Li; Chong Liu; et al. (Science of The Total Environment, 2024)

Variations in plant root traits shaped by intraspecific interactions are species-specific - Shu Guo; Ka Ming Li; Min Liu; Weining Wang; Changhua Fan; Xingliang Xu; Xiaoyong Cui (Rhizosphere, 2024)

An enhanced ant colony optimization algorithm for global path planning of deep-sea mining vehicles - Weixing Liang; Min Lou; Zhangxing Chen; Huiyang Qin; Chen Zhang; Chengwei Cui; Yangyang Wang (Ocean Engineering, 2024)

Study of dynamics-microphysical-lightning activity characteristics in a tropical hailstorm - Zhe Li; Tinglong Zhang; Dong Zheng; Hai Yu; Xuelin Cui; Min Bao; Fangcong Zhou (Journal of Atmospheric and Solar-Terrestrial Physics, 2024)

Volume change characteristic of compacted bentonite during hydration upon high suction change: Experimental study and constitutive simulation - Yang Wang; Wei-Min Ye; Qiong Wang; Yong-Gui Chen; Yu-Jun Cui (Engineering Geology, 2024)

Variations in optical properties of water- and methanol-soluble organic carbon in PM2.5 in Tianjin and Handan over the Wintertime of 2018–2020 - Haibiao Chen; Ruizhi Zhou; Li Fang; Honglei Sun; Qiaoyun Yang; Hongya Niu; Junwen Liu; Yingze Tian; Min Cui; Caiqing Yan (Atmospheric Research, 2024)

Expert Consensus on Big Data Collection of Skin and Appendage Disease Phenotypes in Chinese - Shuang Zhao; Zhongling Luo; Ying Wang; Xinghua Gao; Juan Tao; Yong Cui; Aijun Chen; Daxing Cai; Yan Ding; Heng Gu; Jianying Gu; Chao Ji; et al. (Phenomics, 2024)

Facile hydrothermal assembly of three-dimensional GO-MTZE composite and its adsorption properties toward Cu2+ - Ya-Xin Cui; Jin-Min Zeng; Mei-Yi Duan; Yi-Ping Liu; Yue-Qin Liu; Jin-Gang Yu (Environmental Science and Pollution Research, 2024)

Impact of petroleum hydrocarbon and heavy metal pollution on coral reefs and mangroves: a review - Punniyakotti Elumalai; Punniyakotti Parthipan; Xueke Gao; Jinjie Cui; Arunagiri Santhosh Kumar; Perumal Dhandapani; Aruliah Rajasekar; Hemen Sarma; Nadana Raja Vadivu Ganapathy; Jayaraman Theerthagiri; Ahreum Min; Myong Yong Choi (Environmental Chemistry Letters, 2024)

High nitrogen fertilizer input enhanced the microbial network complexity in the paddy soil - Yanan Chen; Yan Li; Tianyi Qiu; Haoran He; Ji Liu; Chengjiao Duan; Yongxing Cui; Min Huang; Chunyan Wu; Linchuan Fang (Soil Ecology Letters, 2024)

Swimming short fibrous nasal drops achieving intraventricular administration - Juan Wang; Qiuyun Wang; Yifei Fu; Min Lu; Liang Chen; Zhiheng Liu; Xiaohan Fu; Xiyu Du; Buwei Yu; Han Lu; Wenguo Cui (Science Bulletin, 2024)

Biodegradation of various grades of polyethylene microplastics by Tenebrio molitor and Tenebrio obscurus larvae: Effects on their physiology - Meng-Qi Ding; Jie Ding; Zhi-Rong Zhang; Mei-Xi Li; Chen-Hao Cui; Ji-Wei Pang; De-Feng Xing; Nan-Qi Ren; Wei-Min Wu; Shan-Shan Yang (Journal of Environmental Management, 2024)

Testing for adaptive changes linked to range expansion following a single introduction of the fall webworm - Jin‐Xu Dai; Li‐Jun Cao; Jin‐Cui Chen; Fangyuan Yang; Xiu‐Jing Shen; Li‐Jun Ma; Ary Anthony Hoffmann; Min Chen; Shu‐Jun Wei (Molecular Ecology, 2024)
Adaptive evolution following colonization can affect the impact of invasive species. The fall webworm (FWW) invaded China 40 years ago through a single introduction event involving a severe bottleneck and subsequently diverged into two genetic groups. The well‐recorded invasion history of FWW, coupled with a clear pattern of genetic divergence, provides an opportunity to investigate whether there is any sign of adaptive evolution following the invasion. Based on genome‐wide SNPs, we identified genetically separated western and eastern groups of FWW and correlated spatial variation in SNPs with geographical and climatic factors. Geographical factors explained a similar proportion of the genetic variation across all populations compared with climatic factors. However, when the two population groups were analysed separately, environmental factors explained more variation than geographical factors. SNP outliers in populations of the western group had relatively stronger response to precipitation than temperature‐related variables. Functional annotation of SNP outliers identified genes associated with insect cuticle protein potentially related to desiccation adaptation in the western group and genes associated with lipase biosynthesis potentially related to temperature adaptation in the eastern group. Our study suggests that invasive species may maintain the evolutionary potential to adapt to heterogeneous environments despite a single invasion event. The molecular data suggest that quantitative trait comparisons across environments would be worthwhile.

Investigating the levels, spatial distribution, and trophic transfer patterns of short-chain chlorinated paraffins in the Southern Bohai Sea, China - Qingkui Cui; Dianfeng Han; Huawei Qin; Huanjun Li; Yongchun Liu; Wenjian Guo; Min Song; Jiawei Li; Yanqing Sun; Jingjing Luo; Jinglin Xue; Yingjiang Xu (Water Research, 2024)

Devonian sea surface temperature and paleoecology changes constrained by in situ oxygen isotopes of fish fossils - Chang Lu; Xin-Dong Cui; Jun Chen; Ze-Xian Cui; Min Zhu; Yi-Gang Xu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Efficient removal of Congo Red by carbonized Ganoderma lucidum spore with Fe3O4 - Jueyu Wang; Yue Yang; Long Bai; Yongqi Wang; Daizong Cui; Na Zhao; Min Zhao (Journal of Water Process Engineering, 2024)

Growth and physiological responses of submerged macrophytes to linear alkylbenzene sulfonate (LAS) - Cui-Min Han; Wen-Hua You (Environmental Toxicology and Pharmacology, 2024)

A dual-mode portable platform with spatiotemporal temperature–pressure signal readouts for ultrasensitive quantitative determination of cancer cells - Min Tian; Jun Wang; Wang Xiang; Zhi Zheng; Zhonghui Luo; Shihan Jing; Yuxi Zheng; Suisui He; Hua Wei; Cui-Yun Yu (Chemical Engineering Journal, 2024)

Production of bilirubin via whole-cell transformation utilizing recombinant Corynebacterium glutamicum expressing a β-glucuronidase from Staphylococcus sp. RLH1 - Wei Zhou; Yanan Cui; Mengyun Chen; Qijun Gao; Kai Bao; Yongzhong Wang; Min Zhang (Biotechnology Letters, 2024)

Dietary tributyrin supplementation promotes the growth by improving intestinal digestive and antioxidant capacity and the abundance of intestinal beneficial bacteria for swimming crab (Portunus trituberculatus) - Hongyu Peng; Min Jin; Tingting Zhu; Shichao Xie; Wenhao Zhan; Yao Deng; Yuhang Yang; Yuhui Cui; Xiangkai Li; Qicun Zhou (Aquaculture, 2024)

Interaction of microplastics with heavy metals in soil: Mechanisms, influencing factors and biological effects - Baiyan Liu; Shuling Zhao; Tianyi Qiu; Qingliang Cui; Yuyi Yang; Lili Li; Jing Chen; Min Huang; Ai Zhan; Linchuan Fang (Science of The Total Environment, 2024)

Substance flow analysis of non-intentional lead use in China from 1980 to 2050 - Mingyue Zhang; Wei Liu; Muyang Li; Tengyun Ma; Zhihui Chen; Min Liu; Zhaojie Cui (Resources, Conservation and Recycling, 2024)

Plasticity of cold and heat stress tolerance induced by hardening and acclimation in the melon thrips - Hua-Qian Cao; Jin-Cui Chen; Meng-Qing Tang; Min Chen; Ary A. Hoffmann; Shu-Jun Wei (Journal of Insect Physiology, 2024)

Endophytic Enterobacter sp. YG-14 mediated arsenic mobilization through siderophore and its role in enhancing phytostabilization - Jiawei Chen; Xuan Zhang; Min Kuang; Kunpeng Cui; Ting Xu; Xuanming Liu; Rui Zhuo; Ziwei Qin; Zhigang Bu; Zhongliang Huang; Hui Li; Jing Huang; et al. (Journal of Hazardous Materials, 2024)

Enhanced removal of Cd2+ from water by a bacterioferritin from Candidatus Kuenenia stuttgartiensis within engineering bacteria - Jin Wang; Cui-Zhong Chen; Yi-Cheng Wang; Hui-Min Fu; Peng Yan; You-Peng Chen (Chemical Engineering Journal, 2024)

Enhanced hydroisomerization of n-heptane over bifunctional catalysts with highly dispersed Pd nanoparticles supported on H-Yβ composite zeolite - Yu-Hong Kang; Xiao-Qi Zhang; Juan Gao; Guang-Hui Liu; Yan-Jun Li; Yong Gao; Jin-Jun Bai; Ai-Min Wang; Xian-Yong Wei; Cui-Ying Lu (Chemical Engineering Journal, 2024)

Comparative studies of sulfadiazine sodium degradation performance and mechanisms in the systems of persulfate with and without activation - Quantao Cui; Min Zhang; Meng Chen; Chan Yang; Caixue Song; Jingyu Sun; Suding Yan (Chemical Engineering Journal, 2024)

Coupling mechanism between sea level changes and pore heterogeneity of marine shale reservoirs driven by astronomical orbital cycles: Lower Silurian Longmaxi shale in the Upper Yangtze area, South China - Lei Chen; Min Xiong; Xiucheng Tan; Xin Chen; Jian Zheng; Yang Yang; Cui Jing; Gaoxiang Wang (Marine and Petroleum Geology, 2024)

Associations of maternal urinary rare earth elements individually and in mixtures with neonatal size at birth - Feng Qiu; Hongling Zhang; Yuan Cui; Liping Zhang; Wensi Zhou; Min Huang; Wei Xia; Shunqing Xu; Yuanyuan Li (Environmental Pollution, 2024)

Composite aerogel incorporating low temperature phase change microcapsules for enhanced thermal insulation - Bin Yan; Min Li; Honglang Lu; Menghan Pi; Jiahao Mu; Wei Cui; Rong Ran (Chemical Engineering Journal, 2024)

Characteristics of polar organic compounds from diesel truck emissions measured by FT-ICR MS - Cui Min; Han Yuanxin; Yan Caiqing; Zhang Fan; Li Jun; Chen Yingjun (Atmospheric Environment, 2024)

Efficient Removal of Cr(VI) from Wastewater by Magnetic Biochar Derived from Peanut Hull - Yuze Liu; Yinxiu Liang; Wenjie Cui; Hongyan Zhai; Min Ji (Water, Air, & Soil Pollution, 2024)

Prenatal exposures to phthalates and bisphenols in relation to oxidative stress: single pollutant and mixtures analyses - Jia-Yue Zeng; Min Zhang; Xu-Hui Chen; Chong Liu; Yan-Ling Deng; Pan-Pan Chen; Yu Miao; Fei-Peng Cui; Tian Shi; Ting-Ting Lu; Xiao-Ying Liu; Yang Wu; et al. (Environmental Science and Pollution Research, 2024)

Unveiling the crucial role of soil microorganisms in carbon cycling: A review - Haowei Wu; Huiling Cui; Chenxi Fu; Ran Li; Fengyuan Qi; Zhelun Liu; Guang Yang; Keqing Xiao; Min Qiao (Science of The Total Environment, 2024)

Characteristic chromanone acids from Calophyllum membranaceum: Determination of C-3 configuration and anti-inflammatory activity - Wei Shen; Lun Li; Qing-He Liu; Jia-Min Cui; Wei Shi; Xin-Hong Shi; Xiao-Qi Zhang; Wen-Cai Ye; Xiao-Long Hu; Hao Wang (Phytochemistry, 2024)

Suaeda salsa spectral index for Suaeda salsa mapping and fractional cover estimation in intertidal wetlands - Yinghai Ke; Yue Han; Liyue Cui; Peiyu Sun; Yukui Min; Zhanpeng Wang; Zhaojun Zhuo; Qingqing Zhou; Xiaolan Yin; Demin Zhou (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Gas chromatography ion mobility spectroscopy: A rapid and effective tool for monitoring oil oxidation - Fang Cui; Min Liu; Xue Li; Du Wang; Fei Ma; Li Yu; Chundi Hu; Peiwu Li; Liangxiao Zhang (Food Research International, 2024)

Synergistic effect between Ni single atoms and Ni nanoparticles for effectively boosting sustainable co-electrolysis of CO2 and hydrazine - Min Li; Ye Hu; Wenhui Fang; Shixian Xin; Ying Wu; Yutao Cao; Wei Cui; Zengxi Li; Hong Zhao (Chemical Engineering Journal, 2024)

Baicalin exerts neuroprotective actions by regulating the Nrf2-NLRP3 axis in toxin-induced models of Parkinson's disease - Jiahua Huang; Xinyue Zhang; Xueping Yang; Qingyun Yv; Fanlong Ye; Sheng Chen; Ying Cui; Linting Gu; Min Zhu; Wenwei Li (Chemico-Biological Interactions, 2024)

Study of glutathione S-transferase (CqGSTs) gene expression patterns, the response of basic helix–loop–helix (bHLH) transcription factor and genome-wide identification gene family in quinoa (Chenopodium quinoa Willd.) and its mechanisms of salt stress tolerance - Kaiyuan Cui; Hafeez Noor; Fida Noor; Pengcheng Ding; Min Sun; Zhiqiang Gao (Brazilian Journal of Botany, 2023)

Effects of oyster shells on maturity and calcium activation in organic solid waste compost - Wanlin Song; Yang Zeng; Jiali Wu; Qian Huang; Ruirui Cui; Derui Wang; Yuxue Zhang; Min Xie; Dawei Feng (Chemosphere, 2023)

Characteristics of intermediate volatility organic compounds emitted from inland vessels with different influential factors and implication of reduction emissions - Min Cui; Yuanyuan Xu; Zeyu Liu; Yishun Zhang; Fan Zhang; Caiqing Yan; Yingjun Chen (Science of The Total Environment, 2023)

Biomass-derived 3D evaporator with antifouling and salt-rejecting toward solar-enabled steam generation, desalination, and electricity generation - Wenjing Ma; Wenxuan Cao; Min Cui; Haifeng Lu; Ranhua Xiong; Chaobo Huang (Chemical Engineering Journal, 2023)

PPAR-γ promotes the polarization of rat retinal microglia to M2 phenotype by regulating the expression of CD200-CD200R1 under hypoxia - Yiyi Hong; Li Jiang; Fen Tang; Mingyuan Zhang; Ling Cui; Haibin Zhong; Fan Xu; Min Li; Changzheng Chen; Lifei Chen (Molecular Biology Reports, 2023)

Micropeptides: origins, identification, and potential role in metabolism-related diseases - Yirui Lu; Yutong Ran; Hong Li; Jiao Wen; Xiaodong Cui; Xiaoyun Zhang; Xiumei Guan; Min Cheng (Journal of Zhejiang University-SCIENCE B, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Gas production prediction using AM-BiLSTM model optimized by Whale Optimization Algorithm - Lei Qiao; Hui-Cui Xin; Zhi-Min Xu; Kun Xiao (Applied Geophysics, 2023)

A novel approach to the automatic classification of wireline log-predicted sedimentary microfacies based on object detection - Zhong Hong; Guo-Liang Yan; Xiang-Li Cui; Gai Gao; Guang-Min Hu (Applied Geophysics, 2023)

Curcumin strengthens a spontaneous self-protective mechanism-SP1/PRDX6 pathway, against di-n-butyl phthalate-induced testicular ferroptosis damage - Hengtao Bu; Bao Wang; Yulin Wu; Pu Li; Yankang Cui; Xuping Jiang; Xiaowen Yu; Bianjiang Liu; Min Tang (Environmental Science and Pollution Research, 2023)

Advantages of residual phenol in coal chemical wastewater as a co-metabolic substrate for naphthalene degradation by microbial electrolysis cell - Peng Ding; Ping Wu; Qihao Cao; Hongbo Liu; Chongjun Chen; Min-Hua Cui; He Liu (Science of The Total Environment, 2023)

Enhancing degradation of organic matter in microbial electrolytic cells coupled with anaerobic digestion (MEC-AD) systems by carbon-based materials - Mengmeng Li; Qun Zhang; Yang Liu; Jiachen Zhu; Faqian Sun; Min-Hua Cui; He Liu; Tian C. Zhang; Chongjun Chen (Science of The Total Environment, 2023)

Hydrogel-based intelligent greenhouse films for simultaneous fogging prevention and indoor environmental monitoring - Honglang Lu; Huanxiong Liang; Jianle Liu; Hui Zhou; Menghan Pi; Min Li; Bin Yan; Wei Li; Wei Cui; Rong Ran (Chemical Engineering Journal, 2023)

Enhancing biomass oxidation with carbon nitride nanosheets ring inserted on C. I. Pigment Yellow 53 photocatalysts for simultaneous CO and lactic acid production - Weikang Ling; Jiliang Ma; Zhendong Liu; Rui Cui; Junqiang Zhang; Xinze Li; Min Hong; Runcang Sun (Chemical Engineering Journal, 2023)

Tuning 3D refractive indices via constrained uniaxial stretch in cellulose triacetate films plasticized with triethyl citrate - Xueqing Han; Xiaoyu Min; Tong Wu; Minfang An; Lingpu Meng; Liangbin Li; Kunpeng Cui (Carbohydrate Polymers, 2023)

Linking soil depth to aridity effects on soil microbial community composition, diversity and resource limitation - Haoran He; Mingzhe Xu; Wenting Li; Li Chen; Yanan Chen; Daryl L. Moorhead; Albert C. Brangarí; Ji Liu; Yongxing Cui; Yi Zeng; Zhiqin Zhang; Chengjiao Duan; et al. (CATENA, 2023)

The effect of chronic intermittent hypobaric hypoxia improving liver damage in metabolic syndrome rats through ferritinophagy - Fang Cui; Haichao Mi; Ruotong Wang; Yutao Du; Fan Li; Shiyang Chang; Yangchen Su; Aijing Liu; Min Shi (Pflügers Archiv - European Journal of Physiology, 2023)

Functional-structural decoupling in visual network is associated with cognitive decline in patients with type 2 diabetes mellitus: evidence from a multimodal MRI analysis - Min-Hua Ni; Ying Yu; Yang Yang; Ze-Yang Li; Teng Ma; Hao Xie; Si-Ning Li; Pan Dai; Xin-Yu Cao; Yan-Yan Cui; Jun-Ling Zhu; Guang-Bin Cui; et al. (Brain Imaging and Behavior, 2023)

Antagonistic effect of selenium on programmed necrosis of testicular Leydig cells caused by cadmium through endoplasmic reticulum stress in chicken - Lulu Hou; Size Wang; Yueyue Wang; Min Wang; Zilin Cui; He Huang (Environmental Science and Pollution Research, 2023)

The time-varying impact of geopolitical risk on natural resource prices: The post-COVID era evidence - Shusheng Ding; Kaihao Wang; Tianxiang Cui; Min Du (Resources Policy, 2023)

Thermodynamic and economic analysis of a hydrogen production process from medical waste by plasma gasification - Kexin Yin; Runqi Zhang; Min Yan; Lei Sun; Yixin Ma; Peizhe Cui; Zhaoyou Zhu; Yinglong Wang (Process Safety and Environmental Protection, 2023)

The control of curved faults on structural trap formation: Tiantai slope belt, Xihu Sag, East China Sea - Xiaoqing Zhang; Gongcheng Zhang; Yiming Jiang; Min Cui; Xinjian He (Marine and Petroleum Geology, 2023)

The effect of microbial electrolysis cell coupled with anaerobic digestion for landfill leachate treatment - Mengmeng Li; Qun Zhang; Faqian Sun; Min-Hua Cui; He Liu; Chongjun Chen (Journal of Water Process Engineering, 2023)

Atomic hydrogen-mediated enhanced electrocatalytic hydrodehalogenation on Pd@MXene electrodes - Lan-Ying Liu; Guo-Shuai Liu; Shi-Ming Niu; He Liu; Min-Hua Cui; Ai-Jie Wang (Journal of Hazardous Materials, 2023)

Short-term responses of macroinvertebrate assemblages to the “ten-year fishing ban” in the largest highland lake of the Yangtze basin - Lu Yang; Min Pan; Jingrui Sun; Yongde Cui; Jinyan Dong; Jiaojiao Yang; Songhao Ji; Juan Tao; Chengzhi Ding (Journal of Environmental Management, 2023)

Multiple path-dominated activation of peroxymonosulfate by MOF-derived Fe2O3/Mn3O4 for catalytic degradation of tetracycline - Chensi Tang; Min Cheng; Cui Lai; Ling Li; Zhen Wei; Dengsheng Ma; Li Du; Guangfu Wang; Lu Yang; Lin Tang (Journal of Environmental Chemical Engineering, 2023)

Biodegradability enhancement of waste lubricating oil regeneration wastewater using electrocoagulation pretreatment - Li-li Shan; Zhao Tan; Yu Chen; Ruo-shan Wang; Meng Zhang; Chang-long Pang; Yu-Hong Cui; Zhi-min Liao; Hong-qiang Ma; Ze-bing Zhu (Environmental Science and Pollution Research, 2023)

The role of BECCS technology in achieving carbon neutrality: evidences from China’ coal power sector - Yun-Long Zhang; Jia-Ning Kang; Min Dai; Juan-Juan Hou; Lan-Cui Liu; Yi-Ming Wei; Hua Liao (Environment, Development and Sustainability, 2023)

Three new compounds with their anti-glioma effects from the roots of Arnebia guttata Bunge - Yu-Mei Yan; Lin-Jun Zou; Min-Hui Li; Zhao-Cui Sun; Min Zhang; Xu-Dong Xu; Chun-Hong Zhang (Natural Product Research, 2023)

Effects of dietary isoleucine level on growth and expression of genes related to nutritional and physiological metabolism of swimming crab (Portunus trituberculatus) - Shichao Xie; Xiangkai Li; Yuhang Yang; Chen Guo; Xiangsheng Zhang; Tingting Zhu; Jiaxiang Luo; Zheng Yang; Wenli Zhao; Yuhui Cui; Lefei Jiao; Qicun Zhou; et al. (Aquaculture, 2023)

Chronic intermittent hypobaric hypoxia improves iron metabolism disorders via the IL-6/JAK2/STAT3 and Epo/STAT5/ERFE signaling pathways in metabolic syndrome rats - Fang Cui; Jie Sun; Haichao Mi; Bo Li; Longmei Tang; Ruotong Wang; Yutao Du; Bingyan Guo; Yongjun Li; Min Shi (Journal of Trace Elements in Medicine and Biology, 2023)

Tuning the intrinsic catalytic sites of magnetite to concurrently enhance the reduction of H2O2 and O2: Mechanism analysis and application potential evaluation - Ling Li; Min Cheng; Eydhah Almatrafi; Lei Qin; Shiyu Liu; Huan Yi; Lu Yang; Zhexin Chen; Dengsheng Ma; Mingming Zhang; Xuerong Zhou; Fuhang Xu; et al. (Journal of Hazardous Materials, 2023)

“Mini-community” simulation revealed the differences of endophytic fungal communities between the above- and below-ground tissues of Ephedra sinica Stapf - Xi Liu; Jin-Long Cui; Zhong-Ya Zhou; Zong-Bao Zhang; Xuan-Ge Cui; Bo Han; Jun-Hong Wang; Meng-Liang Wang; Yi-Min Li (Fungal Biology, 2023)

Effects of nitrogen forms on nitrogen utilization, yield, and quality of two wheat varieties with different gluten characteristics - Haixing Cui; Yongli Luo; Chunhui Li; Yonglan Chang; Min Jin; Yong Li; Zhenlin Wang (European Journal of Agronomy, 2023)

Individual and joint associations of urinary phthalate metabolites with polycystic ovary and polycystic ovary syndrome: Results from the TREE cohort - Min Zhang; Chong Liu; Xiao-Qiong Yuan; Fei-Peng Cui; Yu Miao; Wen Yao; Dan-Yu Qin; Yan-Ling Deng; Pan-Pan Chen; Jia-Yue Zeng; Xiao-Ying Liu; Yang Wu; et al. (Environmental Toxicology and Pharmacology, 2023)

A model for describing advective and diffusive gas transport through initially saturated bentonite with consideration of temperature - Lin-Yong Cui; Wei-Min Ye; Qiong Wang; Yong-Gui Chen; Yu-Jun Cui (Engineering Geology, 2023)

Gorgeous turn-back: Rough surface treatment strategy induces Cu-C and N-C active moieties for bifunctional oxygen electrocatalysis - Shuai Wang; Zhongmei Che; Min Zou; Yue Wu; Min Cui; Yingshu Guo; Mingrui Zhang; Wei Hu; Zihan Zou; Guangqiang Lv; Zexing Wu; Jeonghun Kim; et al. (Chemical Engineering Journal, 2023)

Ultrasonic-assisted hypochlorite activation accelerated volatile fatty acids production during sewage sludge fermentation: Critical insights on solubilization/hydrolysis stages and microbial traits - Rui Zhu; Shanshan Zhao; Chenlu Ju; Qing Yang; Chengcheng Cui; Lijuan Wu; Min Wang; Leiyu Feng; Yang Wu (Bioresource Technology, 2023)

The composition characteristics of endophytic communities and their relationship with metabolites profile in Ephedra sinica under wild and cultivated conditions - Hui Zhang; Ye Xia; Jin-Long Cui; Xin Ji; Shuang-Man Miao; Gang Zhang; Yi-Min Li (Environmental Science and Pollution Research, 2023)

Exploring the role of detoxification genes in the resistance of Bursaphelenchus xylophilus to different exogenous nematicidal substances using transcriptomic analyses - Jingxin Cao; Xin Hao; Yang Li; Ruina Tan; Zhixin Cui; Lu Li; Yue Zhang; Jingyu Cao; Mengru Min; Liwei Liang; Zhe Xu; Wei Ma; et al. (Pesticide Biochemistry and Physiology, 2023)

Combined effect of simulated microgravity and low-dose ionizing radiation on structure and antibiotic resistance of a synthetic community model of bacteria isolated from spacecraft assembly room - Yueying Lu; Yifan Fu; Letian Chen; Jingjing Cui; Min Huang; Yuming Fu; Hong Liu (Life Sciences in Space Research, 2023)

Effect of a novel joint connection of UHPC wet joint and tapered sleeve locking-type couplers on the lateral cyclic response of precast segmental railway bridge columns - Yuxuan Wang; Zhao Cheng; Shuai Li; Jingquan Wang; Rui Zhong; Min Zeng; Fayan Ming; Bing Cui (Engineering Structures, 2023)

Electron uptake from solid electrodes promotes the more efficient conversion of CO2 to polyhydroxybutyrate by using Rhodobacter sphaeroides - Shuwei Li; Minsoo Kim; Da Seul Kong; Kyoungseon Min; Guangxi Wu; Meiying Cui; Changman Kim; You-Kwan Oh; Soek Kim; Soo Youn Lee; Sung Gyun Kang; Yvonne Nygård; et al. (Chemical Engineering Journal, 2023)

Evaluation of the respective contribution of anode and cathode for triclosan degradation in a bioelectrochemical system - Min-Hua Cui; Qian Zhang; John Justo Ambuchi; Lan-Ying Liu; Lei Chen; Shi-Ming Niu; Chao Zhang; Hong-Bo Liu; Chao Tie; Xue-Juan Bi; He Liu; Ai-Jie Wang (Bioresource Technology, 2023)

Knockdown of USF2 inhibits pyroptosis of podocytes and attenuates kidney injury in lupus nephritis - Ying Xie; Xiaoying Li; Wenli Deng; Nan Nan; Huimei Zou; Lei Gong; Min Chen; Jie Yu; Peilei Chen; Daolin Cui; Fan Zhang (Journal of Molecular Histology, 2023)

M2 Macrophage-Derived Exosomal Ferritin Heavy Chain Promotes Colon Cancer Cell Proliferation - Zilu Cui; Wenkun Li; Yadan Wang; Mengran Zhao; Kuiliang Liu; Yi Yang; Shuo Teng; Nan Zhang; Li Min; Peng Li; Shutian Zhang; Junxuan Xu; et al. (Biological Trace Element Research, 2023)

Release characteristics and toxicity assessment of micro/nanoplastics from food-grade nonwoven bags - Jia Li; Qian Wang; Min Cui; Songguo Yu; Xuehai Chen; Jun Wang (Science of The Total Environment, 2023)

Nonagricultural emissions enhance dimethylamine and modulate urban atmospheric nucleation - Yunhua Chang; Qingyang Ling; Xinlei Ge; Xiangyang Yuan; Shengqian Zhou; Kai Cheng; Jianjiong Mao; Dandan Huang; Qingyao Hu; Jun Lu; Shijie Cui; Yaqing Gao; et al. (Science Bulletin, 2023)

The regulating role of applied voltage on methanogenesis in an up-flow single-chamber microbial electrolysis assisted reactor - Lei Gao; Thangavel Sangeetha; Ling Wang; Min-Hua Cui; Ze-Chong Guo; Wei-Mon Yan; Wen-Zong Liu; Ai-Jie Wang (Journal of Water Process Engineering, 2023)

Mixed cropping increases grain yield and lodging resistance by improving the canopy light environment of wheat populations - Chunhui Li; Wenqian Li; Yongli Luo; Min Jin; Yonglan Chang; Haixing Cui; Shufang Sun; Yong Li; Zhenlin Wang (European Journal of Agronomy, 2023)

Surfactant-induced intervention in interfacial polymerization to develop highly-selective thin-film composite membrane for forward osmosis process - Xuan Zhang; Hui-Min Cui; Yu Gao; Zhi-Wei Yan; Xi Yan; Yan Chen; Xiao-Jing Guo; Wan-Zhong Lang (Desalination, 2023)

Phod-harboring bacterial communities mediated slow and fast phosphorus transformation in alkaline soil of a Robinia pseudoacacia afforestation chronosequence - Ying Wang; Lin Yang; Jiawen Zhang; Yan Li; Haibin Kang; Xiaoxiong Bai; Yongxing Cui; Min Zhang; Liguo Dong; Xuan Yu (Plant and Soil, 2023)

Stable isotope labeling differential glycans discovery in the serum of acute myocardial infarction by ultrahigh-performance liquid chromatography-quadrupole-Orbitrap high resolution mass spectrometry - Xi-Ling Li; Yuxuan Li; Shuyun Xiao; Qingsong Li; Chengqiang Han; Danyang Liu; Tengfei Cui; Xiyang Rao; Kenichiro Todoroki; Guang Yang; Jun Zhe Min (Analytica Chimica Acta, 2023)

Removal of pristine and aged microplastics from water by magnetic biochar: Adsorption and magnetization - Jia Li; Xuehai Chen; Songguo Yu; Min Cui (Science of The Total Environment, 2023)

A new insight into the potential drivers of antibiotic resistance gene enrichment in the collembolan gut association with antibiotic and non-antibiotic agents - Yi-Fei Wang; Tian-Gui Cai; Zhe-Lun Liu; Hui-Ling Cui; Dong Zhu; Min Qiao (Journal of Hazardous Materials, 2023)

Intercalation species regulation in layered vanadium oxide scaffolds enables long cycle life Mg-metal anodes - Jing Liu; Zhenfang Zhou; Min Wang; Jinlei Zhang; Zhenjiang Li; Guicun Li; Fujun Li; Guanglei Cui; Zhonghua Zhang (Chemical Engineering Journal, 2023)

PcCLCg is involved in the accumulation of Cl− in shoots for osmotic adjustment and salinity resistance in the Cl−-tolerant xerophyte Pugionium cornutum - Yan-Nong Cui; Zi-Ru Lin; Mei-Mei Cai; Rui-Wen Liu; Suo-Min Wang; Qing Ma (Plant and Soil, 2023)

Aged polyamide microplastics enhance the adsorption of trimethoprim in soil environments - Jia Li; Songguo Yu; Min Cui (Environmental Monitoring and Assessment, 2023)

A new chamigrane sesquiterpene from the rice fermentation of Antrodiella albocinnamomea - Min Guo; Ying-Zhong Liang; Xiu-Ming Cui; Lin-Jiao Shao; Yin-Fei Li; Xiao-Yan Yang (Natural Product Research, 2023)

Dissolved biochar fractions and solid biochar particles inhibit soil acidification induced by nitrification through different mechanisms - Ren-Yong Shi; Ni Ni; Ru-Hai Wang; Jackson Nkoh Nkoh; Xiao-Ying Pan; Ge Dong; Ren-Kou Xu; Xiu-Min Cui; Jiu-Yu Li (Science of The Total Environment, 2023)

First occurrence of hybodontid teeth in the Luoping Biota (Middle Triassic, Anisian) and recovery of the marine ecosystem after the end-Permian mass extinction - Wen Wen; Qiyue Zhang; Jürgen Kriwet; Shixue Hu; Changyong Zhou; Jinyuan Huang; Xindong Cui; Xiao Min; Michael J. Benton (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Nitrogen regulates stem lodging resistance by breaking the balance of photosynthetic carbon allocation in wheat - Chunhui Li; Yonglan Chang; Yongli Luo; Wenqian Li; Min Jin; Yuanyuan Wang; Haixing Cui; Shufang Sun; Yong Li; Zhenlin Wang (Field Crops Research, 2023)

Simultaneous ion fractionation and concentration by selectrodialysis for saline wastewater valorization - Zhenzhen Cui; Wenguang Wang; Yong Lin; Min Hu; Yuebiao Li; Boyu Pan; Ming Tan; Yang Zhang (Desalination, 2023)

Distribution characteristics and environmental effects of non-methane hydrocarbons in the East China Sea - Wen-Zhu Qiao; Ying-Cui Wu; Ping Wang; Jian Wang; Li-Min Zhou; Si-Tong Li; Hong-Hai Zhang (Continental Shelf Research, 2023)

Highly anti-interference electrocatalytic sensing for dopamine with nitrogen-doped graphdiyne directly in biofluids - Min Cui; Peicheng Xin; Zhongmei Che; Min Zou; Mingrui Zhang; Xiaofeng Sun; Yanan Yuan; Zihan Zou; Guangqiang Lv; Shuai Wang; Wei Hu (Chemical Engineering Journal, 2023)

Design of a highly efficient Cu-based catalyst with two functional areas: The role of Cu0 and oxygen vacancies in Fenton-like system - Cui Lai; Lu Yang; Ling Li; Dengsheng Ma; Min Cheng; Shiyu Liu; Mingming Zhang; Huchuan Yan; Chensi Tang; Zhexin Chen; Lin Tang (Chemical Engineering Journal, 2023)

Metatranscriptomic insights into the microbial electrosynthesis of acetate by Fe2+/Ni2+ addition - Jie Zhang; He Liu; Yan Zhang; Bo Fu; Chao Zhang; Min-Hua Cui; Ping Wu; Zi-Wei Guan (World Journal of Microbiology and Biotechnology, 2023)

Cell entry of Bovine herpesvirus-1 through clathrin- and caveolin-mediated endocytosis requires activation of PI3K-Akt-NF-κB and Ras-p38 MAPK pathways as well as the interaction of BoHV-1 gD with cellular receptor nectin-1 - Yang Liu; Qi Zhang; Min Zou; Jin Cui; Xiaojie Shi; Linjie Li; Faxing Wu; Xingang Xu (Veterinary Microbiology, 2023)

Understory ferns promote the restoration of soil microbial diversity and function in previously degraded lands - Yuming Lu; Maokui Lyu; Xiaoling Xiong; Cui Deng; Yongmeng Jiang; Min Zeng; Jinsheng Xie (Science of The Total Environment, 2023)

Rigorous dynamic simulation methodology for scenario-based safety analysis of pressure-swing distillation considering independent protections - Chengtian Cui; Meng Qi; Chi-Min Shu; Yi Liu (Process Safety and Environmental Protection, 2023)

Cycloartane triterpene glycosides from Actaea vaginata - Min-Li Zhang; Yi-Min Li; Zi-Xuan Zhao; Xiang-Yuan Li; Zhao-Cui Sun; Guo-Xu Ma; Mei-Hua Yang; Xu-Dong Xu; Xiao-Feng Zhang; Hai-Feng Wu; Qiong-Yu Zou; Nelbon Giloi (Phytochemistry Letters, 2023)

Disturbance and restoration of soil microbial communities after in-situ thermal desorption in a chlorinated hydrocarbon contaminated site - Jiali Shentu; Qianqian Chen; Yuxue Cui; Yangyang Wang; Li Lu; Yuyang Long; Min Zhu (Journal of Hazardous Materials, 2023)

Synthesis of composite zeolite membrane by low-temperature water bath for efficient dynamic hardwater softening - Lian Liu; Xingfa Deng; Yan He; Xue-min Cui (Journal of Environmental Chemical Engineering, 2023)

One-dimensional nonlinear rheological consolidation analysis of soft ground under continuous drainage boundary conditions - Penglu Cui; Wengui Cao; Zan Xu; Huixin Li; Min Hu (Computers and Geotechnics, 2023)

Dynamic microbial community composition, co-occurrence pattern and assembly in rhizosphere and bulk soils along a coniferous plantation chronosequence - Ying Wang; Liguo Dong; Min Zhang; Yongxing Cui; Xiaoxiong Bai; Bin Song; Jiawen Zhang; Xuan Yu (CATENA, 2023)

To what extent can recycling batteries help alleviate metal supply shortages and environmental pressures in China? - Min Liu; Wenqiu Liu; Wei Liu; Zhihui Chen; Zhaojie Cui (Sustainable Production and Consumption, 2023)

Evaluation of the effect of biofilm formation on the reductive transformation of triclosan in cathode-modified electrolytic systems - Shi-Ming Niu; Qian Zhang; Thangavel Sangeetha; Lei Chen; Lan-Ying Liu; Ping Wu; Chao Zhang; Wei-Mon Yan; He Liu; Min-Hua Cui; Ai-Jie Wang (Science of The Total Environment, 2023)

Selenium alleviates cadmium-induced oxidative stress, endoplasmic reticulum stress and programmed necrosis in chicken testes - Min Wang; Yueyue Wang; Size Wang; Lulu Hou; Zilin Cui; Qi Li; He Huang (Science of The Total Environment, 2023)

Solid-state fermentation improves the quality of chrysanthemum waste as an alternative feed ingredient - Yiyan Cui; Su Peng; Dun Deng; Miao Yu; Zhimei Tian; Min Song; Jingjing Luo; Xinyan Ma; Xianyong Ma (Journal of Environmental Management, 2023)

Economic, environmental, energy and exergy analysis and multi-objective optimization for efficient purification of a friendly gasoline additive by extractive distillation coupled with pervaporation - Yuyang Jiao; Min Yan; Xianlong Wang; Jianhui Zhong; Yusen Chen; Wenguang Zhu; Xin Li; Zhaoyou Zhu; Peizhe Cui; Yanyue Lu; Yinglong Wang (Fuel, 2023)

Vegetation position impacts soil carbon losses on the slope of the Loess Plateau of China - Peng Shi; Lulu Bai; Zhun Zhao; Jingbing Dong; Zhanbin Li; Zhiqiang Min; Lingzhou Cui; Peng Li (CATENA, 2023)

Soil microbial trait-based strategies drive the storage and stability of the soil carbon pool in Robinia pseudoacacia plantations - Min Zhang; Xiaoxiong Bai; Ying Wang; Yan Li; Yongxing Cui; Sile Hu; M. Adams Jonathan; Liguo Dong; Xuan Yu (CATENA, 2023)

The real-time detection of acupuncture-induced extracellular ATP mobilization in acupoints and exploration of its role in acupuncture analgesia - Wei-Min Zuo; Yu-Jia Li; Kai-Yu Cui; Dan Shen; Di Zhang; Ya-Wen Zheng; Meng Huang; Yong Wu; Xue-Yong Shen; Li-Na Wang; Guang-Hong Ding (Purinergic Signalling, 2023)

The positive effects of polypropylene and polyvinyl chloride microplastics on agricultural soil quality - Jia Li; Yufei Yu; Zhengyan Zhang; Min Cui (Journal of Soils and Sediments, 2023)

The conserved L1089 in the S2 subunit of avian infectious bronchitis virus determines viral kidney tropism by disrupting virus-cell fusion - Shu-Yun Li; Yu-Xi Shen; Xue-Lian Xiang; Yong-Xin Li; Nian-Ling Li; An-Dong Wang; Min Cui; Xin-Feng Han; Yong Huang; Jing Xia (Veterinary Microbiology, 2023)

Reducing plant pathogens could increase crop yields after plastic film mulching - Pingxing Wan; Ningning Zhang; Yufei Li; Shiqing Li; Feng-Min Li; Zengtuan Cui; Feng Zhang (Science of The Total Environment, 2023)

Comprehensive analysis and energy efficient process design for separation of four high purity components from organosilicon system - Haixia Li; Chen Li; Min Yan; Yinglong Wang; Zhaoyou Zhu; Peizhe Cui; Xin Li; Yanyue Lu (Process Safety and Environmental Protection, 2023)

Evaluating the social license to operate of waste-to-energy incineration projects: A case study from the Yangtze River Delta of China - Xinyao He; Min Xu; Caiyun Cui; Bo Xia; Yongjian Ke; Martin Skitmore; Yong Liu (Journal of Cleaner Production, 2023)

Effects of the astronomical orbital cycle on organic matter accumulation during the Late Ordovician–early Silurian in the Upper Yangtze area, South China - Min Xiong; Lei Chen; Xiucheng Tan; Xin Chen; Jian Zheng; Yang Yang; Cui Jing; Gaoxiang Wang (Journal of Asian Earth Sciences, 2023)

Development and validation of single-step microwave-assisted digestion method for determining heavy metals in aquatic products: Health risk assessment - Yong Min Lao; Cui Lan Qu; Bing Zhang; Hui Jin (Food Chemistry, 2023)

Within-day variability, predictors, and risk assessments of exposure to parabens among Chinese adult men - Yu Miao; Pan-Pan Chen; Min Zhang; Fei-Peng Cui; Chong Liu; Yan-Ling Deng; Jia-Yue Zeng; Wen-Jun Yin; Qiang Zeng (Environmental Research, 2023)

Enhanced photocatalytic inactivation of Cylindrospermopsis raciborskii by modified TiO2/Ag3PO4: Efficiency and mechanism - Li Zhou; Xu Zhang; Min Cai; Naxin Cui; Guoyan Zou; Zhiyong Zhao (Chemical Engineering Journal, 2023)

Insights into reactive species generation and organics selective degradation in Fe-based heterogeneous Fenton-like systems: A critical review - Ling Li; Zhuo Yin; Min Cheng; Lei Qin; Shiyu Liu; Huan Yi; Mingming Zhang; Yukui Fu; Xiaofeng Yang; Xuerong Zhou; Guangming Zeng; Cui Lai (Chemical Engineering Journal, 2023)

AcHKT1;2 is a candidate transporter mediating the influx of Na+ into the salt bladder of Atriplex canescens - Huan Guo; Yan-Nong Cui; Le Zhang; Shan Feng; Zhi-Jie Ren; Suo-Min Wang; Ai-Ke Bao (Plant and Soil, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

The microbial synergy and response mechanisms of hydrolysis-acidification combined microbial electrolysis cell system with stainless-steel cathode for textile-dyeing wastewater treatment - Jiawei Xie; Xinyi Zou; Yaofeng Chang; Junxiang Xie; He Liu; Min-hua Cui; Tian C. Zhang; Chongjun Chen (Science of The Total Environment, 2023)

Real-world characterization of carbonaceous substances from industrial stationary and process source emissions - Min Cui; Yuanyuan Xu; Fan Zhang; Caiqing Yan; Jun Li; Mei Zheng; Yingjun Chen (Science of The Total Environment, 2023)

A jasmonate-responsive bHLH transcription factor TaMYC2 positively regulates triterpenes biosynthesis in Taraxacum antungense Kitag - Tingyao Liu; Jingjing Liao; Min Shi; Li Li; Qun Liu; Xin Cui; Wei Ning; Guoyin Kai (Plant Science, 2023)

Social acceptance of NIMBY facilities: A comparative study between public acceptance and the social license to operate analytical frameworks - Min Xu; Yong Liu; Caiyun Cui; Bo Xia; Yongjian Ke; Martin Skitmore (Land Use Policy, 2023)

Efficient preparation of red mud-based geopolymer microspheres (RM@GMs) and adsorption of fluoride ions in wastewater - Min Yi; Kaituo Wang; Hongyang Wei; Deshuai Wei; Xuefei Wei; Binghu Wei; Lin Shao; Toyohisa Fujita; Xuemin Cui (Journal of Hazardous Materials, 2023)

Urinary phthalate metabolites and the risk of endometrial polyp: A pilot study from the TREE cohort - Min Zhang; Chong Liu; Xiao-Qiong Yuan; Wen Yao; Qing-Yun Yao; Yong Huang; Ni-Jie Li; Yan-Ling Deng; Pan-Pan Chen; Yu Miao; Fei-Peng Cui; Yu-Feng Li; et al. (Environmental Pollution, 2023)

Impacts of dust events on chemical characterization and associated source contributions of atmospheric particulate matter in northern China - Ruiyu Li; Miao Zhang; Yuming Du; Guixia Wang; Chunlin Shang; Yao Liu; Min Zhang; Qingpeng Meng; Min Cui; Caiqing Yan (Environmental Pollution, 2023)

High performance carbon dioxide electroreduction in ionic liquids with in situ shell-isolated nanoparticle-enhanced Raman spectroscopy - Ye Hu; Zhongdong Gan; Shixian Xin; Wenhui Fang; Min Li; Yanlei Wang; Wei Cui; Hong Zhao; Zengxi Li; Xiangping Zhang (Chemical Engineering Journal, 2023)

A feasibility investigation of a pilot-scale bioelectrochemical coupled anaerobic digestion system with centric electrode module for real membrane manufacturing wastewater treatment - Jiawei Xie; Xinyi Zou; Yaofeng Chang; He Liu; Min-Hua Cui; Tian C. Zhang; Jiajian Xi; Chongjun Chen (Bioresource Technology, 2023)

Characterization of carbonaceous matter emitted from residential coal and biomass combustion by experimental simulation - Min Cui; Yuanyuan Xu; Binbin Yu; Caiqing Yan; Jun Li; Mei Zheng; Yingjun Chen (Atmospheric Environment, 2023)

A Feature-Enhanced MPS Approach to Reconstruct 3D Deposit Models Using 2D Geological Cross Sections: A Case Study in the Luodang Cu Deposit, Southwestern China - Gang Liu; Hongfeng Fang; Qiyu Chen; Zhesi Cui; Min Zeng (Natural Resources Research, 2022)

The R2R3-MYB gene CgMYB4 is involved in the regulation of cell differentiation and fiber development in the stamens of Chelone glabra L. - Chunlan Piao; Zhenrui Gao; Siming Yuan; Feifei Li; Min-Long Cui (Protoplasma, 2022)

Urinary concentrations of polycyclic aromatic hydrocarbon and phthalate metabolite mixtures in relation to semen quality among men attending an infertility clinic - Yan-Ling Deng; Pan Yang; Yi-Xin Wang; Chong Liu; Qiong Luo; Tian Shi; Jia-Yue Zeng; Ting-Ting Lu; Pan-Pan Chen; Yu Miao; Min Zhang; Fei-Peng Cui; et al. (Environmental Science and Pollution Research, 2022)

A novel method for fabrication of coated microneedles with homogeneous and controllable drug dosage for transdermal drug delivery - Bo Zhi Chen; Meng Chan He; Xiao Peng Zhang; Wen Min Fei; Yong Cui; Xin Dong Guo (Drug Delivery and Translational Research, 2022)

Paenibacillus hamazuiensis sp. nov., a bacterium isolated from Hamazui hot spring in Yunnan province, south-west China - Juan Wang; Ming Deng; En-Min Zhou; Lei Ran; Cui-Ping Miao; Yi-Qing Li; Jun-Mei Ding; Shu-Kun Tang (Archives of Microbiology, 2022)

SLAH1 is involved in the long-distance transport of Cl− from roots into shoots in the Cl−-tolerant xerophyte Pugionium cornutum under salt stress - Yan-Nong Cui; Xiao-Yu Li; Rui-Wen Liu; Zi-Hua He; Suo-Min Wang; Qing Ma (Plant and Soil, 2022)

Evidence for preserved insulin responsiveness in the aging rat brain - Matthew G. Engel; Jeremy Smith; Kai Mao; Gabriela Farias Quipildor; Min-Hui Cui; Maria Gulinello; Craig A. Branch; Samuel E. Gandy; Derek M. Huffman (GeroScience, 2022)
Insulin appears to exert salutary effects in the central nervous system (CNS). Thus, brain insulin resistance has been proposed to play a role in brain aging and dementia but is conceptually complex and unlikely to fit classic definitions established in peripheral tissues. Thus, we sought to characterize brain insulin responsiveness in young (4–5 months) and old (24 months) FBN male rats using a diverse set of assays to determine the extent to which insulin effects in the CNS are impaired with age. When performing hyperinsulinemic-euglycemic clamps in rats, intracerebroventricular (ICV) infusion of insulin in old animals improved peripheral insulin sensitivity by nearly two-fold over old controls and comparable to young rats, suggesting preservation of this insulin-triggered response in aging per se ( p < 0.05). We next used an imaging-based approach by comparing ICV vehicle versus insulin and performed resting state functional magnetic resonance imaging (rs-fMRI) to evaluate age- and insulin-related changes in network connectivity within the default mode network. In aging, lower connectivity between the mesial temporal (MT) region and other areas, as well as reduced MT signal complexity, was observed in old rats, which correlated with greater cognitive deficits in old. Despite these stark differences, ICV insulin failed to elicit any significant alteration to the BOLD signal in young rats, while a significant deviation of the BOLD signal was observed in older animals, characterized by augmentation in regions of the septal nucleus and hypothalamus, and reduction in thalamus and nucleus accumbens. In contrast, ex vivo stimulation of hippocampus with 10 nM insulin revealed increased Akt activation in young ( p < 0.05), but not old rats. Despite similar circulating levels of insulin and IGF-1, cerebrospinal fluid concentrations of these ligands were reduced with age. Thus, these data highlight the complexity of capturing brain insulin action and demonstrate preserved or heightened brain responses to insulin with age, despite dampened canonical signaling, thereby suggesting impaired CNS input of these ligands may be a feature of reduced brain insulin action, providing further rationale for CNS replacement strategies.

An update on microneedle-based systems for diabetes - Wen Xuan Li; Xiao Peng Zhang; Bo Zhi Chen; Wen Min Fei; Yong Cui; Can Yang Zhang; Xin Dong Guo (Drug Delivery and Translational Research, 2022)

Distribution Characteristics and Ecological Risk Assessment of Heavy Metals in Marine Sediments of Binhai County, Jiangsu Province - Shu Chen; Min Xu; Dandan Cui; Lin Lv; Zaifeng Wang; Baiqiong Liu; Jing Wang (Journal of Marine Science and Engineering, 2022)
In recent years, research on heavy metals has become very popular, because the status of heavy metals can reflect the marine environment of a region. Based on this, this paper carries out the evaluation and analysis of heavy metals in marine sediments. Based on the content of the heavy metals in the coastal sediments of Binhai, Jiangsu, from coastal waters in the autumns of 2012, 2015, and 2018, the environmental quality was quantitatively evaluated using the geoaccumulation index and potential ecological risk. The sources of the heavy metals were identified by a multivariate analysis, and the changes over the years and the distribution characteristics were analyzed. Hg and Cr were at a clean grade, while other heavy metals contents indicated mild-to-moderate pollution in the three sets of monitoring data. The comprehensive ecological risk index assessment showed that Hg and Cd were at a moderate ecological risk level in the three sets of monitoring data. Overall, the study area exhibited a mild-to-moderate ecological risk level, with a continuously increasing trend. The overall content of heavy metal in this sea area is greatly affected by human activities, with high values occurring in ports, estuaries, and outer seas.

Where did Yunnan’s puddling steel technology come from? Preliminary analysis of metallurgical relics unearthed from the Shushi Ancient City Site in Zhaotong, Yunnan Province, China - Guisen Zou; Rui Min; Ranchao Zhou; Jianfeng Cui (Archaeological and Anthropological Sciences, 2022)

RNAi-Based Transcriptome Suggests Candidate Genes Regulated by ZxNHX1 to Affect The Salt Tolerance of Zygophyllum xanthoxylum - Hai-Shuang Liu; Xiao-Nong Guo; Wei-Wei Chai; Rui-Xin Zhang; Pei-Qin Li; Cui-Min Ma; Qing Ma; Suo-Min Wang (Journal of Plant Growth Regulation, 2022)

Correction to: GLP-1 Receptor Agonist Inhibited the Activation of RIPK1 for Alleviation the Neuronal Death and Neuroinfammation in APP/PS1 Mice - Xiaodong Kong; Yuting Yang; Huijie Li; Weiyun Cui; Xiaohui Wu; Min Gong; Ying Li (International Journal of Peptide Research and Therapeutics, 2022)

Microbial composition and nitrogen removal pathways in a novel sequencing batch reactor integrated with semi-fixed biofilm carrier: evidence from a pilot study for low- and high-strength sewage treatment - Peng-fei Chen; Rui-jian Zhang; Zhi-li Du; Guang-hua Wang; Hao-tao Dong; Bin Cui; Ru-pei Fan; Lu-xin Li; Qian-bin Wang; Ying-shi Liu; Zhi-min Sun (Environmental Science and Pollution Research, 2022)

Coupled effects of saline solution and vertical stress on swelling deformation of compacted GMZ bentonite/sand mixtures - Yong-Gui Chen; Yu-Hao Hu; Kan Pan; Wei-Min Ye; Yu-Jun Cui (Bulletin of Engineering Geology and the Environment, 2022)

Genetically encoded redox biosensor system for H2O2 measurement in four subcellular compartments in acute myeloid leukemia (AML) cells - Mengmeng Cui; Ghulam Abbas; Dianbing Wang; Qian Liu; Rui Gong; Min Li; Xian-En Zhang (Science China Life Sciences, 2022)

Cavin-1 promotes M2 macrophages/microglia polarization via SOCS3 - Wei Huang; Yiyi Hong; Wenjing He; Li Jiang; Wen Deng; Biyan Peng; Fen Tang; Chaolan Shen; Qianqian Lan; Hui Huang; Haibin Zhong; Jian Lv; et al. (Inflammation Research, 2022)

Transcriptome Analysis of Pacific White Shrimp (Litopenaeus vannamei) Under Prolonged High-Salinity Stress - Yuquan Li; Yigeng Chen; Yanting Cui; Min Shen; Renjie Wang; Zhongkai Wang (Journal of Ocean University of China, 2022)

Sterols and triterpenoids from Ganoderma lucidum and their reversal activities of tumor multidrug resistance - Min Wu; Cui-e Shen; Qiao-fa Lin; Jin-yi Zhong; Yan-fei Zhou; Ben-chen Liu; Jian-hua Xu; Zhi-qiang Zhang; Peng Li (Natural Product Research, 2022)

Dissolving microneedle rollers for rapid transdermal drug delivery - Xiao Peng Zhang; Bao Li Zhang; Bo Zhi Chen; Ze Qiang Zhao; Wen Min Fei; Yong Cui; Xin Dong Guo (Drug Delivery and Translational Research, 2022)

A Simple Protocol for Thallus Culture-Based Genetic Transformation of the Liverwort Marchantia polymorpha - Dong Hye Seo; Sojung Kim; Hyeon Ji Seo; Seung Eun Lee; Cheol Jin Lim; Hee Woong Yang; Li Hua Cui; Min Yong Ahn; Seong Gwan Yu; Na Hyun Cho; So Young Park; Ji Hee Lee; et al. (Journal of Plant Biology, 2022)

Role of aurora kinase B in regulating resistance to paclitaxel in breast cancer cells - Min Liu; Yinan Li; Cui Zhang; Qing Zhang (Human Cell, 2022)
Aurora kinase B (AURKB) is a type of functional kinase with primary functions of participating in cell mitosis, which has been identified to be involved in the occurrence and development of malignant tumors strongly. However, it still remains a controversial with respect to the relationship between the phosphorylation level of AURKB and its function. In our initial research, there was no significant difference in the relative content of AURKB protein between drug-resistant breast cancer cells and wild-type cells; however, its phosphorylation level in drug-resistant cells was significantly higher than that in wild-type cells. Subsequent cell and animal experiments both confirmed the positive correlation between AURKB phosphorylation and drug resistance. Furthermore, PRKCE in the upstream was identified to regulate the phosphorylation of AURKB, which promoted the change of spatial localization of AURKB from nucleus to cytoplasm. Accordingly, phosphorylated AURKB reduced the negative regulation of downstream RAB27B transcription physically, and interacted with RAB27B in cytoplasm to maintain its protein stability. Eventually, it promoted exosome secretion of drug-resistant cells and drug efflux. Using shRNA to knockdown AURKB expression, using hesperadin to inhibit AURKB activity, mutating the AURKB phosphorylation site, or using siRNA as well as BIM to inhibit the activity of the upstream AURKB phosphorylation regulatory protein PRKCE, all of which directly or indirectly reduce AURKB phosphorylation, are effective in reversing PTX resistance in cells. Collectively, this study provides experimental evidence for PRKCE/AURKB/RAB27B axis in regulating the resistance to paclitaxel (PTX) in breast cancer cells, offering a potential intervention target for reversing drug resistance.

DAL-1/4.1B promotes the uptake of exosomes in lung cancer cells via Heparan Sulfate Proteoglycan 2 (HSPG2) - Shuai Zhang; Min Guo; Tingting Guo; Mingyan Yang; Jiaqi Cheng; Chenyang Cui; Jie Kang; Jiajia Wang; Yuanru Nian; Wenjie Ma; Haibin Weng; Haibo Weng (Molecular and Cellular Biochemistry, 2022)

Circular RNA hsa_circ_0001598 promotes programmed death-ligand-1-mediated immune escape and trastuzumab resistance via sponging miR-1184 in breast cancer cells - Li Huang; Jing Ma; Min Cui (Immunologic Research, 2021)

Induced production of a new polyketide in Penicillium sp. HS-11 by chemical epigenetic manipulation - You-Min Ying; Ling Li; Hang-Fei Yu; Yi-Lian Xu; Lu Huang; Wei Mao; Cui-Ping Tong; Zhi-Dong Zhang; Zha-Jun Zhan; Yun Zhang (Natural Product Research, 2021)

Field test research on post-grouting effect for super-long cast-in-place bored pile in thick soft foundation - Yun-liang Cui; Chang-guang Qi; Jin-hui Zheng; Xin-quan Wang; Shi-min Zhang (Geotechnical and Geological Engineering, 2021)

Transient silencing of VvCSN5 enhances powdery mildew resistance in grapevine (Vitis vinifera) - Kai-Cheng Cui; Min Liu; Gui-Hua Ke; Xing-Yuan Zhang; Bo Mu; Min Zhou; Yang Hu; Ying-Qiang Wen (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

GLP-1 Receptor Agonist Inhibited the Activation of RIPK1 for Alleviation the Neuronal Death and Neuroinflammation in APP/PS1 Mice - Xiaodong Kong; Yuting Yang; Huijie Li; Weiyun Cui; Xiaohui Wu; Min Gong; Ying Li (International Journal of Peptide Research and Therapeutics, 2021)

Complex analysis of the personalized pharmacotherapy in the management of COVID-19 patients and suggestions for applications of predictive, preventive, and personalized medicine attitude - Lei-Yun Wang; Jia-Jia Cui; Qian-Ying OuYang; Yan Zhan; Yi-Min Wang; Xiang-Yang Xu; Lu-Lu Yu; Hui Yin; Yang Wang; Chen-Hui Luo; Cheng-Xian Guo; Ji-Ye Yin (EPMA Journal, 2021)
Aims Coronavirus disease 2019 (COVID-19) is rapidly spreading worldwide. Drug therapy is one of the major treatments, but contradictory results of clinical trials have been reported among different individuals. Furthermore, comprehensive analysis of personalized pharmacotherapy is still lacking. In this study, analyses were performed on 47 well-characterized COVID-19 drugs used in the personalized treatment of COVID-19. Methods Clinical trials with published results of drugs use for COVID-19 treatment were collected to evaluate drug efficacy. Drug-to-Drug Interactions (DDIs) were summarized and classified. Functional variations in actionable pharmacogenes were collected and systematically analysed. “Gene Score” and “Drug Score” were defined and calculated to systematically analyse ethnicity-based genetic differences, which are important for the safer use of COVID-19 drugs. Results Our results indicated that four antiviral agents (ritonavir, darunavir, daclatasvir and sofosbuvir) and three immune regulators (budesonide, colchicine and prednisone) as well as heparin and enalapril could generate the highest number of DDIs with common concomitantly utilized drugs. Eight drugs (ritonavir, daclatasvir, sofosbuvir, ribavirin, interferon alpha-2b, chloroquine, hydroxychloroquine (HCQ) and ceftriaxone had actionable pharmacogenomics (PGx) biomarkers among all ethnic groups. Fourteen drugs (ritonavir, daclatasvir, prednisone, dexamethasone, ribavirin, HCQ, ceftriaxone, zinc, interferon beta-1a, remdesivir, levofloxacin, lopinavir, human immunoglobulin G and losartan) showed significantly different pharmacogenomic characteristics in relation to the ethnic origin of the patient. Conclusion We recommend that particularly for patients with comorbidities to avoid serious DDIs, the predictive, preventive, and personalized medicine (PPPM, 3 PM) strategies have to be applied for COVID-19 treatment, and genetic tests should be performed for drugs with actionable pharmacogenes, especially in some ethnic groups with a higher frequency of functional variations, as our analysis showed. We also suggest that drugs associated with higher ethnic genetic differences should be given priority in future pharmacogenetic studies for COVID-19 management. To facilitate translation of our results into clinical practice, an approach conform with PPPM/3 PM principles was suggested. In summary, the proposed PPPM/3 PM attitude should be obligatory considered for the overall COVID-19 management.

Maricaulis alexandrii sp. nov., a novel active bioflocculants-bearing and dimorphic prosthecate bacterium isolated from marine phycosphere - Xiao-ling Zhang; Min Qi; Qiu-hong Li; Zhen-dong Cui; Qiao Yang (Antonie van Leeuwenhoek, 2021)

OsPUB41, a U-box E3 ubiquitin ligase, acts as a negative regulator of drought stress response in rice (Oryza Sativa L.) - Dong Hye Seo; Andosung Lee; Seong Gwan Yu; Li Hua Cui; Hye Jo Min; Seung Eun Lee; Na Hyun Cho; Sojung Kim; Hansol Bae; Woo Taek Kim (Plant Molecular Biology, 2021)

Ziziphus jujuba Mill., a plant used as medicinal food: a review of its phytochemistry, pharmacology, quality control and future research - Shi-Jun Liu; Yan-Ping Lv; Zhi-Shu Tang; Yu Zhang; Hong-Bo Xu; Dong-Bo Zhang; Chun-Li Cui; Hong-Bo Liu; Huan-Huan Sun; Zhong-Xing Song; Si-Min Wei (Phytochemistry Reviews, 2021)

Sources of 24-h personal exposure to PM2.5-bound metals: results from a panel study in Wuhan, China - Xing Wang; Bin Wang; Lili Xiao; Xiuqing Cui; Xingzu Cen; Shijie Yang; Ge Mu; Tao Xu; Min Zhou; Weihong Chen (Environmental Science and Pollution Research, 2021)

DAU-Net: a novel water areas segmentation structure for remote sensing image - Min Xia; Yichen Cui; Yonghong Zhang; Yiming Xu; Jia Liu; Yiqing Xu (International Journal of Remote Sensing, 2021)

Correlation between single-nucleotide polymorphisms and statin-induced myopathy: a mixed-effects model meta-analysis - Qian Xiang; Xiao-Dan Zhang; Guang-Yan Mu; Zhe Wang; Zhi-Yan Liu; Qiu-Fen Xie; Kun Hu; Zhuo Zhang; Ling-Yue Ma; Jie Jiang; Yi-Min Cui (European Journal of Clinical Pharmacology, 2021)

A modified rock mass classification considering seismic effects in the basic quality (BQ) system - Zhen Cui; Qian Sheng; Gui-min Zhang; Hua Liu (Bulletin of Engineering Geology and the Environment, 2021)

Quantitatively determine the dominant driving factors of the spatial—temporal changes of vegetation NPP in the Hengduan Mountain area during 2000–2015 - Shu-ting Chen; Bing Guo; Rui Zhang; Wen-qian Zang; Cui-xia Wei; Hong-wei Wu; Xiao Yang; Xiao-yan Zhen; Xing Li; Da-fu Zhang; Bao-min Han; Hai-ling Zhang (Journal of Mountain Science, 2021)

HIV-1 viral cores enter the nucleus collectively through the nuclear endocytosis-like pathway - Xia Li; Dianbing Wang; Zongqiang Cui; Qin Li; Min Li; Yingxin Ma; Qinxue Hu; Yikai Zhou; Xian-En Zhang (Science China Life Sciences, 2021)

Geographical and interspecific variation in susceptibility of three common thrips species to the insecticide, spinetoram - Yong-Fu Gao; Ya-Jun Gong; Li-Jun Cao; Jin-Cui Chen; Yu-Lin Gao; Majid Mirab-balou; Min Chen; Ary A. Hoffmann; Shu-Jun Wei (Journal of Pest Science, 2021)

Groundwater resources survey of tongchuan city using the audio magnetotelluric method - Zhi-min Xu; Jing-tian Tang; Guang Li; Hui-Cui Xin; Zhang-jian Xu; Xin-ping Tan; Jin Li (Applied Geophysics, 2020)

Fasudil attenuates glial cell-mediated neuroinflammation via ERK1/2 and AKT signaling pathways after optic nerve crush - Wei Huang; Qianqian Lan; Li Jiang; Wenya Yan; Fen Tang; Chaolan Shen; Hui Huang; Haibin Zhong; Jian Lv; Siming Zeng; Min Li; Zhongxiang Mo; et al. (Molecular Biology Reports, 2020)

Kinetic study on the sorption and degradation of antibiotics in the estuarine water: an evaluation based on single and multiple reactions - Jia Li; Min Cui (Environmental Science and Pollution Research, 2020)

Exploring slope spatial heterogeneity by nitrogen transfer and arbuscular mycorrhizal community - Yanyan Yu; Lu Zhao; Min Cui; Yutong Xiao; Cong Wang; Yuan Miao; Zhijie Chen; Yanhong Cao; Junqiang Zheng; Shijie Han (Journal of Soils and Sediments, 2020)

Characterization and Genome Analysis of a Novel Marine Alteromonas Phage P24 - Xinran Zhang; Yundan Liu; Min Wang; Meiwen Wang; Tong Jiang; Jianhua Sun; Chen Gao; Yong Jiang; Cui Guo; Hongbing Shao; Yantao Liang; Andrew McMinn (Current Microbiology, 2020)

Brain interstitial fluid drainage and extracellular space affected by inhalational isoflurane: in comparison with intravenous sedative dexmedetomidine and pentobarbital sodium - Guomei Zhao; Hongbin Han; Jun Yang; Min Sun; Dehua Cui; Yuanyuan Li; Yajuan Gao; Jing Zou (Science China Life Sciences, 2020)

Isolation and Complete Genome Sequence of a Novel Cyanophage S-B68 - Liyang Huang; Qian Liu; Xinxin Liu; Qi Wang; Qiannan Zhao; Min Wang; Hongbing Shao; Cui Guo; Yantao Liang; Yong Jiang (Current Microbiology, 2020)

Pharmacokinetics and Tolerability of the Novel Non-immunosuppressive Fingolimod Derivative, OSU-2S, in Dogs and Comparisons with Data in Mice and Rats - Zhiliang Xie; Min Chen; Swagata Goswami; Rajes Mani; Dasheng Wang; Samuel K. Kulp; Chris C. Coss; Larry J. Schaaf; Fengyu Cui; John C. Byrd; Ryan N. Jennings; Karsten K. Schober; et al. (The AAPS Journal, 2020)

Development of a serological procedure for sensitive and rapid detection of Thladiantha dubia mosaic virus - Na Zhao; Yanmei Miao; Ning Wang; Jia Liu; Jianmin Cong; Qinghui Wei; Jueyu Wang; Daizong Cui; Min Zhao (European Journal of Plant Pathology, 2020)

The sorption performance of corroded Gaomiaozi bentonite by evolved cement water at different temperatures: the case of europium removal - Zhao Sun; Yong-gui Chen; Yinghui Shang; Yu-jun Cui; Wei-min Ye; Dong-bei Wu (Environmental Science and Pollution Research, 2020)

Spatial and temporal variations of antibiotics in a tidal river - Jia Li; Min Cui; Hua Zhang (Environmental Monitoring and Assessment, 2020)

Isolation and complete genome sequence of a novel cyanophage, S-B05, infecting an estuarine Synechococcus strain: insights into environmental adaptation - Tong Jiang; Cui Guo; Min Wang; Meiwen Wang; Siyuan You; Yundan Liu; Xinran Zhang; Hongbin Liu; Yong Jiang; Hongbing Shao; Yantao Liang; Andrew McMinn (Archives of Virology, 2020)

The nucleic acid positive rate and genotype distribution of human cytomegalovirus in human milk banks in China - Xiaoyu Min; Lin Wang; Aili Cui; Chunli Zhang; Dan Wang; Ying Liu; Zhenghong Li; Wenbo Xu (Archives of Virology, 2020)

SsHKT1;1 is coordinated with SsSOS1 and SsNHX1 to regulate Na+ homeostasis in Suaeda salsa under saline conditions - Wen-Ying Wang; Ya-Qi Liu; Hui-Rong Duan; Xiu-Xia Yin; Yan-Nong Cui; Wei-Wei Chai; Xin Song; Timothy J. Flowers; Suo-Min Wang (Plant and Soil, 2020)

Towards Understanding the Mechanism of Heavy Metals Immobilization in Biochar Derived from Co-pyrolysis of Sawdust and Sewage Sludge - Yan-Qin Yang; Min-Hua Cui; Yi-Gang Ren; Jian-Chao Guo; Zhi-Yong Zheng; He Liu (Bulletin of Environmental Contamination and Toxicology, 2020)

Aliphatic suberin confers salt tolerance to Arabidopsis by limiting Na+ influx, K+ efflux and water backflow - Pei Wang; Chun-Mei Wang; Li Gao; Yan-Nong Cui; Hai-Li Yang; Nayana D. G. de Silva; Qing Ma; Ai-Ke Bao; Timothy J. Flowers; Owen Rowland; Suo-Min Wang (Plant and Soil, 2020)

Safety, pharmacokinetic and pharmacodynamic properties of single ascending dose and continuous infusion of remimazolam besylate in healthy Chinese volunteers - Xiao-yan Sheng; Yan Liang; Xue-yuan Yang; Li-e Li; Xia Ye; Xia Zhao; Yi-min Cui (European Journal of Clinical Pharmacology, 2020)

Rapid detection of Anguina agrostis by loop-mediated isothermal amplification - Lu-zhen Yu; Shao-yi Song; Cui Yu; Bin-bin Jiao; Yi-min Tian; You-jun Li (European Journal of Plant Pathology, 2020)

Multi-scale and multi-component digital core construction and elastic property simulation - Li-Kai Cui; Jian-Meng Sun; Wei-Chao Yan; Huai-Min Dong (Applied Geophysics, 2020)

A practicable method to prepare nitrated proteins with peroxynitrite and low concentration of sodium hydroxide - Nan Zhang; Xiaochen Gao; Weijia Zhang; Doaa Higazy; Ke Wang; Zhenfang Fu; Min Cui (Molecular Biology Reports, 2020)

The expression and role of PIDD in retina after optic nerve crush - Fen Tang; Fan Xu; Ling Cui; Wei Huang; Li Jiang; Lifei Chen; Wenya Yan; Wenjing He; Chaolan Shen; Hui Huang; Jian Lv; Xin Zhao; et al. (Journal of Molecular Histology, 2020)

Acute response of Pacific white shrimp Litopenaeus vannamei to high-salinity reductions in osmosis-, metabolism-, and immune-related enzyme activities - Min Shen; Yanting Cui; Renjie Wang; Tiantian Dong; Haibin Ye; Shusheng Wang; Ranghui Fu; Yuquan Li (Aquaculture International, 2020)

Genome Analysis of Two Novel Lytic Vibrio maritimus Phages Isolated from the Coastal Surface Seawater of Qingdao, China - Yuye Han; Min Wang; Qian Liu; Yundan Liu; Qi Wang; Xueping Duan; Lu Liu; Yong Jiang; Hongbing Shao; Cui Guo (Current Microbiology, 2019)

iTRAQ-based analysis of 17β-estradiol induced proteome in Chinese tongue sole Cynoglossus semilaevis - Ying Zhu; Yangzhen Li; Hailong Li; Lei Wang; Ning Zhang; Yang Liu; Liang Meng; Xiwen Xu; Zhongdian Dong; Min Wei; Hua Guo; Zhongkai Cui; et al. (Journal of Oceanology and Limnology, 2019)

Layer regrouping optimization for multilayer heterogeneous reservoirs at a high water cut stage - Wu Zhongwei; Cui Chuanzhi; Japan Trivedi; Li Rongtao; Tang Wenhao; Wei Zijian; Gao Min (Arabian Journal of Geosciences, 2019)

Differential PCR detection of Streptococcus agalactiae and Streptococcus iniae in tilapia ( Oreochromis niloticus ) by a single primer pair - Miao Cui; Huijie Zhang; Jingjing Li; Ru Liu; Min Wu; Delin Xu; Qizhong Zhang (Journal of Fish Diseases, 2019)

Iodine Nutrition and Thyroid Function in Pregnant Women Exposed to Different Iodine Sources - Yanting Chen; Wen Chen; Cong Du; Lili Fan; Wei Wang; Min Gao; Yixin Zhang; Tingkai Cui; Yunmeng Hao; Elizabeth N. Pearce; Chongdan Wang; Wanqi Zhang (Biological Trace Element Research, 2019)

Central IGF-1 protects against features of cognitive and sensorimotor decline with aging in male mice - Gabriela E. Farias Quipildor; Kai Mao; Zunju Hu; Ardijana Novaj; Min-Hui Cui; Maria Gulinello; Craig A. Branch; Sriram Gubbi; Khushbu Patel; Douglas R. Moellering; Stefano Tarantini; Tamas Kiss; et al. (GeroScience, 2019)

Selenium Rescues Aflatoxin B1-Inhibited T Cell Subsets and Cytokine Levels in Cecal Tonsil of Chickens - Fengyuan Wang; Zhicai Zuo; Kejie Chen; Xi Peng; Jing Fang; Hengmin Cui; Gang Shu; Min He; Li Tang (Biological Trace Element Research, 2019)

MiR-449a-5p mediates mitochondrial dysfunction and phenotypic transition by targeting Myc in pulmonary arterial smooth muscle cells - Chen Zhang; Cui Ma; Lixin Zhang; Linlin Zhang; Fengying Zhang; Mingfei Ma; Xiaodong Zheng; Min Mao; Tingting Shen; Daling Zhu (Journal of Molecular Medicine, 2019)

Adsorptive Removal of Tetracyclines and Fluoroquinolones Using Yak Dung Biochar - Jun Wu; Jian Lu; Cui Zhang; Zhenhua Zhang; Xiuyun Min (Bulletin of Environmental Contamination and Toxicology, 2019)

Primary molecular basis of androgenic gland endocrine sex regulation revealed by transcriptome analysis in Eriocheir sinensis - Chengwen Song; Lei Liu; Min Hui; Yuan Liu; Hourong Liu; Zhaoxia Cui (Journal of Oceanology and Limnology, 2019)

Insights into the effect of chemical treatment on the physicochemical characteristics and adsorption behavior of pig manure-derived biochars - Rong-Zhong Wang; Dan-Lian Huang; Chen Zhang; Yun-Guo Liu; Guang-Ming Zeng; Cui Lai; Xiao-Min Gong; Min Cheng; Jia Wan; Qing Zhang (Environmental Science and Pollution Research, 2019)

Investigation of early Bronze Age civilizations in Yunnan: a scientific analysis of metallurgical relics found at the Guangfentou ruins in Jiangchuan - Guisen Zou; Jianfeng Cui; Xu Liu; Xiaorui Li; Rui Min (Archaeological and Anthropological Sciences, 2019)

Comparison of diploid and triploid Carassius auratus provides insights into adaptation to environmental change - Li Ren; Xin Gao; Conghui Yang; Hui Tan; Jialin Cui; Shi Wang; Wuhui Li; Chun Zhang; Min Tao; Qinbo Qin; Shaojun Liu (Science China Life Sciences, 2018)

Metal wet deposition in the Three Gorges Reservoir (TGR) region of Southwest China - Min Gao; Jian Cui; Liuyi Zhang; Dongyi He; John Yang; Fengwu Zhou; Qiangmei Leng; Fumo Yang (Environmental Science and Pollution Research, 2018)

Soil sustainable utilization technology: mechanism of flavonols in resistance process of heavy metal - Min Li; Xu Zhang; Huanhuan Yang; Xinxin Li; Zhaojie Cui (Environmental Science and Pollution Research, 2018)

Source apportionment of nitrogen and phosphorus from non-point source pollution in Nansi Lake Basin, China - Bao-lei Zhang; Bo-hao Cui; Shu-min Zhang; Quan-yuan Wu; Lei Yao (Environmental Science and Pollution Research, 2018)

PGC-1α coordinates with Bcl-2 to control the cell cycle in U251 cells through reducing ROS - Kun Yao; Xu-feng Fu; Xing Du; Yan Li; Shan-shan Yang; Min Yu; Qing-hua Cui (Journal of Zhejiang University-SCIENCE B, 2018)

Long-Term Effects of Docosahexaenoic Acid-Bound Phospholipids and the Combination of Docosahexaenoic Acid-Bound Triglyceride and Egg Yolk Phospholipid on Lipid Metabolism in Mice - Hongxia Che; Jie Cui; Min Wen; Jie Xu; Teruyoshi Yanagita; Qi Wang; Changhu Xue; Yuming Wang (Journal of Ocean University of China, 2018)

CD200Fc Attenuates Retinal Glial Responses and RGCs Apoptosis After Optic Nerve Crush by Modulating CD200/CD200R1 Interaction - Rong Huang; Qianqian Lan; Lifei Chen; Haibin Zhong; Ling Cui; Li Jiang; Hui Huang; Li Li; Siming Zeng; Min Li; Xin Zhao; Fan Xu (Journal of Molecular Neuroscience, 2018)

MicroRNA-181c Ameliorates Cognitive Impairment Induced by Chronic Cerebral Hypoperfusion in Rats - Chen Fang; Qian Li; Guowen Min; Min Liu; Jing Cui; Jing Sun; Liang Li (Molecular Neurobiology, 2017)

Interaction of Wip1 and NF-κB regulates neuroinflammatory response in astrocytes - Fan Xu; Lifei Chen; Xin Zhao; Haibin Zhong; Ling Cui; Li Jiang; Hui Huang; Li Li; Siming Zeng; Min Li (Inflammation Research, 2017)

The virulence factor PA protein of highly pathogenic H5N1 avian influenza virus inhibits NF-κB transcription in vitro - Zhu Cui; Jiao Hu; Xiaoquan Wang; Min Gu; Xiaowen Liu; Shunlin Hu; Zenglei Hu; Huimou Liu; Wenbo Liu; Sujuan Chen; Daxin Peng; Xinan Jiao; et al. (Archives of Virology, 2017)

Locus Mapping, Molecular Cloning, and Expression Analysis of rps6kb2, a Novel Metamorphosis-Related Gene in Chinese Tongue Sole (Cynoglossus semilaevis) - Yang Liu; Min Wei; Hua Guo; Changwei Shao; Liang Meng; Wenteng Xu; Na Wang; Lei Wang; Deborah M Power; Jilun Hou; Shahid Mahboob; Zhongkai Cui; et al. (Marine Biotechnology, 2017)

Salidroside Ameliorates Diabetic Neuropathic Pain in Rats by Inhibiting Neuroinflammation - Gui-Lian Ni; Rong Cui; Ai-Min Shao; Zhong-Min Wu (Journal of Molecular Neuroscience, 2017)

Study on the morphology, histology and enzymatic activity of the digestive tract of Gymnocypris eckloni Herzenstein - Lizhu Yang; Jing Fang; Xi Peng; Hengmin Cui; Min He; Zhicai Zuo; Yi Zhou; Zhuangzhi Yang (Fish Physiology and Biochemistry, 2017)

Involvement of the miR-462/731 cluster in hypoxia response in Megalobrama amblycephala - Cui-Hong Huang; Nan Chen; Chun-Xiao Huang; Bao Zhang; Meng Wu; Lei He; Hong Liu; Rong Tang; Wei-Min Wang; Huan-Ling Wang (Fish Physiology and Biochemistry, 2017)

Effects of calcium at toxic concentrations of cadmium in plants - Danlian Huang; Xiaomin Gong; Yunguo Liu; Guangming Zeng; Cui Lai; Hassan Bashir; Lu Zhou; Dafei Wang; Piao Xu; Min Cheng; Jia Wan (Planta, 2017)

Species diversity and molecular systematics of Fibroporia (Polyporales, Basidiomycota) and its related genera - Yuan-Yuan Chen; Fang Wu; Min Wang; Bao-Kai Cui (Mycological Progress, 2017)

RIPK1/RIPK3/MLKL-mediated necroptosis contributes to compression-induced rat nucleus pulposus cells death - Songfeng Chen; Xiao Lv; Binwu Hu; Zengwu Shao; Baichuan Wang; Kaige Ma; Hui Lin; Min Cui (Apoptosis, 2017)

A novel lectin from Artocarpus lingnanensis induces proliferation and Th1/Th2 cytokine secretion through CD45 signaling pathway in human T lymphocytes - Bo Cui; Lu Li; Qiyan Zeng; Faquan Lin; Lijun Yin; Liejun Liao; Min Huang; Jingping Wang (Journal of Natural Medicines, 2017)

Enhanced bioremediation of lead-contaminated soil by Solanum nigrum L. with Mucor circinelloides - Liqun Sun; Xiufeng Cao; Min Li; Xu Zhang; Xinxin Li; Zhaojie Cui (Environmental Science and Pollution Research, 2017)

China is initiating the Aquatic 10-100-1,000 Genomics Program - Yingjie Liu; Pao Xu; Junmin Xu; Yu Huang; Yongxin Liu; Hui Fang; Yinchang Hu; Xinxin You; Chao Bian; Min Sun; Ruobo Gu; Lifeng Cui; et al. (Science China Life Sciences, 2017)

p38 MAPK Participates in the Mediation of GLT-1 Up-regulation During the Induction of Brain Ischemic Tolerance by Cerebral Ischemic Preconditioning - Min Zhang; Jian-Xue Gong; Jia-Lei Wang; Meng-Yang Jiang; Li Li; Yu-Yan Hu; Jie Qi; Ling-Yan Zhang; Hang Zhao; Xin Cui; Xiao-Hui Xian; Wen-Bin Li (Molecular Neurobiology, 2017)

Comparison of the immunogenicity of two inactivated recombinant rabies viruses overexpressing the glycoprotein - Muhammad Tariq Navid; Yingying Li; Ming Zhou; Min Cui; Zhen F. Fu; Lijun Tang; Ling Zhao (Archives of Virology, 2016)

Up-regulation of Wip1 involves in neuroinflammation of retinal astrocytes after optic nerve crush via NF-κB signaling pathway - Haibin Zhong; Ling Cui; Fan Xu; Lifei Chen; Li Jiang; Hui Huang; Jiping Xu; Xin Zhao; Li Li; Siming Zeng; Min Li (Inflammation Research, 2016)

Protective Effects of Extracellular and Intracellular Polysaccharides on Hepatotoxicity by Hericium erinaceus SG-02 - Fangyuan Cui; Xia Gao; Jianjun Zhang; Min Liu; Chen Zhang; Nuo Xu; Huajie Zhao; Lin Lin; Meng Zhou; Le Jia (Current Microbiology, 2016)

Levels, congener profile and inventory of polychlorinated biphenyls in sediment from the Songhua River in the vicinity of cement plant, China: a case study - Song Cui; Qiang Fu; Yi-Fan Li; Wen-long Li; Tian-xiao Li; Min Wang; Zhen-xiang Xing; Lu-ji Zhang (Environmental Science and Pollution Research, 2016)

Taxonomy and multi-gene phylogeny of Haploporus (Polyporales, Basidiomycota) - Lu-Lu Shen; Jia-Jia Chen; Min Wang; Bao-Kai Cui (Mycological Progress, 2016)

Microbial metabolism induced chain shortening of polyacrylamide with assistance of bioelectricity generation - Min Sun; Zhong-Hua Tong; Yu-Zhi Cui; Jun Wang (Environmental Science and Pollution Research, 2016)

Fast Marching and Runge–Kutta Based Method for Centreline Extraction of Right Coronary Artery in Human Patients - Hengfei Cui; Desheng Wang; Min Wan; Jun-Mei Zhang; Xiaodan Zhao; Ru San Tan; Weimin Huang; Wei Xiong; Yuping Duan; Jiayin Zhou; Tong Luo; Ghassan S. Kassab; et al. (Cardiovascular Engineering and Technology, 2016)

Flow cytometric analysis of DNA content for four commercially important crabs in China - Lei Liu; Zhaoxia Cui; Chengwen Song; Yuan Liu; Min Hui; Chunlin Wang (Acta Oceanologica Sinica, 2016)

Factors Associated with Thrombolysis Outcome in Ischemic Stroke Patients with Atrial Fibrillation - Qiuyun Zhao; Xiaobo Li; Wanli Dong; Min Ye; Yongjun Cao; Meijuan Zhang; Qiantao Cheng; Junshan Zhou; Guofang Chen; Ming Yu; Shanshan Hong; Xiue Wei; et al. (Neuroscience Bulletin, 2016)

Alleviating effects of exogenous NO on tomato seedlings under combined Cu and Cd stress - Yi-jun Wang; Yu-Xiu Dong; Juan Wang; Xiu-min Cui (Environmental Science and Pollution Research, 2016)

Sequence Characteristics and Phylogenetic Implications of the nrDNA Internal Transcribed Spacers (ITS) in Protospecies and Landraces of Sugarcane (Saccharum officinarum L.) - Cui-Feng Yang; Li-Tao Yang; Yang-Rui Li; Ge-Min Zhang; Chun-Ya Zhang; Wei-Zan Wang (Sugar Tech, 2016)

PGC-1α regulates the cell cycle through ATP and ROS in CH1 cells - Xu-feng Fu; Kun Yao; Xing Du; Yan Li; Xiu-yu Yang; Min Yu; Mei-zhang Li; Qing-hua Cui (Journal of Zhejiang University-SCIENCE B, 2016)

Phylogeny and taxonomy of the genus Anomoloma (Amylocorticiales, Basidiomycota) - Jie Song; Xue-Ying Liu; Min Wang; Bao-Kai Cui (Mycological Progress, 2016)

Metabolic responses to Lactobacillus plantarum contamination or bacteriophage treatment in Saccharomyces cerevisiae using a GC–MS-based metabolomics approach - Feng-Xia Cui; Rui-Min Zhang; Hua-Qing Liu; Yan-Feng Wang; Hao Li (World Journal of Microbiology and Biotechnology, 2015)

Clinical, biochemical, neuroimaging and molecular findings of X-linked Adrenoleukodystrophy patients in South China - Min-yan Jiang; Yan-na Cai; Cui-li Liang; Min-zhi Peng; Hui-ying Sheng; Li-ping Fan; Rui-zhu Lin; Hua Jiang; Yonglan Huang; Li Liu (Metabolic Brain Disease, 2015)

Synthesis and Application of Modified Zero-Valent Iron Nanoparticles for Removal of Hexavalent Chromium from Wastewater - Dan-Lian Huang; Guo-Min Chen; Guang-Ming Zeng; Piao Xu; Ming Yan; Cui Lai; Chen Zhang; Ning-Jie Li; Min Cheng; Xiao-Xiao He; Yan He (Water, Air, & Soil Pollution, 2015)

Efficacy and tolerability of canagliflozin as add-on to metformin in the treatment of type 2 diabetes mellitus: a meta-analysis - Ting Yang; Min Lu; Lingyue Ma; Ying Zhou; Yimin Cui (European Journal of Clinical Pharmacology, 2015)

Response of extracellular carboxylic and thiol ligands (oxalate, thiol compounds) to Pb2+ stress in Phanerochaete chrysosporium - Ningjie Li; Guangming Zeng; Danlian Huang; Chao Huang; Cui Lai; Zhen Wei; Piao Xu; Chen Zhang; Min Cheng; Ming Yan (Environmental Science and Pollution Research, 2015)

Therapeutic potential of human umbilical cord blood mesenchymal stem cells on erectile function in rats with cavernous nerve injury - Jian-Qiang Zhu; Hong-Kai Lu; Zhi-Qiang Cui; Yong-Chuan Wang; Yong-Hui Li; Weixin Zhao; Qiang Fu; Yue-Min Xu; Yong Xu; Lu-Jie Song (Biotechnology Letters, 2015)

Sulbactam Plays Neuronal Protective Effect Against Brain Ischemia via Upregulating GLT1 in Rats - Xin Cui; Li Li; Yu-Yan Hu; Shuang Ren; Min Zhang; Wen-Bin Li (Molecular Neurobiology, 2015)

A bellow pressure fiber optic sensor for static ice pressure measurements - Li-Qin Cui; Xin Long; Jian-Min Qin (Applied Geophysics, 2015)

Low Bone Mass is Associated with Stroke in Chinese Postmenopausal Women: The Chongqing Osteoporosis Study - Rui Zhou; Dong Liu; Rui Li; Shiming Zhou; Min Cui; Lin Chen; Huadong Zhou (Cell Biochemistry and Biophysics, 2015)

Effect of quinoid redox mediators on the aerobic decolorization of azo dyes by cells and cell extracts from Escherichia coli - Daizong Cui; Guofang Li; Dan Zhao; Min Zhao (Environmental Science and Pollution Research, 2015)

Gelsolin: Role of a Functional Protein in Mitigating Radiation Injury - Mingjuan Li; Fengmei Cui; Ying Cheng; Ling Han; Jia Wang; Ding Sun; Yu-long Liu; Ping-kun Zhou; Rui Min (Cell Biochemistry and Biophysics, 2015)

A Combinatorial Yeast Overlay Method for the Isolation of Antibacterial Oligopeptides - Ran He; Liang Cui; Yan Cao; Zhixue Wang; Kai Wang; Min Fu; Shaoyun Song; Chuanfu Dong; Xiaoxuan Wu; Ye Gao; Xiaoxiao Zhang; Fan Feng; et al. (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2014)

TRAF4 participates in Wnt/β-catenin signaling in breast cancer by upregulating β-catenin and mediating its translocation to the nucleus - Ailian Wang; Jian Wang; Huanyan Ren; Fan Yang; Lili Sun; Kexin Diao; Zhijuan Zhao; Min Song; Zeshi Cui; Enhua Wang; Minjie Wei; Xiaoyi Mi (Molecular and Cellular Biochemistry, 2014)

Cassiterite LA-MC-ICP-MS U/Pb and muscovite 40Ar/39Ar dating of tin deposits in the Tengchong-Lianghe tin district, NW Yunnan, China - Xiao-Cui Chen; Rui-Zhong Hu; Xian-Wu Bi; Hui-Min Li; Jiang-Bo Lan; Cheng-Hai Zhao; Jing-Jing Zhu (Mineralium Deposita, 2014)

Effects of dietary sea cucumber saponin on the gene expression rhythm involved in circadian clock and lipid metabolism in mice during nighttime-feeding - Min Wen; Jie Cui; Jie Xu; Yong Xue; Jingfeng Wang; Changhu Xue; Yuming Wang (Journal of Physiology and Biochemistry, 2014)

Increased accumulation of the cardio-cerebrovascular disease treatment drug tanshinone in Salvia miltiorrhiza hairy roots by the enzymes 3-hydroxy-3-methylglutaryl CoA reductase and 1-deoxy-d-xylulose 5-phosphate reductoisomerase - Min Shi; Xiuqin Luo; Guanhua Ju; Xiaohong Yu; Xiaolong Hao; Qiang Huang; Jianbo Xiao; Lijie Cui; Guoyin Kai (Functional & Integrative Genomics, 2014)

RETRACTED ARTICLE: Further Pieces of Evidence to the Pulmonary Origin of Sevoflurane Escaping to the Operating Room During General Anaesthesia - Zhanhong Xu; Min Dong; Ran Dong; Shuyan Li; Shangjin Cui (Cell Biochemistry and Biophysics, 2014)

Estimation of chlorophyll- a concentration in coastal waters with HJ-1A HSI data using a three-band bio-optical model and validation - Haijing Tian; Chunxiang Cao; Min Xu; Zaichun Zhu; Di Liu; Xiaoqin Wang; Shenghui Cui (International Journal of Remote Sensing, 2014)

Platelet-derived growth factor-BB induces matrix metalloproteinase-2 expression and rat vascular smooth muscle cell migration via ROCK and ERK/p38 MAPK pathways - Ying Cui; Yin-Wei Sun; Hai-Shuang Lin; Wei-Min Su; Yan Fang; Ying Zhao; Xiao-Qing Wei; Yuan-Hua Qin; Kazuhiro Kohama; Ying Gao (Molecular and Cellular Biochemistry, 2014)

Expression of TGF-β1, SNAI1 and MMP-9 is associated with lymph node metastasis in papillary thyroid carcinoma - Ni Wang; Rong Jiang; Jun-Yan Yang; Cui Tang; Lei Yang; Man Xu; Qi-Feng Jiang; Zhi-Min Liu (Journal of Molecular Histology, 2014)

Differences in transmissibility and pathogenicity of reassortants between H9N2 and 2009 pandemic H1N1 influenza A viruses from humans and swine - Liang He; Qiwen Wu; Kaijun Jiang; Zhiqiang Duan; Jingjing Liu; Haixu Xu; Zhu Cui; Min Gu; Xiaoquan Wang; Xiaowen Liu; Xiufan Liu (Archives of Virology, 2014)

Comparison of complete genome sequences of dog rabies viruses isolated from China and Mexico reveals key amino acid changes that may be associated with virus replication and virulence - Fulai Yu; Guoqing Zhang; Xiangfu Zhong; Na Han; Yunfeng Song; Ling Zhao; Min Cui; Simon Rayner; Zhen F. Fu (Archives of Virology, 2014)

Prevalence of human papillomavirus infection in esophageal and cervical cancers in the high incidence area for the two diseases from 2007 to 2009 in Linzhou of Henan Province, Northern China - Hong Yan Liu; Sheng Li Zhou; Jian Wei Ku; Dong Yun Zhang; Bei Li; Xue Na Han; Zong Min Fan; Ji Li Cui; Hong Li Lin; Er Tao Guo; Xi Chen; Yuan Yuan; et al. (Archives of Virology, 2014)

Application of T-DNA activation tagging to identify glutamate receptor-like genes that enhance drought tolerance in plants - Guihua Lu; Xiping Wang; Junhua Liu; Kun Yu; Yang Gao; Haiyan Liu; Changgui Wang; Wei Wang; Guokui Wang; Min Liu; Guanfan Mao; Binfeng Li; et al. (Plant Cell Reports, 2014)

Differential immune response of mallard duck peripheral blood mononuclear cells to two highly pathogenic avian influenza H5N1 viruses with distinct pathogenicity in mallard ducks - Zhu Cui; Jiao Hu; Liang He; Qunhui Li; Min Gu; Xiaoquan Wang; Shunlin Hu; Huimou Liu; Wenbo Liu; Xiaowen Liu; Xiufan Liu (Archives of Virology, 2014)

Natural antisense transcripts of UL123 packaged in human cytomegalovirus virions - Cui-Qing Yang; Ling-Feng Miao; Xing Pan; Cong-Cong Wu; Simon Rayner; Edward S. Mocarski; Han-Qing Ye; Min-Hua Luo (Archives of Virology, 2014)

Full-length sequence analysis of hepatitis E virus isolates: showing potential determinants of virus genotype and identity - Dong Yang; Mei Jiang; Min Jin; Zhigang Qiu; Weihong Cui; Zhiqiang Shen; Bo Li; Lianfeng Gong; Zhaoli Chen; Xinwei Wang; Jun-Wen Li (Virus Genes, 2013)

Influence of HbA1c on short-term blood pressure variability in type 2 diabetic patients with diabetic nephropathy - Fang Liu; Min Wu; Yan-huan Feng; Hui Zhong; Tian-lei Cui; You-qun Huang; Ya-ping Liang; Yong-shu Diao; Li Zang; Ling Li; Jing Zang; Hong-yu Qiu; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Association of Endothelin-converting Enzyme-1b C-338A Polymorphism with Increased Risk of Ischemic Stroke in Chinese Han Population - Rui Li; Min Cui; Jin Zhao; Mingming Yu; Zegang Ying; Shiming Zhou; Huadong Zhou (Journal of Molecular Neuroscience, 2013)

Vitexin protects against cardiac hypertrophy via inhibiting calcineurin and CaMKII signaling pathways - Cui-cui Lu; Ying-qi Xu; Ji-chao Wu; Peng-zhou Hang; Yan Wang; Chen Wang; Jian-wei Wu; Jian-cui Qi; Yong Zhang; Zhi-min Du (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Factors underlying the association of body mass index with serum ALT in Chinese hypertensive adults without known hepatic diseases - Yan Zhang; Xian-hui Qin; Jian-ping Li; Yi-min Cui; Ze-yuan Liu; Zhi-gang Zhao; Jun-bo Ge; De-ming Guan; Jian Hu; Yan-ni Wang; Fu-min Zhang; Xin Xu; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

QTL mapping and correlation analysis for 1000-grain weight and percentage of grains with chalkiness in rice - JIAN-MIN BIAN; HUAN SHI; CUI-JUAN LI; CHANG-LAN ZHU; QIU-YING YU; XIAO-SONG PENG; JUN-RU FU; XIAO-PENG HE; XIAO-RONG CHEN; LI-FANG HU; LIN-JUAN OUYANG; HAO-HUA HE (Journal of Genetics, 2013)

Verapamil reverses cardiac iron overload in streptozocin-induced diabetic rats - Hong-li Shan; Yan Wang; Jian-wei Wu; Peng-zhou Hang; Xin Li; Li-hua Sun; Jian-cui Qi; Yu-ying Mao; Zhi-dan Sun; Zhi-min Du (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Bioconversion of ginsenoside Rc into Rd by a novel α-l-arabinofuranosidase, Abf22-3 from Leuconostoc sp. 22-3: cloning, expression, and enzyme characterization - Qing-Mei Liu; Hae-Min Jung; Chang-Hao Cui; Bong-Hyun Sung; Jin-Kwang Kim; Song-Gun Kim; Sung-Taik Lee; Sun-Chang Kim; Wan-Taek Im (Antonie van Leeuwenhoek, 2013)

Serum microRNA expression profile as a biomarker for the diagnosis of pertussis - Yiyue Ge; Kangchen Zhao; Yuhua Qi; Xiaoyan Min; Zhiyang Shi; Xian Qi; Yunfeng Shan; Lan Cui; Minghao Zhou; Yong Wang; Hua Wang; Lunbiao Cui (Molecular Biology Reports, 2013)

Oncogenic CUL4A determines the response to thalidomide treatment in prostate cancer - Shancheng Ren; Chuanliang Xu; Zilian Cui; Yongwei Yu; Weidong Xu; Fubo Wang; Ji Lu; Min Wei; Xin Lu; Xu Gao; You Liang; Jian-Hua Mao; et al. (Journal of Molecular Medicine, 2012)

Beta2-Adrenergic Receptor and Astrocyte Glucose Metabolism - Jun-hong Dong; Xin Chen; Min Cui; Xiao Yu; Qi Pang; Jin-peng Sun (Journal of Molecular Neuroscience, 2012)

Association of Metals and Proteasome Activity in Erythrocytes of Prostate Cancer Patients and Controls - Christine Neslund-Dudas; Bharati Mitra; Ashoka Kandegedara; Di Chen; Sara Schmitt; Min Shen; Qiuzhi Cui; Benjamin A. Rybicki; Q. Ping Dou (Biological Trace Element Research, 2012)

Satellite monitoring of massive green macroalgae bloom (GMB): imaging ability comparison of multi-source data and drifting velocity estimation - Ting-Wei Cui; Jie Zhang; Li-E Sun; Yong-Jun Jia; Wenjing Zhao; Zong-Ling Wang; Jun-Min Meng (International Journal of Remote Sensing, 2012)

Detection of Autoantibodies and Increased Concentrations of Interleukins in Plasma from Patients with Tourette's Syndrome - Yu-hang Cheng; Yi Zheng; Fan He; Jian-hong Yang; Wen-biao Li; Min-ling Wang; De-yan Cui; Ying Chen (Journal of Molecular Neuroscience, 2012)

Identification and Binding Characterization of Three Odorant Binding Proteins and One Chemosensory Protein from Apolygus lucorum (Meyer-Dur) - Jin-Feng Hua; Shuai Zhang; Jin-Jie Cui; Dao-Jie Wang; Chun-Yi Wang; Jun-Yu Luo; Li-Min Lv (Journal of Chemical Ecology, 2012)

Effects of hydroxypropyl-β-cyclodextrin on the growth and morphology of Absidia coerulea - Lanyu Cui; Yanbing Shen; Xiaodong Guo; Yizhong Wang; Yu Zheng; Jianmei Luo; Min Wang (World Journal of Microbiology and Biotechnology, 2012)

Remediation of saturated Shanghai sandy silt contaminated with p-xylene using air sparging - Yong-Gui Chen; Wei-Min Ye; Zi-Jun Xie; Bao Chen; Yu-Jun Cui (Natural Hazards, 2012)

Statin use and risk of pancreatic cancer: a meta-analysis - Xiaobing Cui; Yue Xie; Min Chen; Jun Li; Xiaoming Liao; Jian Shen; Meng Shi; Wenjing Li; Haoxuan Zheng; Bo Jiang (Cancer Causes & Control, 2012)

Molybdenum improves antioxidant and osmotic-adjustment ability against salt stress in Chinese cabbage (Brassica campestris L. ssp. Pekinensis) - Mu Zhang; Chengxiao Hu; Xiaohu Zhao; Qiling Tan; Xuecheng Sun; Anyong Cao; Min Cui; Ying Zhang (Plant and Soil, 2012)

Use of the Cre-loxP recombination system as an estimate for Agrobacterium-mediated co-transformation of tobacco leaves - Min-Ting Liang; Cui-Ping Yang; Zhi-Ping Xie; Christian Staehelin (Biotechnology Letters, 2012)

Physiological responses to salt stress of T2 alfalfa progenies carrying a transgene for betaine aldehyde dehydrogenase - Li-Ping Yan; Cui-Lan Liu; Hui-Min Liang; Xiu-Hong Mao; Fei Wang; Cai-Hong Pang; Jing Shu; Yang Xia (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

A Promising CdSe@CdS-Quantum Dots-Cysteine for the Determination of Trace IgE by Solid Substrate Room Temperature Phosphorescence Immunoassay - Jia-Ming Liu; Li-ping Lin; Zhen-Bo Liu; Min-Lan Yang; Xin-xing Wang; Li-hong Zhang; Ma-lin Cui; Li Jiao (Journal of Fluorescence, 2012)

The Effect of Dietary Vanadium on Cell Cycle and Apoptosis of Liver in Broilers - Xiaodong Liu; Heng-min Cui; Xi Peng; Jing Fang; Wei Cui; Bangyuan Wu (Biological Trace Element Research, 2011)

Evaluation of suitable reference genes for gene expression studies in Lycoris longituba - SHAO JIE CUI; QIU LING HE; YING CHEN; MIN REN HUANG (Journal of Genetics, 2011)

Production of glutamine synthetase in Escherichia coli using SUMO fusion partner and application to l-glutamine synthesis - Qi Wang; Cui Min; Tingting Yan; Hefang Pu; Yinqiang Xin; Shuangquan Zhang; Lan Luo; Zhimin Yin (World Journal of Microbiology and Biotechnology, 2011)

Single nucleotide polymorphism of CACNA2D1 gene and its association with milk somatic cell score in cattle - Zheng Rong Yuan; Jiao Li; Li Liu; Lu Pei Zhang; Li Min Zhang; Cui Chen; Xiao Jie Chen; Xue Gao; Jun Ya Li; Jin Bao Chen; Hui Jiang Gao; Shang Zhong Xu (Molecular Biology Reports, 2011)

Effect of Dietary High Molybdenum on the Cell Cycle and Apoptosis of Kidney in Broilers - Jie Xiao; Heng-min Cui; Fan Yang; Xi Peng; Yun Cui (Biological Trace Element Research, 2011)

Holes in Progressively Thinning Arctic Sea Ice Lead to New Ice Algae Habitat - Sang Heon Lee; C. Peter McRoy; Hyoung Min Joo; Rolf Gradinger; Huehua Cui; Mi Sun Yun; Kyung Ho Chung; Sung-Ho Kang; Chang-Keun Kang; Eun Jung Choy; SeungHyun Son; Eddy Carmack; et al. (Oceanography, 2011)

Low Dietary Selenium Induce Increased Apoptotic Thymic Cells and Alter Peripheral Blood T Cell Subsets in Chicken - Xi Peng; Heng-min Cui; Junliang Deng; Zhicai Zuo; Wei Cui (Biological Trace Element Research, 2011)

Effective mitigation of nitrate leaching and nitrous oxide emissions in intensive vegetable production systems using a nitrification inhibitor, dicyandiamide - Min Cui; Xuecheng Sun; Chengxiao Hu; Hong J. Di; Qiling Tan; Changsheng Zhao (Journal of Soils and Sediments, 2011)

Effect of Vanadium on the Subset and Proliferation of Peripheral Blood T Cells, and Serum Interleukin-2 Content in Broilers - Wei Cui; Heng-min Cui; Xi Peng; Zhicai Zuo; Xiaodong Liu; Bangyuan Wu (Biological Trace Element Research, 2011)

Production of Bioactive γ-Glutamyl Transpeptidase in Escherichia coli Using SUMO Fusion Partner and Application of the Recombinant Enzyme to l-Theanine Synthesis - Qi Wang; Cui Min; Fenfen Zhu; Yinqiang Xin; Shuangquan Zhang; Lan Luo; Zhimin Yin (Current Microbiology, 2011)

P38-Nrf-2 Signaling Pathway of Oxidative Stress in Mice Caused by Nanoparticulate TiO2 - Jue Wang; Na Li; Lei Zheng; Sisi Wang; Ying Wang; Xiaoyang Zhao; Yanmei Duan; Yaling Cui; Min Zhou; Jingwei Cai; Songjie Gong; Han Wang; et al. (Biological Trace Element Research, 2011)

Effects of nitrogen form on growth, CO2 assimilation, chlorophyll fluorescence, and photosynthetic electron allocation in cucumber and rice plants - Yan-hong Zhou; Yi-li Zhang; Xue-min Wang; Jin-xia Cui; Xiao-jian Xia; Kai Shi; Jing-quan Yu (Journal of Zhejiang University-SCIENCE B, 2011)

Potential application of sludge produced from coal mine drainage treatment for removing Zn(II) in an aqueous phase - Mingcan Cui; Min Jang; Sang-Hyun Cho; Jeehyeong Khim (Environmental Geochemistry and Health, 2011)

Kinetic and mechanism studies of the adsorption of lead onto waste cow bone powder (WCBP) surfaces - Jihoon Cha; Mingcan Cui; Min Jang; Sang-Hyun Cho; Deok Hyun Moon; Jeehyeong Khim (Environmental Geochemistry and Health, 2011)

Effect of High Fluorine on the Cell Cycle and Apoptosis of Renal Cells in Chickens - Caimin Bai; Tao Chen; Yun Cui; Tao Gong; Xi Peng; Heng-min Cui (Biological Trace Element Research, 2010)

Isolation and characterization of polymorphic microsatellite markers in Metasequoia glyptostroboides (Taxodiaceae) - Min-Yan Cui; Shuo Yu; Min Liu; Yuan-Yuan Li (Conservation Genetics Resources, 2010)

Modification of cambial cell wall architecture during cambium periodicity in Populus tomentosa Carr. - Hui-Min Chen; Jia-Jia Han; Ke-Ming Cui; Xin-Qiang He (Trees, 2010)

Effects of glyceollin I on vascular contraction in rat aorta - Min-Ji Song; Inji Baek; Su Bun Jeon; Minchul Seo; Yong-Hoon Kim; Song Cui; Yeon-Shin Jeong; In-Jung Lee; Dong Hyun Shin; Young Hyun Hwang; In Kyeom Kim (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Characteristics and sources of atmospheric polycyclic aromatic hydrocarbons (PAHs) in Shanghai, China - Xian Yu Wang; Qing Bo Li; Yong Ming Luo; Qian Ding; Lian Min Xi; Jian Min Ma; Yan Li; Yi Peng Liu; Cui Li Cheng (Environmental Monitoring and Assessment, 2010)

Development and characterization of microsatellite loci in Ruppia maritima L. (Ruppiaceae) - Shuo Yu; Min-Yan Cui; Bin Liu; Xiao-Yan Wang; Xiao-Yong Chen (Conservation Genetics Resources, 2009)

Fifteen polymorphic microsatellite loci in Wiebesia pumilae (Hill) (Agaonidae) - Min Liu; Xiao-Yan Wang; Min-Yan Cui; Yan Chen (Conservation Genetics Resources, 2009)

Estrogen regulates DNA methyltransferase 3B expression in Ishikawa endometrial adenocarcinoma cells - Min Cui; Zeqing Wen; Zhongli Yang; Ji Chen; Fei Wang (Molecular Biology Reports, 2009)

The effect of root exudates from two transgenic insect-resistant cotton lines on the growth of Fusarium oxysporum - Xiao-gang Li; Biao Liu; Sondre Heia; Dou-dou Liu; Zheng-min Han; Ke-xin Zhou; Jin-jie Cui; Jun-yu Luo; Yang-ping Zheng (Transgenic Research, 2009)

Genetic structure and diversity of cultivated soybean (Glycine max (L.) Merr.) landraces in China - Yinghui Li; Rongxia Guan; Zhangxiong Liu; Yansong Ma; Lixia Wang; Linhai Li; Fanyun Lin; Weijiang Luan; Pengyin Chen; Zhe Yan; Yuan Guan; Li Zhu; et al. (Theoretical and Applied Genetics, 2008)

Synthesis and Luminescent Properties of Lanthanide Complexes with a Novel Multipodal Ligand - Zhen-Zhong Yan; Yu Tang; Wei-Sheng Liu; Hai-Xia Cui; Min-Yu Tan (Journal of Fluorescence, 2008)

Antitumor Effect of Paclitaxel-Loaded PEGylated Immunoliposomes Against Human Breast Cancer Cells - Tao Yang; Min-Koo Choi; Fu-De Cui; Seung-Jin Lee; Suk-Jae Chung; Chang-Koo Shim; Dae-Duk Kim (Pharmaceutical Research, 2007)

The hepatitis B virus protein MHBs(t) sensitizes hepatoma cells to TRAIL-induced apoptosis through ERK2 - Xiaohong Liang; Juan Du; Yugang Liu; Min Cui; Chunhong Ma; Lihui Han; Zhonghua Qu; Zhiyong Zhang; Zhaohui Sun; Lining Zhang; Youhai H. Chen; Wensheng Sun (Apoptosis, 2007)

High production of laccase by a new basidiomycete, Trametes sp - Pingui Tong; Yuzhi Hong; Yazhong Xiao; Min Zhang; Xiaoming Tu; Tengjiao Cui (Biotechnology Letters, 2007)

Solid Substrate-Room Temperature Phosphorescence Method for the Determination of Trace Mn(II) Based on Oxidizing Reaction of Hydrogen Peroxide Using α,α′-Bipyridine as Sensitizer - Jia-Ming Liu; Xiao-Jie Cui; Fei Gao; Lai-Ming Li; Xiu-Chai Huang; Min-Lan Yang; Fei-Ming Li; Hong Wu (Journal of Fluorescence, 2006)

Pseudomonas stutzeri as a novel biocatalyst for pyruvate production from DL-lactate - Jianrong Hao; Cuiqing Ma; Chao Gao; Jianhua Qiu; Min Wang; Yinan Zhang; Xing Cui; Ping Xu (Biotechnology Letters, 2006)

Experimental investigation of external explosion in the venting process - Zhi-min Du; Xin-qiao Jin; Dong-ming Cui; Jing-fang Ye (Journal of Zhejiang University-SCIENCE B, 2005)

High Frequency of Shoot Regeneration from Hypocotyls and Stem Segments of Antirrhinum majus (Snapdragon) - Min-Long Cui; Kenji Takayanagi; Takashi Handa (Plant Cell, Tissue and Organ Culture (PCTOC), 2004)

Epoxypropane biosynthesis by Methylomonas sp. GYJ3: batch and continuous studies - Jia-Ying Xin; Jun-Ru Cui; Li-Min Zhu; Jian-Bo Chen; Chun-Gu Xia; Shu-Ben Li (World Journal of Microbiology and Biotechnology, 2002)

Photochemical and Microbial Degradation of 2,4,6-Trinitrotoluene (TNT) in a Freshwater Environment - Huey-Min Hwang; L. F. Slaughter; S. M. Cook; Hua Cui (Bulletin of Environmental Contamination and Toxicology, 2000)

Photochemical and Microbial Degradation of 2,4,6-Trinitrotoluene (TNT) in a Freshwater Environment - Huey-Min Hwang; L. F. Slaughter; S. M. Cook; Hua Cui (Bulletin of Environmental Contamination and Toxicology, 2000)

Cloning and Tissue Expressional Characterization of a Full-Length cDNA Encoding Human Neuronal Protein P17.3 - Yingyu Cui; Long Yu; Ruomu Gong; Min Zhang; Yuxin Fan; Peng Yue; Shouyuan Zhao (Biochemical Genetics, 1999)